Disinfection byproducts inhibit methane production and emissions in WWTP effluents and receiving rivers - Fanyan Yang; Dongqi Wang; Shu Chen; Jicheng Zhong; Xin Xu; Hechen Sun; Shengnan Wu; Yufang Li; Ting Liu; Ziqi Ren; Guanghui Zhao; Zhongjie Yu; et al. (Water Research, 2026)

2D discrete element method simulation for direct shear of nonwoven needle-punched geotextile with pillar structure and co-extruded textured geomembrane - Gaojie Xu; Jianyong Shi; Yuping Li; Shi Shu; Xun Wu; Yuchen Zhang; Shijin Feng (Geotextiles and Geomembranes, 2026)

Vacancy-rich Li/Al-LDH synthesized via dual-step freeze-drying for ultrahighly selective lithium extraction from high Mg/Li brines - Shu Wang; Guangming Shi; Yunchang Liu; Yufei Ma; Libo Liao; Yiguo Wu; Jianxiang Ding; Zhi Cheng; Fayang Xing; Nannan Xing; Fei Huang; Changjiang Li (Desalination, 2026)

Evolution of dominant synoptic weather patterns associated with PM2.5 pollution events in the Yangtze River Delta over the past decade - Zhongrui Xie; Lili Shi; Xianman Ye; Qifan Shuai; Yaofu Zhu; Xiyao Chen; Ben Ye; Liang Xu; Min Gao; Shupeng Zhu; Shoujuan Shu; Renguang Wu; et al. (Atmospheric Research, 2026)

SETDB1 induces H3K9me3 methylation modification of RASSF2 to inhibit PTEN and facilitate ovarian cancer progression - Jing Wang; Xinyu Li; Jianmiao Chang; Xiaoxue Hou; Lijia Sun; Yanan Yan; Lisha Shu; Xin Wu (Molecular Genetics and Genomics, 2026)

Integration of clinical and cellular lipidomics identifies a serum metabolite signature predictive of oxaliplatin resistance in colorectal cancer - Xue-fei Wu; Li-ye Xie; Fu-wei Lian; Hao-tang Wei; Shu-fang Ning; Bang-li Hu (Functional & Integrative Genomics, 2026)

HSF4 alleviates ferroptosis in colorectal cancer through transcriptional regulation of MBOAT1/2 - Kelin Yue; Haolin Wu; Kexin Li; Shu Yang; Xuan Bai; Wenjing Zhang; Yu Zhang (Functional & Integrative Genomics, 2026)

Advances in selenium-containing brown rice protein: structural characteristics, functional modification, and applications - Shu Li; Xinjie Shang; Yaxin Wu; Yumeng Wang; Shiyu Lin; Zexu Li; Zhaohui Xu; Yixuan Li; Yao Tang; Rui Yang (Food Hydrocolloids, 2026)

Non-catalytic microwave-assisted co-pyrolysis of glycerol and polypropylene: Product distribution and synergistic mechanisms for monocyclic aromatic hydrocarbons formation - Dong Shu; Yuan Zeng; Anqi Dai; Qiuhao Wu; Linyao Ke; Xiaoling Ma; Hui Li; Yunfeng Zhao; Leilei Dai; Roger Ruan; Yunpu Wang (Environmental Research, 2026)

Elucidating interfacial electronic bridge modulation via p–p orbital hybridization in dual-piezoelectric heterojunction for piezo-photocatalytic water decontamination - Meng Dai; Jingcai Chang; Yulin Huang; Hanxuan Li; Xiaoge Wu; Dong Zhai; Shu-guang Wang; Zuoli He (Chemical Engineering Journal, 2026)

Differential migration, partitioning behavior, and ecological risks of corticosteroids versus phenolic estrogens in coastal riverine tidal flats and bed sediments - Jian Gong; Ke-Xin Yang; Can-Yuan Lin; Qiang Li; Chong Han; Cui-Qin Wu; Shu-Han Zhang; De-Xin Wang; Wei Tao; Qi-Hang Wu; Shen-Ao Liu; Dong-Hao Luo; et al. (Marine Pollution Bulletin, 2026)

Patterns and mechanisms of cross-media antimicrobial resistance development in a typical reclaimed water-receiving urban river - Bang-Ze Li; Shu-Hao Du; Han-Lin Cui; Xin-Xin Gao; Jia-Hao Wu; Bei-Ying Li; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2026)

Contribution of the slab fluids- melts to petrogenesis of adakitic rocks related to gold mineralization: Mo isotopic constraints - Shu-wen Li; Wen-liang Xu; Qun Yang; Yun-sheng Ren; Wu-shuang Zhang; Bin Wang; Kan Gao; Si-tong Chen; Yao-heng Fang; Hao-zhe Li; Tian-ci Liu; Xuan-mei Xue; et al. (Lithos, 2026)

Mussel-inspired construction of superhydrophilic/underwater superoleophobic PTFE membranes using a novel ε-polylysine-based modification for efficient oil-water separation - Xin Wu; Chenyang Li; Shuiling Hong; Ang Gao; Haoming Duan; Wei Li; Shuo Yang; Leixin Yang; Dengkun Shu; Jingwei Xie; Bowen Cheng (Journal of Environmental Chemical Engineering, 2026)

Ru-Co bimetallic catalysts with synergistic crystalline phase regulation and hydrogen spillover for deep hydrodeoxygenation of lignin oil - Jing-jing Wu; Jia-yuan Tian; Feng Lin; Yu-long Ma; Yong-gang Sun; Pei Ma; Shuai-lei Li; Xue Zhang; Yi-shu Ma; Xiao-lin Xue (Journal of Environmental Chemical Engineering, 2026)

Synergistic piezo-photocatalytic activation of PMS by a water hyacinth–derived biochar/BiOCl catalyst for efficient ofloxacin degradation - Liangliang Chang; Zhen Wu; Hucheng Shu; Meilan Li; Bingcheng Bao; Wei Gong; Jinyi Guo; Baoyue Cao (Journal of Environmental Chemical Engineering, 2026)

The dual environmental effects of glyphosate and plastic co-exposure: Microbial synergistic degradation and soil nutrient-cycle alteration - Qian Li; Yanjiao Qi; Jiazhi Gao; Shen Yang; Xiaoyu Wang; Xiuhong Shu; Ying Chang; Dan Zhang; Lan Wu; Feixuan Xiong; Zifan Wang; Hong Zhang (Journal of Environmental Chemical Engineering, 2026)

Synergistic TP/APTES coating on PBT membrane enables superhydrophilicity and efficient oil-water separation - Shuiling Hong; Chenyang Li; Xin Wu; Ang Gao; Haoming Duan; Man Liu; Sijia Zhang; Shuo Yang; Leixin Yang; Dengkun Shu; Jingwei Xie; Bowen Cheng (Journal of Environmental Chemical Engineering, 2026)

A hybrid soft sensing framework for cost-effective monitoring of nitrogen in wastewater treatment under data scarcity - Yaorong Shu; Zhilin Li; Jinpeng Chen; Xiaoyu Lin; Wenjun Liu; Juan Mao; Hui Liu; Feixiang Zan; Xiejuan Lu; Xiaohui Wu (Journal of Environmental Chemical Engineering, 2026)

Role of 2-phenylethanol in regulating population density and biocontrol efficacy of Scheffersomyces spartinae W9 via quorum sensing - Siyi Wu; Xiurong Zou; Yingying Wei; Jiamei Li; Yi Chen; Shu Jiang; Jianfen Ye; Feng Xu; Xingfeng Shao (International Journal of Food Microbiology, 2026)

Corrigendum to “SiO2 oral exposure promotes the crosstalk between NETs and PANoptosis of lung epithelial cells by driving NOX1/ROS, triggering pneumonia in mice” [Journal of Environmental Sciences 162 (2026) 504–516] - Hao Wu; Chunyu Wei; Yidan Wang; Naixi Yang; Shu Li (Journal of Environmental Sciences, 2026)

The influence of replacing soybean meal with corn gluten meal on the digestive and absorptive capacity and amino acid metabolism of sub-adult grass carp (Ctenopharyngodon idella) - Yan Liu; Xiao-Qiu Zhou; Lin Feng; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Wen-Jie Tang; Cheng-Bo Zhong; Pei Wu (Aquaculture, 2026)

The potential role of the Sox9a protein in regulating cyp19a transcription and ovarian development in the olive flounder (Paralichthys olivaceus) - Chang Shu; Lijuan Wang; Congcong Zou; Xungang Tan; Yuxia Zou; Zhihao Wu; Yan Liu; Qiaowan Wu; Ling Wang; Guoyu Wang; Ze Li; Feng You (Theriogenology, 2026)

Linking botany and mineral exploration: Alhagi sparsifolia as a potential indicator for Ni-Cu sulfide deposits - Meng-Meng Cui; Ben-Xun Su; Shan-Ke Liu; Hui-Li Yan; Wen-Jun Li; Bing-Yu Gao; Jing Wang; Zhen-Yan He; Shu-Kuan Wu; Ye-Tao Tang (Journal of Asian Earth Sciences, 2026)

Mitochondrial pathway-mediated gut cell apoptosis: A key mechanism of nitenpyram toxicity in Diaphorina citri adults - Yuning Li; Huyin Hu; Huanqian Yao; Xinyi Xie; Shuyin He; Cuiting Liu; Veeran Sethuraman; Hanhong Xu; Zhongzhen Wu; Benshui Shu (Journal of Asia-Pacific Entomology, 2026)

Novel Streptomyces sp. SCUT-3 promoter’ and 5’UTR chimeras enhanced its alginate lyase expression for kelp degradation - Jun Dai; Hai-Ning Wang; Can Qin; Peng-Bo Dan; Jun-Jin Deng; Lei Wu; Zhi-Wei Li; Fu-Gen Zhang; Chu-Yan Liang; Ming-Shu Zhang; Xiao-Chun Luo (Chemical Engineering Journal, 2026)

Fungal residue dominates soil organic carbon accumulation during vegetation restoration - Shu Zhu; Jiwei Li; Zhenhao Wei; JianZhao Wu; Ziyuan Liu; Zhouping Shangguan; Lei Deng (CATENA, 2026)

Differentiated provisioning in a mobile royal camp: zooarchaeological and stable isotope evidence from Houmingzi, a locality within a Liao–Jin spring nabo site complex, Northeast China - Wuyu Zhou; Yuanyuan Chen; Shu Wang; Zongyu Li; Yunxin Fu; Enxue Feng; Chunxue Wang; Song Wu (Archaeological and Anthropological Sciences, 2026)

Microbial network fragmentation at a coal washing hotspot: Assembly mechanisms and stability implications - Senhua Jiang; Yangkun Shi; Jing Zhang; Chenyu Huang; Yue Li; Wenbo Zhang; Jinghui Ma; Nan Chen; Longfei Shu; Cheng Wang; Feifei Liu; Bo Wu (Applied Soil Ecology, 2026)

The causal effects of immune factors on sarcopenia-related phenotypes - Jin-Li Hou; Yang Chai; Jia-Xin Wu; Ben Niu; Fei-Yan Deng; Shu-Feng Lei (European Journal of Applied Physiology, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

An interpretable stacking model for early warning of mastitis in dairy cows - Haoyu Wang; Shenghui Yang; Yongjun Zheng; Ning Guan; Han Feng; Xiaoyan Pei; Shu Li; Congming Wu; Haiyang Jiang (Preventive Veterinary Medicine, 2026)

Toddacoumalins A-J, ten undescribed coumarins from the roots of Toddalia asiatica - Feng Wu; Han Yao; Xin-Rui Liao; Nan An; Xing-Shu Li; Wen-Hao Hu; Albert S.C. Chan; Hou-Jin Li; Wen-Jian Lan (Phytochemistry, 2026)

Analytical solution for axisymmetric gas flow in layered MSW landfills: Coupling stratification and depth-dependent gas permeability - Xun Wu; Bin Xiao; Bote Luo; Yulin Li; Shi Shu; Yuchen Zhang (Journal of Environmental Management, 2026)

Mineral carbonation: Processes, mechanisms, and its role in the carbon–hydrogen cycle - Dingkui Zhou; Shuyun Cao; Xiaowen Li; Xuemei Cheng; Jianhua Liu; Yanlong Dong; Lefan Zhan; Shichang Wu; Shu Jiang; Guanzhong Shi (Earth-Science Reviews, 2026)

CHBP-loaded mesoporous polydopamine nanoparticles attenuate neuroinflammation and reprogram microglia-neuron crosstalk for spinal cord injury repair - Linyi Xiang; Jiacheng Zhang; Yuzhe Wu; Jingwei Shi; Yun Shu; Ruize Miu; Jiayi Zhao; Junsheng Zhu; Zhichao Tao; Yibo Geng; Haojie Zhang; Zhenglin Li; et al. (Chemical Engineering Journal, 2026)

The Cangshan Mountain Precipitation Experiment (CAMPEX): Modulation of Precipitation by Typical Steep Mesoscale Terrain over Southwest China - Jian Li; Yin Zhao; Gaili Wang; Anlun Xu; Mengke Zhang; Tao Zhang; Baoju Dong; Guotao Zhang; Jian Huang; Yu Li; Cheng Yang; Bin Shu; et al. (Journal of Meteorological Research, 2026)

Real-world study of effectiveness and safety compared among isavuconazole, amphotericin B, and voriconazole in invasive mold disease patients - Ye Qiu; Wu-shu Chen; Zheng-tu Li; Shao-qiang Li; Yan Wang; Yang-qing Zhan; Feng Ye (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

UAV-based crop pest and disease monitoring: A review of multi-source sensing and intelligent methods - Jie Guo; Jin-Hai Li; Le Dong; Shun-Yu Wang; Guang-Yue Wu; Yu-Peng Zhang; Chang-Yong Tao; De-Hua Gao; Shu-Ming Yang; Yu-Tan Wang (Computers and Electronics in Agriculture, 2026)

Coupling microbial electrosynthesis and chain elongation for simultaneous biomethane upgrading and carboxylate recovery: A tunable carbon valorization strategy - Kai-Kai Wu; Shu-tong Wu; Chuan Chen; Zi-Han Wang; Ya-Ru Wang; Li Zhao; Juan Tong; Fei Shen; De-Feng Xing; Nan-Qi Ren; Lei Zhao (Water Research, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

Differential effects of a novel mesoionic insecticide, triflumezopyrim, on Apis mellifera and Apis cerana - Mei-Ling Zhang; Shu-Wei Wang; Wen-Min Li; Sasiprapa Krongdang; Yan-Yan Wu; Ping-Li Dai; Shan-Shan Li; Jing Gao (Journal of Hazardous Materials, 2026)

Stress-dependent stability of microbial sulfidogenic bioremediation is governed by community assembly and evolutionary dynamics - Senhua Jiang; Jing Zhang; Yangkun Shi; Yue Li; Wenbo Zhang; Jinghui Ma; Cheng Wang; Longfei Shu; Feifei Liu; Bo Wu (Journal of Hazardous Materials, 2026)

Rethinking rural small hydropower transition in China through socio-ecological archetypes: Mechanism mapping and scenario simulation - Jiawen Li; Shu Lei; Guiliang Tian; Zheng Wu; Xinyu Liu (Journal of Cleaner Production, 2026)

Novel insights into the legacy effects of NBPT on fungal interactions and pathogenic fungal reduction in agricultural soils - Tikun Guan; Jilin Lei; Huangwei Liu; Jiarui Li; Ting Yang; Qi Wang; Han Wu; Meng Wang; Weizheng Shu; Rui Liu (Journal of Environmental Sciences, 2026)

Impact of high-pressure processing on the degradation kinetics and bioactivity of resveratrol - Wen-Chien Lu; Yu-Tsung Cheng; Yung-Jia Chan; Shu-Ju Chen; Yan-Zhen Wu; Zeng-Chin Liang; Po-Hsien Li (Food Chemistry, 2026)

Ultraviolet-ozone tuned organic-inorganic interface for high-performance PbS quantum dot short-wave infrared photodetectors - Jun Han; Ning Feng; Chuan Wei; Li Yan; Chengrun Shu; Jiatong Liu; Zhouying Wu; Hao Yan; Meili Xu; Yaowu He; Xiaomin Xu; Hong Meng (Chemical Engineering Journal, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Continental Jurassic/Cretaceous transition in Northeast China: Stratigraphic and spatiotemporal constraints from the Hailar Basin and adjacent areas - Chong-Yang Chen; Li-Ping Yao; Pu-Jun Wang; Hai-Bo Wu; Jing-Sheng Li; Yan-Ping Hou; Yun-Fei Xue; Shu-Qin Zhang (Cretaceous Research, 2026)

Research on Collaborative Microseismic Phase Picking for Single-Component Arrays Based on Time-Frequency Two-Dimensional Cross-Correlation - Gui-wu Chen; Yan Li; Shu-xun Zhang; Hao Wang; Shao-lei Song; Peng-Cheng Huang (Applied Geophysics, 2026)

A novel phytoformula targeting lipid peroxidation inhibition attenuates UV-induced skin photoaging - Ling-Ping Wu; Wei Chen; Qian-Pei Lin; Shi-Yun Feng; Jin Dai; Qiong-Yi Zhang; Wen-Yi Chen; Hiroshi Kurihara; Xiao-Min Li; Shu-Hua Ouyang; Yi-Fang Li; Rong-Rong He (PharmaNutrition, 2026)

Low-dose fluoride and lead co-exposure alters bone mineral density in youth: A nationally representative cross-sectional study - Chunxiang Li; Zeyuan Niu; Yuhui Du; Lihong Yang; Fan Wu; Xinxin Hu; Xiaohang Meng; Zichen Feng; Shu Niu; Qing Sun; Yan Wang; Xiaoli Fu; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

Tropical deforestation, seasonal drought and decline of chemical weathering during the Permian–Triassic transition in southwestern China - Wenchao Shu; Daoliang Chu; Yiran Cao; Haijun Song; Paul B. Wignall; Jacopo Dal Corso; Yuyang Wu; Li Tian; Huyue Song; Jinnan Tong (Global and Planetary Change, 2026)

Thermophilic keystone taxa drive humification in coal gangue co-composting via shikimate-pathway carbon flux - Dian Li; Sanghoon Kim; Tian Tang; Shu Wu; Hongye Ma; Yangsheng Liu (Environmental Research, 2026)

Impacts of vegetation management on pollination network structure and robustness in urban parks: A case study from Beijing Wenyu River Park - Yaxuan Li; Meiling Shu; Chenxi Li; Liwen Liu; Yan Zhou; Lan Wu; Yuyu Wang (Urban Ecosystems, 2026)

Lactiplantibacillus Plantarum O126 Postbiotics Boost growth, Antioxidant levels, Disease resistance, and Gut Health in Sea Cucumber (Apostichopus japonicus) - Feng-Li Chen; Hui-Ting Zhao; Wei Gu; Zong-Xiu Wu; Jing-Wen Xiang; Qing Yang; Yu-Lin Yang; Lei Tan; Meng-Xia Sun; Wei Cong; Shu Li; Bin-Tong Yang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Uncovering the Community Structure and Adaptive Characteristics of Soil Protists Across Natural, Semi‐Natural and Highly Degraded Habitats - Shi‐wei Feng; Xiaonan Wang; Ping Wen; Jing‐li Lu; Zhuo‐hui Wu; Xinzhu Yi; Wen‐sheng Shu; Jie‐Liang Liang; Pu Jia; Jin‐tian Li (Environmental Microbiology, 2026)
Protists are vital to soil ecological functions. However, their diversity and community patterns remain poorly characterised across habitats. This study investigated protists in 270 samples spanning five terrestrial ecosystems: natural (forest, grassland, desert), semi‐natural (farmland) and highly degraded (mine wasteland). The species richness of protists and the consumer functional group were highest in farmland and lowest in mine wasteland. We demonstrated that habitat type ( R partial Mantel = 0.291) exerted stronger effects on protistan communities than geographic distance ( R partial Mantel = 0.072). While α‐diversity drivers varied among habitats (e.g., total phosphorus (TP) was only positive in farmland and forest), β‐diversity was consistent and significantly correlated with mean annual temperature (MAT), mean annual precipitation (MAP), aridity index (AI) and moisture. We identified nine potential ecological groups of protists, reflecting their adaptive differentiation. To explore community assembly, a null model was conducted, revealing that stochastic processes dominated all habitats. Furthermore, co‐occurrence networks of protists, prokaryotes and fungi showed lower modularity and stability in mine wasteland compared with other habitats, indicating co‐occurrence patterns may be more specialised under resource limitation. Collectively, our results highlight the importance of habitat type in shaping protistan communities, suggesting that protists can be predictably regulated in degraded environments.

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Hydroxytyrosol preserves myofibrillar protein integrity in grass carp (Ctenopharyngodon idella): Implications for flesh quality enhancement - Yi-Wei Liao; Pei Wu; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2026)

Nanofiber engineering of covalent organic frameworks via monomer–solvent synergy for high-efficiency uranium capture - Xiao-yi Tang; Qun-yan Wu; Yi-chen Huang; Peng-fei An; Lin Wang; Ji-pan Yu; Shu-sen Chen; Zi-jie Li; Li-yong Yuan; Wang-suo Wu; Zhi-fang Chai; Wei-qun Shi (Journal of Hazardous Materials, 2026)

Diverse arc magmatism generated by depth-dependent melting of subducted mélange: Evidence from the Gangdese Belt, South Tibet - Haoyu Yan; Jie Li; Chutian Shu; Bin Wu; Ahmed E. Masoud; Xiaoping Long (Global and Planetary Change, 2026)

Injectable nanocomposite depot with real-time ultrasound control of osteogenic drug release - Yu Shu; Xiang Zhang; Ruonan Jiang; Shunan Wang; Yin Yi; Wenting Du; Siyi Li; Yuanyuan Liu; Huimin Liang; Pengfei Zhou; Panpan Liang; Jinlin Song; et al. (Chemical Engineering Journal, 2026)

LEO-augmented real-time kinematic with different multi-GNSS/multi-frequency combinations - Yang Sun; Pan Li; Liang Zhang; Zhiyuan Wu; Jingkai Yuan; Mingbao Wei; Meifang Wu; Kan Wang; Bao Shu; Guanwen Huang; Qin Zhang (Advances in Space Research, 2026)

Model-based insights into temperature-driven declines in groundwater recharge under global warming in Michigan’s Lower Peninsula - Jing Zhang; Si-Chen Wu; Shu-Guang Li; Hua-Sheng Liao; Shi-Tao Peng; Jian-Min Zhang (Hydrological Sciences Journal, 2026)

Seismic vulnerability analysis of cable-stayed bridge based on kernel function improved response surface method - Yan Liang; Yingsen Miao; Li Yan; Bo Wu; Pinwu Guan; Jingxiao Shu (Soil Dynamics and Earthquake Engineering, 2026)

PpMYC2 positively regulates chilling tolerance of peach fruit by suppressing sucrose degradation - Qian Li; Yingying Wei; Yi Chen; Shu Jiang; Jianfen Ye; Fangming Wu; Feng Xu; Xingfeng Shao (Postharvest Biology and Technology, 2026)

Enhanced decoupling of multiple elements in coastal reclaimed soils following intensive agricultural use in eastern China - Shengzhi Liu; Xiaobo Bian; Yifeng Zhu; Danyang Wang; Aijing Yin; Pengbao Wu; Xiaohui Yang; Zhaofu Li; Qiang Shu; Huan Zhang; Chao Gao (Journal of Cleaner Production, 2026)

SiO2 oral exposure promotes the crosstalk between NETs and PANoptosis of lung epithelial cells by driving NOX1/ROS, triggering pneumonia in mice - Hao Wu; Chunyu Wei; Yidan Wang; Naixi Yang; Shu Li (Journal of Environmental Sciences, 2026)

Sodium alginate enhances rheological properties and curcumin encapsulation in donkey myofibrillar protein Pickering emulsions: Molecular docking and experimental insights - Hui Shen; Jingsong Zhu; Yingxue Jiao; Yajing Qi; Teng Li; Wenhui Qi; Ying Shu; Kaixuan Zhao; Fengyang Wu; Chi Ren; Zhisheng Zhang (Food Chemistry, 2026)

Investigation of pipe–soil interface effects on the stress–deformation behavior of buried high-density polyethylene pipes: full-scale test and analytical solution - Yuchen Zhang; Jianyong Shi; Yu Ping Li; Shi Shu; Xun Wu (Computers and Geotechnics, 2026)

Injectable curdlan-derived hydrogel with differential release of copper and zinc ions for synergistic therapy of infected wounds - Haiyan Wang; Chenyang Ding; Chenjun Liu; Wenjun Sun; Ben Wu; Huali Nie; Haiyan Li; Xiao Feng; Linyuan Shu; Hui Sun; Siyu Ni (Carbohydrate Polymers, 2026)

High-efficiency restoration of stone cultural relics via immobilized carbonic anhydrase on magnetic graphite oxide - Yaofeng Hu; Yifan Gui; Wei Li; Cuiling Gong; Ziqi Hou; Tong Shu; Ya Wu; Gen Lu; Longjiang Yu (Bioresource Technology, 2026)

The research on landslide spatial prediction method based on knowledge graph and representation learning: a case study of Anxi county, Fujian Province - Xinlei Jin; Daichao Li; Shu Wang; Peng Ye; Jialiang Gao; Mingjiang Liu; Zhenwei Zeng; Sheng Wu (Bulletin of Engineering Geology and the Environment, 2026)

Dissecting the aberrant vasculature of glioblastoma: mechanisms and therapeutic targets - Yinan Li; Yinfei Du; Fan Guan; Xuetong Li; Shu Cui; Wei Gao; Xinmiao Long; Minghua Wu (Cancer and Metastasis Reviews, 2026)

Quorum sensing-driven biofilm cathode of Shewanella oneidensis for enhanced uranium adsorption: Elucidating the role of exogenous AHLs and validation in actual uranium-contaminated groundwater - Jing Sun; Hong Shu; Xiaoyan Wu; Tingting Liu; Guangyue Li; Zhao Cui; Ting Li; Xiaowei Zhou; Zhongran Dai; Qian Li (Journal of Hazardous Materials, 2026)

Seawater reforming of ethanol and acetic acid over Ni/SBA-15 catalysts: Salt-induced deactivation pathways - Yunyu Guo; Yueyue Song; Yangfan Zhang; Wenjian Liu; Fei Wu; Chao Li; Yuchen Jiang; Guozhu Chen; Shu Zhang; Xun Hu (Desalination, 2026)

Imiquimod-induced colitis: A novel ROS/ERK-driven model of intestinal inflammation and barrier dysfunction - Kuang-Ting Liu; Shu-Hao Chang; Kuan-Chen Wu; Zheng-Yi Li; Mao-Chia Chang; Yen-Chu Huang; Mu-Chi Chung; Shih-Chung Wang; Yi-Ju Chen; Jeng-Jer Shieh (Chemico-Biological Interactions, 2026)

Integrative combination of gas–liquid-phase plasma mutagenesis and high-throughput screening to enhance eicosapentaenoic acid production by Schizochytrium sp. - Chao Yu; Jialin Zhu; Jinyong Wu; Xiangsong Chen; Shuhuan Lu; Xiangyu Li; Sa Zhao; Weiwei Zhu; Min Shu; Mianbin Wu; Jianming Yao (Journal of Zhejiang University-SCIENCE B, 2026)

Genomic insights into the diversity of rice cultivars developed in Heilongjiang Province, China - Yuhan Zhou; Naixin Liu; Jiaqi Yang; Baicui Chen; Chengxin Li; Fanshan Bu; Sanling Wu; Ziqi Zhou; Qingtao Yu; Qingyao Shu (Journal of Zhejiang University-SCIENCE B, 2026)

The Impact of Delay Time on Blasting Mining Efficiency: Insights from Simulations and Field Experiments - Tao Hu; Xiang-long Li; Jian-guo Wang; Chun-ping Wu; Shu-feng Liang; Bao-qian Huan (Applied Geophysics, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Shear-slip calculation for the interface between anchor bolt grouting body and surrounding rock considering the expansion effect: theoretical model and numerical simulation - Wei Shu; Baolong Zhu; Honggang Wu; Jing Li (Ocean Engineering, 2026)

PE microplastics altered microbial resource limitation and C/N use efficiency in cotton rhizosphere soil - Yudong Chen; Xiaotong Li; Yulin Shu; Zhoukang Li; Guang Yang; Jinlong Wang; Qiong Wu; Wen Cao; Eryang Li; Yuehan Liu; Wusong Li; Guanghui Lv (Journal of Hazardous Materials, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

An innovative modified coal gangue capable of improving sandy soil remediation, wheat growth and drought resistance - Tian Tang; Shu Wu; Dian Li; Hongye Ma; Zheng Wang; Liuzhou Chen; Sanghoon Kim; Yajun Wang; Yangsheng Liu (Chemical Engineering Journal, 2026)

Mesoporous catechin nanocarriers potentiate curcumin to treat osteoarthritis via synergistic antioxidant and macrophage repolarization - Xinyu Zhang; Junyan Li; Ye Zhu; Huilin Hu; Ping Gong; Hui Xu; Ningli Guo; Quanzhou Wu; Chao Lou; Minghao Chao; Zhang Chen; Minjiang Chen; et al. (Chemical Engineering Journal, 2026)

Icariside II sensitizes osteosarcoma to doxorubicin through the lincROR/Wnt/β-catenin signaling regulatory axis - Shu-ting Zhou; Zhi-peng Li; Yong-xin Mai; Yu-Yan Wang; Feng-xiang Pang; Jin-fang Zhang; Xian-lin Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Ultra-low limit heparin detection based on 11-mercaptoundecanoic acid /chitosan functionalized and AuNPs enhanced fiber surface plasma - Jun Wu; Meijuan Jia; Meihui Zhang; Minglu Li; Shu Fang; Jie Dong; Anhua Dong; Ruotong Tian; Jun Zhou; Changyu Shen (Analytica Chimica Acta, 2026)

S100A8 aggravates sepsis-associated encephalopathy by promoting PFKFB3-dependent glycolysis and microglial neuroinflammation - Hongjie Hu; Shu Peng; Jingbo Chen; Dayong Li; Shuhui Wu; Hebin Jiang; Yuru Lu; Yaqin Song; Wei Zhu (Inflammation Research, 2026)

Bioactive metabolites from Samsoniella sp. KY1174: isolation, characterization, and cytotoxicity against cancer cell lines - Xingtong Chen; Huiting Wu; Huilin Shu; Haoyu Yu; Fan Cai; Jianbin Xiao; Wei Lin; Yuxin Shi; Mingliang Zhang; Qin Li; Huaidong Zhang; Wanhao Chen; et al. (Natural Product Research, 2026)

Comparative Proteomic Profiling of a Virulent Wild-Type Nocardia seriolae and Its Attenuated Vaccine Strain - Yao Yao; Weimei He; Li Wu; Lei Huang; Chengying Li; Yingying Tao; Xiaoyi Pan; Jianhong Shu; Yulong He; Jiayun Yao; Huapeng Feng (Fishes, 2026)
Nocardia seriolae (N. seriolae) is a significant bacterial pathogen in global aquaculture, causing substantial economic losses. Live-attenuated vaccines represent a promising control strategy, but their molecular mechanisms remain poorly understood. This study employed a quantitative proteomic approach to compare the proteomic profiles of a virulent wild-type strain (F1) and an attenuated vaccine strain (F110) of N. seriolae. Using a data-independent acquisition (DIA)-based LC-MS/MS analysis, we identified 4516 proteins, with 540 showing significant differential expression (311 upregulated, 229 downregulated). Bioinformatic analysis revealed that upregulated proteins in F110 were primarily involved in metabolic processes, including phosphatidate cytidylyltransferase and various enzymes related to amino acid and nucleotide metabolism. Conversely, downregulated proteins were enriched in virulence-associated functions, including HtpX and MFS transporter permease. These findings suggest that attenuation involves a complex reprogramming of metabolic pathways coupled with a reduction in key virulence factors, providing insights into the potential molecular basis of vaccine development and potential targets for novel therapeutic strategies.

Dynamic changes in epidermal wax composition and quality of three goji berry varieties during postharvest storage - Ben Niu; Zihao Zong; Yifan Ding; Huizhi Chen; Weijie Wu; Maratab Ali; Mohamed A. Farag; Xiangjun Fang; Ting Huang; Chaoyi Shen; Li-shu Wang; Ruiling Liu; et al. (Postharvest Biology and Technology, 2026)

Sulfite exporter SsTauE enhances bacterial feather degradation by maintaining sulfur homeostasis - Lei Wu; Ming-Shu Zhang; Zhen-Dong Yang; Zhi-Wei Li; Jun-Jin Deng; Xiao-Chun Luo (International Biodeterioration & Biodegradation, 2026)

Untargeted metabolomics elucidates the enhanced protective effects of blackberry juice fermented with Lacticaseibacillus paracasei on hypothalamic-pituitary-adrenal (HPA) axis neuronal dysfunction - Han Wu; Qing-Ru Di; Anthony Pius Bassey; Shu-Dong Xie; Maria G. Corradini; Jian-Zhong Zhou; Xiao-Li Liu (Food Chemistry, 2026)

Desert ecosystem gradient heterogeneity alters rhizosphere soil elemental stoichiometric homeostasis and microbial nutrient limitations - Yudong Chen; Xiaotong Li; Yulin Shu; Wenjing Li; Wen Cao; Qiong Wu; Yuehan Liu; Eryang Li; Jinlong Wang; Wusong Li; Guanghui Lv (CATENA, 2026)

Differences between daytime and nighttime in the impacts of anthropogenic aerosol-radiative-cloud interaction on the summer precipitation over the mid-lower Yangtze River Basin - Zhuohui Wang; Shu Li; Anning Huang; Xinsheng Zhu; Tijian Wang; Bingliang Zhuang; Mengmeng Li; Rongchang Wu (Atmospheric Environment, 2026)

Geographical effects on ambient air pollution and clinical visits for respiratory diseases: a case study with three exposure scenarios - Hui-Ju Wen; Shu-Li Wang; Chih-Da Wu; Mao-Chang Liang (Atmospheric Pollution Research, 2026)

Genome-wide analysis of Zoysia japonica REVEILLE family identifies ZjRVE8-1 as a positive cold-tolerance regulator - Cuiling Liu; Liangliang He; Ming Jiang; Zhihao Wu; Jieyi Li; Chao Liu; Quanrui Su; Jingyi Sun; Fei Xu; Shu Chen (Plant Cell Reports, 2026)

Quercetin Alleviates Postoperative Cognitive Dysfunction of Aged Mice by Regulating Microglial Polarization through Inducing miR-379-5p RNA Modification - Shu Rong Li; Long Wang; Yi Wei Li; Yi Xiao Li; Ren Wei Li; Zhi Fang Zhuo; Qing Hua Wu (Molecular Neurobiology, 2026)

The Reorganization of Cerebellar Functional Network Topology in Post-stroke Aphasia: A Resting-State fMRI Study - Liting Chen; Zhenye Luo; Wenfeng Mai; Xiaoling Wu; Xiaole Fan; Lifeng Li; Yongqiang Shu; Xiaoyun Chen; Qun Fang; Hong Wang; Yanhong Dai; Shuixing Zhang (Molecular Neurobiology, 2026)

Reciprocal rate-modulated evolution of slow-moving reservoir landslide: learning from hydrological-adapted block model - Shu Zhang; Qiang Li; Huiming Tang; Zongxing Zou; Jianfan Zhao; Jiefei Zhang; Meiling Wu (Landslides, 2026)

Comparison of soil enzyme activity and stoichiometry between urban park and forest in the Pearl River Delta region, China - Han Sheng; Xu Li; Luis Carlos Ramos Aguila; Fasih Ullah Haider; Shu-Yi-Dan Zhou; Guopeng Wu; Chushu Meng; Yunxuan Deng; Juxiu Liu (Applied Soil Ecology, 2026)

Global patterns and drivers of canopy storage capacity in different biomes - Meng-Di Wu; Zhi-Yun Jiang; Si-Yi Zhang; Yu-Jun Ma; Shui-Xia Li; Shu-Qin Han; Jin-Zhao Liu (Agricultural and Forest Meteorology, 2026)

Large-scale analysis of SARS-CoV-2 genomic data from sewage using eVarEPS reveals that amino acid mutations detected in sewage provide an early warning on population prevalence - Ziquan Lv; Chang Shu; Yulin Fu; Yinghui Li; Shisong Fang; Xiangjie Yao; Qinglan Sun; Kesheng Peng; Jian Lu; Guomei Fan; Dongmei Liu; Jinzhen Tang; et al. (Water Research, 2025)

Enrichment of anthropogenic organic matter and acetoclastic pathway dominates ebullition CH4 production in urban river - Shengnan Wu; Dongqi Wang; Hongmei Ma; Yufang Li; Guanghui Zhao; Hechen Sun; Fanyan Yang; Xin Xu; Ting Liu; Ziqi Ren; Shu Chen; Chenyang Wu; et al. (Water Research, 2025)

Wave propagation characteristics and parameter sensitivity analysis of Longmaxi shale in deep oil and gas reservoirs under multiple dissipation mechanisms - Jiajun Shu; Tao Li; Lijie Wu; Yue Li; Bingni Wu; Bo Liu; Zhengding Deng; Jingzhu Huang; Rubén Galindo; Fausto Molina Gómez (Soil Dynamics and Earthquake Engineering, 2025)

Di-2-ethylhexyl phthalate may exaggerate allergic response in boys with atopic dermatitis – 4-year follow-up of the Taiwan Maternal and Infant Cohort Study - Chin-Li Lu; Hui-Ju Wen; Chiung-Shiow Wang; Chien-Wen Sun; Ming-Tsang Wu; Mei-Lien Chen; Chia-Jung Hsieh; Shu-Li Wang (Science of The Total Environment, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Gaussian feature-enhanced distributed neural network control for multi-AUV formation based on tunnel prescribed performance and high-order control barrier functions - Di Wu; Dong Li; Bang Song; Minghao Chen; Lingling Liu; Feng Shu (Ocean Engineering, 2025)

Gene expressions in newborns and the association with prenatal exposure to phthalate plasticizers – The Taiwan Maternal and Infant Cohort Study (TMICS) - Yi-Ju Wu; Hui-Ju Wen; Chung-Hsing Chen; Shin-Fen Tsai; Shih Sheng Jiang; Shu-Li Wang (Journal of Hazardous Materials, 2025)

Soil organic carbon decline under bamboo invasion: The role of microbial carbon cycling - Chushu Meng; Chaotang Lei; Xu Li; Han Sheng; Guopeng Wu; Juxiu Liu; Shu-Yi-Dan Zhou (Journal of Environmental Management, 2025)

Metal transformation, immobilization, and risks in ceramsite production via co-sintering of metal-contaminated soil and coal gangue - Guopeng Ke; Wu Zeng; Jingyong Liu; Yaohuang Li; Ruzhu Yang; Shuyu Dong; Qunyi Shu; Tao Chen; Wenxiao Huang; Weixin Li (Fuel, 2025)

Donkey myofibrillar protein/sodium alginate-stabilized high internal phase Pickering emulsion as fat substitutes in emulsion-type sausages: Physicochemical, sensory properties and freeze-thaw stability - Wenhui Qi; Hui Shen; Yingxue Jiao; Teng Li; Joel Rivadeneira; Ying Shu; Kaixuan Zhao; Fengyang Wu; Liwen Wang; Zhisheng Zhang (Food Research International, 2025)

Electrospun GeP/PVDF piezoelectric composite membrane as a functional separator for lithium dendrite suppression - Kewei Shu; Yi Zhang; Qijie Wu; Yan Zong; Huilan Li; Chen Zhao (Chemical Engineering Journal, 2025)

The effects of non-solvating and weakly solvating diluents on the solvation structures and dynamical properties of localized high-concentration electrolytes for lithium metal batteries - Tao Wang; Yuechao Wu; Junyu Huang; Hongjin Li; Yuyang Zhang; Shu Li; Tianying Yan (Chemical Engineering Journal, 2025)

Lactobacillus delbrueckii Alleviate Oxidative Stress and Intestinal Injuries by Activating TLR2 and TLR4 Expressions in IPEC-J2 Cells - Fengming Chen; Shu Wu; Xiaoyu Wang; Yinghui Li; Binsheng He; Yafen Fu; Xingguo Huang; Jiayi Chen (Probiotics and Antimicrobial Proteins, 2025)

A comprehensive analysis of scRNA-Seq and RNA-Seq unveils B cell immune suppression in the AAV-loaded brain - Shunyu Wu; Lu Xue; Xiang Li; Yaoxuan Wang; Yuting Zhu; Yuanbo Luo; Jiayu Sun; Tingting Jin; Wenying Shu; Zhaoyan Wang (Immunologic Research, 2025)

Multi-modal fusion model combines SERS spectroscopy and clinicopathological features to predict neoadjuvant therapy response in breast cancer - Murong Li; Fei Xie; Longfei Yin; Xiongwei Cai; Wenting Yu; Zhaonan You; Tiantian Liu; Lei Chen; Song Yu; Guohua Wu; Shu Wang (Analytica Chimica Acta, 2025)

Efficient socket-based data transmission method and implementation in deep learning - Xin-Jian Wei; Shu-Ping Li; Wu-Yang Yang; Xiang-Yang Zhang; Hai-Shan Li; Xin Xu; Nan Wang; Zhanbao Fu (Applied Geophysics, 2025)

Oxidative stress and ferroptosis in diabetic cardiomyopathy: mechanistic interplay and therapeutic implications - Shan Li; Yuhe Shu; Shuyu Yang; Simin Zhang; Haoling Chen; Dan Wu; Bo Li; Li Dong (Apoptosis, 2025)

Dispersion characteristics of seismic wave reflection and transmission in porous media strata via the improved Biot model - Jiajun Shu; Tao Li; Ruiqi Yuan; Yue Li; Bingni Wu; Zhengding Deng; Jingzhu Huang (Soil Dynamics and Earthquake Engineering, 2025)

Transcriptional module AdERF195-AdIDH1 regulates citrate degradation in kiwifruit during the low temperature storage - Xin-yi Li; Hong-min Shu; Yang Tong; Xiao-fen Liu; Chao-jie Wu; Xiang Li; Xue-ren Yin; Ying-ying Wu (Postharvest Biology and Technology, 2025)

Deciphering coastal plain groundwater dynamics: insights from satellite and hydrologic data in Pinghu City, China - Chengcheng Wu; Chengpeng Lu; Edward Park; Yunfeng Wang; Yangcun Xie; Alain M. Plattner; Zhibin Li; Bo Liu; Longcang Shu; Yong Zhang (Journal of Hydrology, 2025)

Yorkie involves in immune response under hypoxia stress in Chinese mitten crab (Eriocheir sinensis) - Yuhan Ma; Yuchang Zhu; Chang Liu; Yiyang Xu; Zihao Wu; Yuhan Tu; Junwei Guo; Siyue Li; Yuting Xi; Jialin Li; Dazuo Yang; Rantao Zuo; et al. (Fish & Shellfish Immunology, 2025)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

UV-switchable dual-mode sensing in a lead-free CsCu2I3 perovskite sensor for selective detection of mixed amines - Rui Wu; Qingyi Guan; Mingji Xu; Ruixiang Li; Shu Chen; Chunhua Luo; Hui Peng; Hechun Lin (Chemical Engineering Journal, 2025)

Sequential release of an injectable depot simulating the bone healing mechanism based on LIPUS for bone defects repair - Xujia Shan; Xiaoyan Yuan; Siyi Li; Wenting Du; Xiang Zhang; Yin Yi; Yu Shu; Shunan Wang; Ruonan Jiang; Pengfei Zhou; Huimin Liang; Yuanyuan Liu; et al. (Chemical Engineering Journal, 2025)

Bi-directional pH-responsive cellulose nanocrystals-based pesticide microcapsules for sustainable agriculture - Jia-wei Ding; Li-na Guo; Shu-heng Li; Qin Gao; Wang Wu; De-qiang Li; Jun Li (Carbohydrate Polymers, 2025)

A novel method to quantify Dendrobium officinale polysaccharides in biological samples via 99mTc-labelling and radioHPGPC analysis - Pengfei Dou; Jinglin Wang; Yamin Shu; Fang Cheng; Gang Nie; Li Luo; Zhijing Wu; Ziming Zheng; Yongkang Gai; Junxi Liu; Yan Liu; Yinxing Zhou; et al. (Carbohydrate Polymers, 2025)

Natural lignan justicidin A-induced mitophagy as a targetable niche in bladder cancer - Kai-Hsun Chang; Hsin-Chih Chen; Ching-Ying Chen; Shu-Ping Tsai; Man-Yuan Hsu; Pao-Yuan Wang; Shan-Ying Wu; Chun-Li Su (Chemico-Biological Interactions, 2025)

Stability deterioration and failure analysis of dangerous rock masses in cold regions under the influence of freeze-thaw cycles - Jiajun Shu; Tao Li; Bingni Wu; Zhengding Deng; Jingzhu Huang (Journal of Mountain Science, 2025)

Human adenovirus in Taiwan, 2019–2023 - Su-Lin Yang; Wan-Ju Tsai; Chung-Hao Li; Yu-Hsin Cheng; Shu-Wei Lin; Ming-Tsan Liu; Fang-Tzy Wu (Archives of Virology, 2025)

Two new compounds from the root bark of Acanthopanax gracilistylus and their inhibitory effects on neutrophil elastase, cyclooxygenase-1, and cyclooxygenase-2 in vitro - Jin-Yuan Duan; Shu-Ming Li; Hao-Dong Yang; Yuan-Gui Yang; Jiao-Feng Wu; Jing-Yu Weng; Hong-Bo Liu; Hong-Bo Xu (Phytochemistry Letters, 2025)

Molecular insights into sodium alginate selective flotation separation of bastnaesite from calcite and fluorite - Min Liu; Jia Tian; Longhua Xu; Xin Wu; Guohuan Li; Zhiyuan Wang; Kaiqian Shu; Kai Xue; Yi Luo; Yue Cao; Donghui Wang; Zhoujie Wang (Journal of Environmental Chemical Engineering, 2025)

Revealing the mechanisms of riboflavin and choline enhances performance of the anaerobic digestion of food waste: Efficiency, microbial communities, and functional genes - Chengyuan Su; Guangrong Zhou; Fengxiu Ding; Lipeng Wu; Shu Gao; Qiuhong Li; Yuxiang Lu; Peng Zheng; Shenglong Chen (Journal of Environmental Chemical Engineering, 2025)

Dietary biotin facilitates collagen deposition and myofiber growth and development, improving muscle chewiness and hardness in grass carp (Ctenopharyngodon idella) - Yang Yang; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng; Xiao-Qiu Zhou (Food Bioscience, 2025)

High-throughput real-time detection of sepsis inflammatory biomarker proteins in clinical samples using metasurface plasmon resonance biosensors - Jing Wu; Youqian Chen; Liping Huang; Yuhan Sun; Jingjing Zhao; Xiaoyang Cheng; Ruiwen Sun; Hanlin Zhou; Yue Shu; Wen Li; Wenhong Zhang; Wei Liu; et al. (Chemical Engineering Journal, 2025)

Highly efficient and sustainable bioconversion of cottonseed meal to high-value products through solid-state fermentation by protease-enhanced Streptomyces sp. SCUT-3 - Zhen-Jie Dai; Ming-Shu Zhang; Zhi-Wei Li; De-Lin Lu; Lei Wu; Can Qin; Hai-Ning Wang; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Unveiling Moxibustion's Impact on AD Mice Learning and Memory: Role of Mitochondrial Respiratory Chain Complex I Subunit in the Hippocampus - Yuan Shen; Hong-Ying Li; Qing-Qing Yang; Ke Zhang; Shu-Qing Liu; Ning Zhang; Chen-Yu Li; Shu-Guang Yu; Lu-Shuang Xie; Qiao-Feng Wu (Molecular Neurobiology, 2025)

2-Arylbenzofurans from the stems and leaves of Artocarpus tonkinensis and their potential antiproliferative activities - Jia-Ming Guo; Lin-Xuan Li; Xin-Yi Li; Tian-Yu Wang; En-Ning Zhu; An-Jiao Wu; Shu-Ri Li; Hui- Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2025)

Overlooked role of aged cationic natural organic matter in aquatic microplastics aggregation-sedimentation - Qian Peng; Zhiyan Feng; Miao Li; Chencheng Qin; Xiaoai Guo; Jiaxin Wu; Aoqiang Shu; Lin Liu; Xiaodong Wu; J. Paul Chen; Xingzhong Yuan; Hou Wang (Water Research, 2025)

In situ addition of layered double hydroxides promotes sulfate-dependent anaerobic methane oxidation and microbial community shifts in freshwater-influenced mangroves sediments - Jijuan Ding; Fei Liu; Jing Huang; Ping Li; Junmao Zhang; Bo Wu; Longfei Shu; Zhili He; Cheng Wang (Water Research, 2025)

High-frequency sequence patterns in lacustrine basins: Insights from delta-hyperpycnal flow systems in the Middle Jurassic shale interval, Sichuan Basin, China - Haocheng Shi; Benzhong Xian; Yichen Liu; Zhiyun Yu; Lin Zhao; Junyang Geng; Rongheng Tian; Qianran Wu; Li Liu; Yujie Shuai; Yi Shu (Sedimentary Geology, 2025)

Combined transcriptome and metabolome analyses provide insights into host adaptation mechanism of Spodoptera frugiperda to cruciferous vegetables - Benshui Shu; Yuning Li; Cuiting Liu; Junying Wu; Cuiling Ye; Jintian Lin; Jingjing Zhang (Journal of Insect Physiology, 2025)

Why is the combined treatment of copper and aluminum more toxic to citrus than single factor treatment? - Wen-Shu Chen; Ti Wu; Tian-Tian Xia; Liang-Yuan Tong; Fei Lu; Xin Ye; Jiuxin Guo; Zeng-Rong Huang; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2025)

Modified coal gangue enables synchronous sandy soil remediation and safe potato production: Efficacy and mechanisms - Tian Tang; Zheng Wang; Liuzhou Chen; Shu Wu; Dian Li; Hongye Ma; Sanghoon Kim; Yajun Wang; Yangsheng Liu (Journal of Cleaner Production, 2025)

Gridded forest carbon sinks and carbon removal projections from 2020 to 2060 in China - Min Jia; Shu Ye; Li Zhang; Pengcheng Wu; Ni Huang; Yanfeng Bai; Jianhui Ruan; Zhuoming He; Mingyu Li; Shaoyuan Chen; Li Wang; Bofeng Cai; et al. (Journal of Environmental Management, 2025)

Identification of a Streptomyces sp. SCUT-3 aminopeptidase SsLap1 and its synergistic with endopeptidase Sep39 for peanut meal hydrolysis - Hua-Hong Cai; Ming-Shu Zhang; Lei Wu; Zhi-Wei Li; Can Qin; Chu-Yan Liang; Jun-Jin Deng; Xiao-Chun Luo (Food Bioscience, 2025)

6,7-Dimethoxy-3H-Quinazolin-4-One as a dual-function inhibitor of polyphenol oxidase and bacteria: biological evaluation, mode of action, and anti-browning studies - Xiu-Zhen Li; Jin-Rui Qiao; Yi-Rui Wu; Dong-Yan Zhou; Yu-Dan Shi; Shu-Meng Zhu; Qiu-Han Bai; Xiao-Lei Xia; Wei-Ming Chai (Food Bioscience, 2025)

Characterization of microbial consortium for rice straw degradation and the role of nitrogen sources in community assembly - Liuzhou Chen; Tian Tang; Dian Li; Zheng Wang; Shu Wu; Yangsheng Liu (Chemical Engineering Journal, 2025)

Topology-engineered semi-crosslinked phosphaphenanthrene architectures for epoxy resins: Unlocking synergistic flame retardancy, mechanical, and dielectric properties - Ze-Kun Wang; Yan-Fang Xiao; Shu-Gen Wu; Zhen Qin; Yu-Zhong Wang; Li Chen (Chemical Engineering Journal, 2025)

Incorporating frequency domain features into radiomics for improved prognosis of esophageal cancer - Shu Chen; Shumin Zhou; Liyang Wu; Shuchao Chen; Shanshan Liu; Haojiang Li; Guangying Ruan; Lizhi Liu; Hongbo Chen (Medical & Biological Engineering & Computing, 2025)

Two new diarylheptanoids from Curcuma kwangsiensis rhizomes - Shuo-Guo Li; Le Deng; Qiu-Fang Chen; Rui Yang; Cao-Min Zou; Shu-Mei Wang; Meng-Hua Wu; Jiang Meng (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A new method for identification of effective hydrocarbon source rocks and evaluation of relative contributions to reservoirs - Huiyi Xiao; Tao Hu; Xiongqi Pang; Yunlong Xu; Yao Hu; Caijun Li; Tianwu Xu; Dingye Zheng; Tingyu Pu; Chenxi Ding; Zhiming Xiong; Shu Jiang; et al. (Marine and Petroleum Geology, 2025)

Application of a PMF+BMR hybrid model for source apportionment and ecological risk assessment of soil heavy metal(loid)s - Jiaheng Wu; Huijuan Wang; Zilin Han; Yilan Shu; Xinmiao Huang; Qicheng Zhong; Rongxi Li; Zhengqiu Fan (Journal of Hazardous Materials, 2025)

Interfacial strength vs toughness: Enhancing mechanical and impact performance of CF/PEEK thermoplastic composites - Yu Gao; Song Yan; Kaiyan Min; Xiahui Liu; Yue Li; Ju Wu; Jianfeng Zhou; Shu Zhu; Peng Wang (Chemical Engineering Journal, 2025)

Genetic identification and characterization of two novel loci for grain arsenic concentration in tetraploid wheat at various field environments - Zhaoyong Zeng; Dandan Ou; Li Yin; Yueyi Wu; Yuanfeng Huo; Yinggang Xu; Huaping Tang; Shu Yuan; Xuesong Gao; Yusheng Qin; Jian Ma; Guangdeng Chen (Plant and Soil, 2025)

MiR-21-5p promotes RPE cell necroptosis by targeting Peli1 in a rat model of AMD - Yishun Shu; Ziwen Li; Tianyi Zong; Tong Mu; Haoyuan Zhou; Qian Yang; Meili Wu; Yanqiu Liu; Tianhua Xie; Chengye Tan; Miao Zhuang; Xiaolu Wang; et al. (In Vitro Cellular & Developmental Biology - Animal, 2025)

Seasonal groundwater variations in the coastal plain under intense human activities: Hydrochemical evolution, quality degradation, and health risk assessment - Zhibin Li; Chengpeng Lu; Yong Zhang; Xilin Yu; Qize Gao; Zhenhuan Yuan; Chengcheng Wu; Bo Liu; Longcang Shu (Journal of Environmental Management, 2025)

Effects of mono- and di-glycerides/phospholipids (MDG/PL) on the bioavailability of lutein and DHA in rats: more effective for lutein - Shu-zhen Huang; Huan-huan Yin; Fang Tian; Liang Wang; Wen-jing Wu; Xiang Li; Yanrong Zhao; Xiao-ya Wang; Yun Li; Megan Terp; Ying-yi Mao; Jin-yao Chen (Food Bioscience, 2025)

Hypoxia-inducible factor-1α involves in regulating anti-lipopolysaccharide factors expression via NF-κB under hypoxia stress in Chinese mitten crab (Eriocheir sinensis) - Yuhan Ma; Zihao Wu; Yuhan Tu; Chang Liu; Junwei Guo; Yiyang Xu; Siyue Li; Yuting Xi; Jialin Li; Tongjun Ren; Dazuo Yang; Shu Huang; et al. (Fish & Shellfish Immunology, 2025)

Singlet oxygen-driven selective guanine oxidation in Fenton-like system enables efficient removal of antibiotic resistance genes - Xiaoyu Liu; Bingkun Huang; Ying Li; Zelin Wu; Jing Zhang; Yanbiao Shi; Chuan-Shu He; Jianping Zou; Zhaokun Xiong; Bo Lai (Chemical Engineering Journal, 2025)

Alveolar surfactant-mimicking inhaled biomimetic nanovaccine with alveolar macrophage-targeting property potentiates anti-mpox immunity - Bin Li; Jiamei Wang; Judun Zheng; Wei Wang; Lingjie He; Yan Yan; Xinting Fu; Xingjie You; Man Gu; Han Duan; Yue Jia; Qin Gu; et al. (Chemical Engineering Journal, 2025)

Traditional Chinese Medicine, Ziyin-Mingmu Decoction, Regulates Cholesterol Metabolism, Oxidative Stress, Inflammation and Gut Microbiota in Age-related Macular Degeneration Models - Xing Li; Khalid S. Ibrahim; Michal R. Baran; Gabriel Mbuta Tchivelekete; Xinzhi Zhou; Yi Wu; James Reilly; Zhoujin Tan; Zhiming He; Xinhua Shu (Pharmaceutical Research, 2025)
Background Age-related macular degeneration (AMD) is the commonest cause of retinal disorders in the aged population. Ziyin-Mingmu decoction (ZD) has been widely used to treat AMD patients over thousands of years, however the underlying functional mechanisms of ZD are largely elusive. In this study, we aim to elucidate the therapeutic mechanisms of ZD in AMD models. Methods An in vivo AMD mouse model and an in vitro AMD model were established. Cholesterol level in mouse tissues was measured. Expression of antioxidant genes and proinflammatory cytokines in mouse tissues and in human retinal pigment epithelial (RPE) cells were detected using biochemical approaches. Gut microbiota community and functional pathways were analysed using bioinformatics approach. Compounds in ZD were identified using HPLC/MS. Results High fat diet (HFD)-fed mice had significantly higher levels of cholesterol in the retina, RPE, liver and serum, and markedly decreased expression of cholesterol metabolism-associated genes in those tissues, compared to mice fed with normal diet. Similarly, expression of antioxidant and inflammation genes was dysregulated in HFD-fed mouse tissues. ZD treatment reversed these HFD-induced pathological effects. HFD also altered the composition of cecum bacterial communities and associated metabolic pathways, which returned to control levels by ZD. In vitro assays showed that H 2 O 2 significantly increased oxidative stress and enhanced expression of proinflammatory cytokines. Co-treatment with ZD significantly counteracted these changes. HPLC/MS identified 105 compound in water extracted ZD and most are polyphenols. Conclusion Our data suggests that protection of ZD against AMD is possibly through mitigating cholesterol level, oxidative stress and inflammation, and modulating gut microbiota by polyphenols.

A nutritional strategy for improving sub-adult grass carp (Ctenopharyngodon idella) flesh flavor: The role of α-lipoic acid in regulating muscle nucleotide and fatty acid metabolism - Yang Zhang; Pei Wu; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2025)

Corrigendum to “Novel nutritional strategy: Dietary valine improves the health value and nutrient deposition in grass carp (Ctenopharyngodon idella)” [Aquaculture Volume 598, 15 March 2025, 742053] - Meng-Ling Cai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng (Aquaculture, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Elevated globally rock weathering carbon sinks driven by reduced snow cover - Lian Xiong; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Yue Li; Luhua Wu; Junhan Li; Chen Ran; Sirui Zhang; Jingjing Liao; Xiaodong Yuan; Chaochao Du; et al. (Science Bulletin, 2025)

Simultaneous ammonium recovery and organic removal from domestic wastewater in a stacked bipolar membrane electrodialysis reactor coupled with membrane contactor (BMED-MC) - Yueting Wu; Lulu Qin; Longjing Sun; Rui Shu; Dan Sun; Hua Li; Xue Xia (Journal of Environmental Chemical Engineering, 2025)

A spatial weight sampling method integrating the spatiotemporal pattern enhances the understanding of the occurrence mechanism of wildfires in the southwestern mountains of China - Wenlong Yang; Mingshan Wu; Lei Kong; Xiaojie Yin; Yanxia Wang; Chao Zhang; Leiguang Wang; Qingtai Shu; Jiangxia Ye; Shenghao Li; Zhichao Huang; Mengting Xue; et al. (Forest Ecology and Management, 2025)

Analysis of flavor quality differences between LZ coffee and coffee based on untargeted metabolomics - Yunyang Wu; Shu Luo; Yi Song; Liming He; Fang Li; Yuan Yang; Mengxiang Wei; Xia Luo (Food Bioscience, 2025)

Sex-specific association of co-exposures to melamine and phthalates in children with their early renal injury - Hui-Ju Tsai; Chia-Fang Wu; Sih-Syuan Li; Jia-Jen Chen; Chia-Jung Hsieh; Chu-Chih Chen; Shu-Li Wang; Mei-Lien Chen; Ming-Tsang Wu (Environmental Pollution, 2025)

High- and low-latitude forcings on East Asian summer monsoon variability over the past 36,000 years: A high-resolution record from Lake Chaohu, eastern China - Shuguang Lu; Li Wu; Chunmei Ma; Junwu Shu; Houchun Guan; Xiaoyu Han; Wenjing Luo; Ziyi Xu; Boshi Liu; Wentian Cai; Yang Zhang; Qiwen Wei (Science China Earth Sciences, 2025)

Seasonal Variation of Phyllosphere Microbial Communities Under Warming - Chaotang Lei; Shu‐Yi‐Dan Zhou; David T. Tissue; Roy Neilson; Zhiyang Lie; Ting Wu; Xujun Liu; Chushu Meng; Xu Li; Dong Zhu; Juxiu Liu (Global Change Biology, 2025)
The phyllosphere is a complex microbial ecosystem residing on plant leaves, hosting microbes that influence plant growth and fitness. The phyllosphere is sensitive to temperature and moisture, so understanding its response to climate warming and variable moisture associated with changes in seasons is crucial for predicting ecosystem function. We conducted a 12‐year warming experiment in a sub‐tropical forest by transplanting a natural ecosystem from higher to lower elevations. We sampled phyllosphere microbial communities across wet and dry seasons for three consecutive years (years 10–12) to assess potential adaptation strategies to warming. Phyllosphere microbial community structure and diversity varied seasonally, with higher bacterial richness in the dry season; however, warming reduced bacterial richness across seasons. Co‐occurrence networks revealed stronger microbial interactions in the dry season, which exhibited reduced connectivity under warming. Community assembly was largely stochastic, with warming enhancing species turnover and dispersal. Notably, plant probiotics, enriched in the wetter season with greater environmental disturbances, played a key role in adaptation to seasonal changes and warming. Seasonal shifts in microbial function were observed: wet‐season bacteria were enriched in carbohydrate and energy metabolism, while dry‐season bacteria showed elevated sulfur metabolism, reflecting adaptive metabolic strategies to environmental conditions. Our study enhances the understanding of the seasonal patterns of phyllosphere microbial communities and the impact of climate warming, offering new insights into plant–microbial adaptation strategies in response to climate change.

Adsorbent application and nitrogen deep placement reduced ammonia emissions in wheat fields - Yang Yang; Weizheng Shu; Ye Yang; Xiaoyu Ni; Yuejin Wu; Wenge Wu; Na Li (Soil and Tillage Research, 2025)

Discovery and configurations assignment of Ile/Leu-containing cyclic peptides with cytotoxic activity, Reniochpeptins A–D, from the marine sponge Reniochalina sp. - Shuai-Shuai Zhang; Zong-Mei Wu; Ying Wu; Ya-Jun Zeng; Yuan-Yuan Zhang; Xin-Li Lin; Si Zhang; Kai-Xuan Zhan; Hou-Wen Lin; Shu-Ping Wang (Phytochemistry, 2025)

Leveraging ionic information for machine learning-enhanced source identification in integrated wastewater treatment plant - Yaorong Shu; Fanming Kong; Xiaoyu Lin; Jinpeng Chen; Wenjun Liu; Zhilin Li; Juan Mao; Xiaohui Wu (Journal of Water Process Engineering, 2025)

Electroactive biofilms alter the EPS structure and metabolic pathways to sense potential and tetracycline - Fenglin Li; Lean Zhou; Shu Wang; Yongliang Wu; Tian Li; Shiquan Sun; Jinting Wang (Journal of Hazardous Materials, 2025)

Unveiling the journey of industrial selective catalytic reduction (SCR) catalysts: Understanding deactivation mechanisms and innovating regeneration techniques - Zian Liu; Qianwei Shu; Zhefei Li; Yang Liu; Shuya Rui; Binghui Wu; Zhiping Ye; Junhua Li (Journal of Cleaner Production, 2025)

Electric field-driven preparation of highly dispersed ENP membrane and its study on Cr(VI) removal from water - Yangshuo Sun; Guiyang Jiang; Yiming Zhou; Leilin Shu; Jiarui Li; Longcheng Liu; Junzhe Zhang; Xunrui Cheng; Yiyun Liu; Xiaoyan Xu; Zhi Zhu; Junshan Liu; et al. (Chemical Engineering Journal, 2025)

Synthesis of hollow HC-Ni0.96S@MXene/C nanobox as advanced anode for lithium-ion and sodium-ion battery - Song-Yi Liao; Jing Chen; Dao-Ren Deng; Cai-Yun Wu; Selina X. Yao; Yi Wang; Yu-Ming Ru; Xiao-Yan Li; Xu-Gang Shu; Yong-Gang Min (Chemical Engineering Journal, 2025)

Anwulignan alleviates IRI by the activation of Nrf2/HO-1 signaling pathway and inhibiting NLRP3-caspase-1-GSDMD-mediated pyroptosis in rats - Xin Wang; Shihui Wu; Yuxin Jiang; Zihao Yuan; Jian Liu; Shu Jing; Jiale Liu; Jinghui Sun; Chunmei Wang; Dan Wang; He Li (Tissue and Cell, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Uncovering soil heavy metal pollution hotspots and influencing mechanisms through machine learning and spatial analysis - Xiaoyong Song; Yao Sun; Huijuan Wang; Xinmiao Huang; Zilin Han; Yilan Shu; Jiaheng Wu; Zhenglin Zhang; Qicheng Zhong; Rongxi Li; Zhengqiu Fan (Environmental Pollution, 2025)

Identification and characterization of anthocyanins’ composition and regulatory genes involved in anthocyanins biosynthesis in water dropwort (Oenanthe javanica) - Kai Feng; Nan Sun; Ya-Qing Bian; Wu-Di Rui; Ya-Jie Yan; Zhi-Yuan Yang; Jia-Lu Liu; Zi-Qi Zhou; Shu-Ping Zhao; Peng Wu; Liang-Jun Li (Planta, 2025)

Pathogenic characterization and drug resistance of neonatal sepsis in China: a systematic review and meta-analysis - Ruixue Wu; Xiaoyu Cui; Rui Pan; Na Li; Ying Zhang; Jianbo Shu; Yang Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Screening of Spinal Muscular Atrophy Carriers and Prenatal Diagnosis in Pregnant Women in Yancheng, China - Huilin Sun; Jianli Zheng; Qing’e Zhang; Feifei Ying; Yadong Fu; Yongjuan Guan; Jing Wu; Yueyun Zhou; Jingjing Dong; Mengjun Xu; Fangfang Yang; Ning An; et al. (Biochemical Genetics, 2025)

Novel nutritional strategy: Dietary valine improves the health value and nutrient deposition in grass carp (Ctenopharyngodon idella) - Meng-Ling Cai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng (Aquaculture, 2025)

Probiotic potential of intestinal bacteria isolated from the digestive tract of hybrid snakehead (Channa argus♀ × Channa maculata♂) - Wen-Hao Wu; Yan-Xin Sun; Jia-Hao Zhang; Kun-Ming Huang; Xi-Chao Liu; Shu Tang; Wei Li; Biao Jiang; You-Lu Su (Aquaculture, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Effect of uniaxial stress on the thermal effect and kinetics during the re-ignition process of pre-oxidized bituminous coal - Mingqiu Wu; Haitao Li; Liang Wang; Chi-Min Shu; Xiaojun Shi; Yu Wang; Jie Li; Minggao Yu (Process Safety and Environmental Protection, 2025)

A Gln alteration influences leaf morphogenesis by mediating gibberellin levels in tobacco - Qi-Li Mi; Hong-Tao Lv; Fei-Fei Huang; Li Xu; Zi-Ying Huang; Wen-Wu Yang; Mei-Yun Zou; Hai-Tao Huang; Wan-Li Zeng; Jia-Yin Zhao; Qing-Xian Chen; Yong-En Si-Tu; et al. (Journal of Plant Physiology, 2025)

Effect of oral Mn-based nanozymes Mn3O4 NPs on morphological, antioxidation, mucosa, and fecal microbial community in mice colons - Baoyue Zhang; Lei Yang; Zhengkun Wu; Xianxiang Wang; Xiaoling Zhao; Wei Zhang; Danqin Li; Hualin Fu; Juchun Lin; Funeng Xu; Xiaoyang Ai; Gang Shu (Food and Chemical Toxicology, 2025)

Injectable melatonin carbon dot composite hydrogel enhances anti-inflammatory and tenogenic differentiation of tendon-derived stem cells for minimally invasive treatment of Achilles tendinopathy - Zheyu Yao; Zheyang Yuan; Qianglong Chen; Liwei Yao; Xiqian Zhang; Xiang Gao; Senyi Wu; Yiding Shao; Jiahui Feng; Xufeng Mao; Wenmiao Shu; Junxi Wu; et al. (Chemical Engineering Journal, 2025)

Structural characteization and anti-colorectal cancer activity of a fucogalactan purified from Ganoderma tsugae - Xin Zhang; Shuai Liu; Keyi Wu; Lili Shu; Yu Li; Lanzhou Li; Di Wang (Carbohydrate Polymers, 2025)

Spinal PTP1B Regulated NMDA Receptor-mediated Nociceptive Transmission and Peripheral Inflammation-induced Pain Sensitization - Shu-Jin Wu; Xin-Yi Lan; Yue Shi; Yan-Ni Liu; Xiao-Xi Zhang; Qi Zhang; Yu-Bo Gao; Juan Li; Xian Yang; Hu-Hu Bai (Molecular Neurobiology, 2025)

cascAGS: Comparative Analysis of SNP Calling Methods for Human Genome Data in the Absence of Gold Standard - Qianqian Song; Taobo Hu; Baosheng Liang; Shihai Li; Yang Li; Jinbo Wu; Shu Wang; Xiaohua Zhou (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Methamphetamine inhibits huntingtin-associated protein 1-mediated tyrosine receptor kinase B endocytosis resulting the neuroprotective dysfunction of brain-derived neurotrophic factor - Baoyu Shen; Zhenling Wu; Mengran Lv; Genmeng Yang; Yuanyuan Cao; Yuan Zhang; Junjie Shu; Wenjuan Dong; Zhenping Hou; Di Jing; Xinjie Zhang; Yuhan Hou; et al. (Toxicology, 2025)

Unintentional emissions of polychlorinated naphthalenes in China: Sources, composition, and historical trends - Ye Huang; Lin Huang; Ying Li; Nazupar Sidikjan; Yunshan Zhang; Yan Chen; Yangmin Chen; Ye Li; Wei Du; Long Chen; Yan Wu; Shanshan Zhang; et al. (Journal of Environmental Sciences, 2025)

Microorganism-mediated production of anthocyanins: Current progress and future prospects - Chi Shu; Shan Zhang; Siyu Wu; Shuting Liu; Jianing Xu; Jin Zhao; Bin Li (Food Research International, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

The role of cationic bridges in enhancing sulfamethoxazole adsorption onto montmorillonite - Qianhui Guan; Xiao Shu; Wensheng Wu; Yue Zhang; Chenhui Wang; Mingfu Li; Ni Liang; Quan Chen (Environmental Geochemistry and Health, 2025)

Fracture failure characteristics of shallow coral reef under wave dynamic loading - Tao Li; Jiajun Shu; Bingni Wu; Jingzhu Huang; Zhengding Deng (Marine Georesources & Geotechnology, 2025)

Inhibitory performance and mechanism analysis of modified fly-ash inhibitor on the coal spontaneous combustion: A combined study of laboratory experiments and molecular dynamic simulation - Mingqiu Wu; Haitao Li; Jiachen Wang; Liang Wang; Shanshan Li; Yu Wang; Minggao Yu; Jie Li; Chi-Min Shu (Process Safety and Environmental Protection, 2025)

Discovery of cycloheptapeptides phakefusins A−E from the marine sponge Phakellia fusca based on molecular networking - Ying Wu; Zhao-Ze Xu; Can Kong; Shuai-Shuai Zhang; Xin-Li Lin; Si Zhang; Li-Yun Liu; Fan Sun; Hou-Wen Lin; Shu-Ping Wang (Phytochemistry, 2025)

In situ preparation of carbon/zeolite composite materials derived from coal gasification fine slag for removing malachite green: Performance evaluation and mechanism insight - Xinzhang Shi; Longhua Xu; Jia Tian; Kaiqian Shu; Zhoujie Wang; Kai Xue; Houqin Wu; Donghui Wang; Guohuan Li (Journal of Water Process Engineering, 2025)

Effects of stir-frying on chemical profile, sensory quality and antioxidant activity of Chrysanthemi Flos: A metabolomics and sensory study - Yangfei Ding; Ranran Cheng; Yu Li; Dongliang Jiang; Hongsu Zhao; Xinfeng Wu; Yachun Shu; Tulin Lu; Chuanshan Jin; Deling Wu; Wei Zhang (Food Research International, 2025)

Preparation and characterization of novel natural pigment-indicating film: Application in kiwifruit freshness monitoring - Si Xia; Xiangjun Fang; Weijie Wu; Guannan Wang; Huizhi Chen; Zhiwen Hu; Li-Shu Wang; Ruilin Liu; Haiyan Gao (Food Chemistry, 2025)

Silk protein: A novel antifungal and edible coating for strawberry preservation - Yan Wang; Weijie Wu; Ruiling Liu; Ben Niu; Xiangjun Fang; Hangjun Chen; Mohamed A. Farag; Li-Shu Wang; Guannan Wang; Hailong Yang; Huizhi Chen; Haiyan Gao (Food Chemistry, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Prospective LCA towards achieving carbon neutrality goals: Framework application and challenges - Ya-Xi Fang; Pei-Ze Wu; Sha Chen; Yu Li; Shu-Fen Cui; Jin-Xing Zhu; Hai-Zhou Cao; Ke-Jun Jiang; Ling Zhong (Environmental Impact Assessment Review, 2025)

Silicon-based bimetallic nanozyme-enhanced immunochromatographic strips for highly sensitive simultaneous detection of multiple environmental pollutants - Wenlong Bai; Shuai Zheng; Zhigang Li; Xiaosong Wu; Chongwen Wang; Yong Liu; Long Zhang; Fanglin Liu; Shu Wang (Chemical Engineering Journal, 2025)

Design of Ni-based heterostructured catalyst with Ni3+ for enhanced bidirectional sulfur conversion - Yurui Wu; Wei Li; Hengzhi Liu; Yufang Chen; Manfang Chen; Xingqiao Wu; Yunfeng Peng; Wenlong Xia; Yuchao Du; Keyang Fu; Xiukang Yang; Xianyou Wang; et al. (Chemical Engineering Journal, 2025)

Multi-omics Analysis Reveals Key Gut Microbiota and Metabolites Closely Associated with Huntington’s Disease - Shu-Xia Qian; Yu-Feng Bao; Xiao-Yan Li; Yi Dong; Xiao-Ling Zhang; Zhi-Ying Wu (Molecular Neurobiology, 2025)

Metabolic engineering of Escherichia coli for upcycling of polyethylene terephthalate waste to vanillin - Yang Li; Xiao-Min Zhao; Si-Qi Chen; Zhao-Yuan Zhang; Qi-Sheng Fu; Shu-Min Chen; Sheng Chen; Jing Wu; Ke-Wei Xu; Ling-Qia Su; Zheng-Fei Yan (Science of The Total Environment, 2024)

Coseismic surface deformation and source mechanism of the 2023 Ms 6.2 Jishishan earthquake, northeastern Tibetan Plateau - Peng Chen; Siqi Shu; Zhonghai Wu; Tao Wang; Chengjun Feng; Jiamei Liu; Shuai Zhang; Haojie Wang; Kun Li (Journal of Structural Geology, 2024)

Determination of soil environmental criteria for high-risk trace metals in urban park soils using improved CLEA model - Zilin Han; Huijuan Wang; Xinmiao Huang; Xiaoyong Song; Yilan Shu; Jiaheng Wu; Jiaxun Sun; Rongxi Li; Zhengqiu Fan (Journal of Hazardous Materials, 2024)

The restoration of karst rocky desertification has enhanced the carbon sequestration capacity of the ecosystem in southern China - Chaochao Du; Xiaoyong Bai; Yangbing Li; Qiu Tan; Cuiwei Zhao; Guangjie Luo; Jinfeng Wang; Luhua Wu; Chaojun Li; Junhan Li; Yuanhuan Xie; Chen Ran; et al. (Global and Planetary Change, 2024)

Volatilomics of Cabernet Sauvignon grapes and sensory perception of wines are affected by canopy side in vineyards with different row orientations - Hao-Cheng Lu; Meng-Bo Tian; Ning Shi; Hui-Qing Li; Ming-Yu Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Andrea Schubert; Jun Wang (Food Chemistry, 2024)

Histidine is effective in promoting muscle growth and protein deposition: In vivo and in vitro experimental models of grass carp (Ctenopharyngodon idella) - Xin Zeng; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Ling Tang; Shu-Wei Li; Sheng-Yao Kuang; Lin Feng (Food Bioscience, 2024)

Zn2+-coordination-driven helical dodecapeptide assembly hydrogel - Di Wu; Shuzhen Cheng; Chao Wu; Li-Shu Wang; Hesham El-Seedi; Guanghua Zhao; Xianbing Xu; Ming Du (Food Bioscience, 2024)

Effects of flotation reagents with aniline aerofloat and ammonium dibutyl dithiophosphate on a constructed rapid infiltration system: Performance and microbial metabolic pathways - Yunnan Zhang; Zhexiang Cai; Ziyi Wu; Huayu Liang; Daoning Li; Shuo Fan; Shu Gao; Shenglong Chen; Yuxiang Lu; Chengyuan Su (Environmental Pollution, 2024)

Identification of the synonymous variant c.3141G > A in TNRC6B gene that altered RNA splicing by minigene assay - Feiyu Zhou; Hongping Zhong; Bo Wu; Yaqiong Cui; Jiaci Li; Xiaodong Jia; Changshun Yu; Dong Li; Jianbo Shu; Chunquan Cai (Molecular Biology Reports, 2024)

Novel MEI1 mutations cause chromosomal and DNA methylation abnormalities leading to embryonic arrest and implantation failure - Xiangli Wu; Yuqing Tian; Yiqi Yu; Xujun He; Xiaohua Tang; Shishi Li; Jing Shu; Xiaoyan Guo (Molecular Genetics and Genomics, 2024)

Identification and culture of functional salivary gland ductal epithelial cells - Han-Shu Zhang; You-Wei Zhao; Xin-Yi Tao; Xin Cong; Li-Ling Wu; Guang-Yan Yu; Yan Zhang (Histochemistry and Cell Biology, 2024)

C 21 steroidal glycosides from the root bark of Periploca sepium and their NO production inhibitory and cytotoxic activity - Zhi-Heng Shu; Miao Chen; Yao Li; Cai-Lian Fan; Wei-Wu Chen; Yao Xin-Sheng; Yi Dai (Natural Product Research, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

The screening of iron oxides for long-term transformation into vivianite to recover phosphorus from sewage - Danhui Liang; Jifei Chang; Yu Wu; Shu Wang; Xin Wang; Nanqi Ren; Nan Li (Water Research, 2024)

Mechanisms of evolution and pollution source identification in groundwater quality of the Fen River Basin driven by precipitation - Zhibin Li; Chengpeng Lu; Yong Zhang; Chengcheng Wu; Bo Liu; Longcang Shu (Science of The Total Environment, 2024)

Establishment of an immunoassay for detection of nonylphenols in surfactant oilfield chemicals based on computer-aided design - Jinyan Li; Yong Shu; Luming Jiang; Shanshan Song; Xinxin Xu; Xiaoling Wu; Hua Kuang; Chuanlai Xu; Lingling Guo (Science of The Total Environment, 2024)

Electrokinetic remediation of cadmium-contaminated soil using polarity reversal method: Optimization analysis and mechanism exploration - Zheng Wang; Tian Tang; Liuzhou Chen; Shu Wu; Xin Li; Yangsheng Liu (Journal of Environmental Management, 2024)

Photocorrosion suppression of copper sulfide via hybridization with amino-functionalized metal–organic framework for natural sunlight-driven photocatalysis - Zewei Liu; Cheng Tang; Zepeng Yu; Shu Li; Chengzhang Deng; Sijie Liu; Zhiqiang Wu; Rong Tan (Fuel, 2024)

Tough and temperature-resistant mask-based separator realized by K-β”-Al2O3 protective layer for stabilizing NaK liquid metal batteries - Yong Chen; Jie Xu; Qi Wu; Laiping Li; Peizhi Mou; Zhe Chen; Haoxiang Yu; Lei Yan; Jie Shu; Liyuan Zhang (Chemical Engineering Journal, 2024)

Discovery of ElABCG39: a key player in ingenol transmembrane efflux identified through genome-wide analysis of ABC transporters in Euphorbia lathyris L. - Guyin Lin; Pirui Li; Linwei Li; Ruyuan Wang; Wanli Zhao; Mei Tian; Junzhi Wu; Shu Xu; Yu Chen; Xu Feng (Plant Cell Reports, 2024)

The effects of online-training artificial neural network mechanism and multi-stage parametric modeling method on simulation-based design system for ship optimization - Lin Du; Qin Wu; Yuehui Shu; Guang-nian Li (Ocean Engineering, 2024)

The involvement of tumor necrosis factor receptor-associated factor 6 in regulating immune response by NF-κB at pre-molt stage of Chinese mitten crab (Eriocheir sinensis) - Jialin Li; Yuhan Ma; Zihao Wu; Jiaming Li; Fengchi Wang; Zhichao Yang; Yuting Xi; Dazuo Yang; Yusheng Jiang; Qilin Yi; Shu Huang (Fish & Shellfish Immunology, 2024)

Wave propagation characteristics of fluid-containing soil granular materials at different frequencies under multiple dissipation mechanisms: A case study on calcareous sand in the South China Sea - Tao Li; Jiajun Shu; Yue Li; Bingni Wu; Bo Liu; Zhengding Deng; Jingzhu Huang; Rubén Galindo (Computers and Geotechnics, 2024)

Multimodal enhancement of ferroptosis for synergistic cascade colorectal cancer therapy - Ziying Wu; Kun Chen; Weisheng Mo; Yue Wang; Xiewei Lin; Zhien Lan; Caijing Mo; Haocheng Wang; Xiaoying Li; Xingdi Fan; Hungchen Chen; Zhilin Shu; et al. (Chemical Engineering Journal, 2024)

Recent advances in micro/nano-robots for environmental pollutant removal: Mechanism, application, and prospect - Jia-yi Hou; Hong-tao Liu; Li-ting Huang; Shu-biao Wu; Zu-lin Zhang (Chemical Engineering Journal, 2024)

Bayesian inversion of HFC-134a emissions in southern China from a new AGAGE site: Results from an observing system simulation experiment - Juan Li; Jianxiong Sheng; Lei Zhu; Bo Yao; Jing Wu; Dongchuan Pu; Lei Shu; Song Liu; Xicheng Li; Yuyang Chen; Xiaoxing Zuo; Yali Li; et al. (Atmospheric Environment, 2024)

Thalamic Nucleus Reuniens Glutamatergic Neurons Mediate Colorectal Visceral Pain in Mice via 5-HT2B Receptors - Di Li; Han Du; Shu-Ting Qu; Jing-Lai Wu; Yong-Chang Li; Qi-Ya Xu; Xia Chen; Xiao-Xuan Dai; Ji-Tian Xu; Qian Wang; Guang-Yin Xu (Neuroscience Bulletin, 2024)
Irritable bowel syndrome (IBS) is a common functional bowel disorder characterized by abdominal pain and visceral hypersensitivity. Reducing visceral hypersensitivity is the key to effectively relieving abdominal pain in IBS. Increasing evidence has confirmed that the thalamic nucleus reuniens (Re) and 5-hydroxytryptamine (5-HT) neurotransmitter system play an important role in the development of colorectal visceral pain, whereas the exact mechanisms remain largely unclear. In this study, we found that high expression of the 5-HT 2B receptors in the Re glutamatergic neurons promoted colorectal visceral pain. Specifically, we found that neonatal maternal deprivation (NMD) mice exhibited visceral hyperalgesia and enhanced spontaneous synaptic transmission in the Re brain region. Colorectal distension (CRD) stimulation induced a large amount of c-Fos expression in the Re brain region of NMD mice, predominantly in glutamatergic neurons. Furthermore, optogenetic manipulation of glutamatergic neuronal activity in the Re altered colorectal visceral pain responses in CON and NMD mice. In addition, we demonstrated that 5-HT 2B receptor expression on the Re glutamatergic neurons was upregulated and ultimately promoted colorectal visceral pain in NMD mice. These findings suggest a critical role of the 5HT 2B receptors on the Re glutamatergic neurons in the regulation of colorectal visceral pain.

Semi-synthesis and in vitro anti-cancer effects evaluation of novel xanthohumol derivatives - Xiaolong Sun; Jie Chen; Di Huang; Feng Ding; Long Zhao; Hong-Mei Li; Xiang-Shu Wang; Yu-Xin Zhang; Cheng-Zhu Wu (Molecular Diversity, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Estimation of ammonia emissions from rice fields under different N inputs in China - Na Li; Xiaoyu Ni; Ye Yang; Yuejin Wu; Weizheng Shu; Wenge Wu; Yang Yang (Resources, Conservation and Recycling, 2024)

Nano- and microplastics drive the dynamic equilibrium of amoeba-associated bacteria and antibiotic resistance genes - Min Zhou; Lu Ma; Zihe Wang; Shicheng Li; Yijun Cai; Meicheng Li; Lin Zhang; Cheng Wang; Bo Wu; Qingyun Yan; Zhili He; Longfei Shu (Journal of Hazardous Materials, 2024)

A mixed domain deblending approach for simultaneous source data based on deep learning - Shengqiang Mu; Wenda Li; Tianqi Wu; Guoxu Shu; Shoudong Huo (Journal of Applied Geophysics, 2024)

Cellular damage and response mechanisms of Candida tropicalis SHC-03 induced by toxic byproducts in corn stover hydrolysate - Zhengyue Zhang; Lan Wu; Qian Li; Baichao Shu; Dang Li; Yulei Chen; Jiaye Tang; Siyi Long; Jie Liao; Yifan Zhao; Hanyu Wang; Menggen Ma (International Biodeterioration & Biodegradation, 2024)

Insights of kaolinite surface and salt ions on the formation of carbon dioxide hydrates in confined nanopore: A molecular dynamics simulation study - Shuanshi Fan; Shu Wu; Xuemei Lang; Yanhong Wang; Gang Li (Gas Science and Engineering, 2024)

Gypsum ridges as conduits for deep methane emission in an evaporite basin– Insights into the origin of atmospheric methane on Mars - Yiliang Li; Zikang Li; Xiaorong Qin; Binlong Ye; Ziyu Niu; Anouk Ehreiser; Wenhua Zhang; Yang Pan; Liping Qin; Rong Shu; Jianxi Zhu; Yigang Xu; et al. (Earth and Planetary Science Letters, 2024)

Enhancement of chlorine-resistant bacteria inactivation via coupling Magnéli phase Ti4O7-based electrochemical oxidation and chlorination - Sheng-Nan Li; Shu-Xian Zheng; Zi-Xuan Zheng; Yu Ling; Hai-Ming Wu; Hai Liu (Chemical Engineering Journal, 2024)

The joint impact of PM2.5, O3, and CO2 on the East Asian Summer Monsoon in 2013 and 2018 due to contrasting emission reduction - Danyang Ma; Tijian Wang; Hao Wu; Yawei Qu; Shu Li; Bingliang Zhuang; Mengmeng Li; Min Xie; Natalya Andreeva Kilifarska-Nedialkova (Atmospheric Environment, 2024)

Association of Asian dust storms and PM2.5 with clinical visits for respiratory diseases in children - Hui-Ju Wen; Shu-Li Wang; Chih-Da Wu; Mao-Chang Liang (Atmospheric Environment, 2024)

Three new isocoumarin analogues from an endolichenic fungus Aspergillus flavus CPCC 400810 - Ren-Zhong Wang; Bing-Jie Su; Yu-Chuan Chen; Tong-Mei Xiao; Bi-Ying Yan; Li-Yan Yu; Shu-Yi Si; De-Ling Wu; Ming-Hua Chen (Natural Product Research, 2024)

Anti-coronavirus and anti-pulmonary inflammation effects of iridoids, the common component from Chinese herbal medicines for the treatment of COVID-19 - Dan-Yu Huang; Yong-Xin Luo; Wen-De Zheng; Shu-Yu Wu; Pei-Qi Huang; Jing-Wei Jin; Pan-Pan Wu; Li-She Gan (Journal of Natural Medicines, 2024)

Increasing structure diversity of farnesylated chalcones by a fungal aromatic prenyltransferase - Ying Wu; Shiyunhua Qian; Xiang Zhou; Shu-Ming Li; Chun-Mao Yuan; Song Yang; Kang Zhou (Phytochemistry, 2024)

A promising food-grade protector for Retinyl acetate emulsions with fibrillated egg white - Xiaomeng Li; Mengyao Wu; Minquan Xia; Mohamed Salama; Haoyang Sun; Lixian Ding; Xi Huang; Dewei Shu; Zhaoxia Cai (Food Chemistry, 2024)

Exploring the novel benefits of leucine: Protecting nitrite-induced liver damage in sub-adult grass carp (Ctenopharyngodon idella) through regulating mitochondria quality control - Lu-Lu Zhen; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Integrative Analysis of the Age-Related Dysregulated Genes Reveals an Inflammation and Immunity-Associated Regulatory Network in Alzheimer’s Disease - Zhuoze Wu; Lei Dong; Zhixiao Tian; Chenhui Yu; Qingrong Shu; Wei Chen; Hao Li (Molecular Neurobiology, 2024)

Dispersive solid-phase extraction based on zirconium metal-organic framework coupled with gas chromatography-mass spectrometry for determining sugar phosphates in biological samples - Yuyan Hu; Boxue Wu; Ying-Shu Tang; Yi Wu; Li-Yan Liu (Analytica Chimica Acta, 2024)

YAP/TAZ-TEAD activity promotes the malignant transformation of cervical intraepithelial neoplasia through enhancing the characteristics and Warburg effect of cancer stem cells - Shu Li; Xing Li; Yong-bin Yang; Su-fang Wu (Apoptosis, 2024)
A number of studies have confirmed that Yes-associated protein (YAP)/transcriptional co-activator with PDZ-binding motif (TAZ)-transcriptional enhanced associate domain (TEAD) activity is the driver of cancer development. However, the role and mechanism of the YAP/TAZ-TEAD pathway in cervical intraepithelial neoplasia (CIN) remain to be clarified. Therefore, this study was designed to observe the effect of YAP/TAZ-TEAD activity on the development of CIN and provide new ideas for the diagnosis and treatment of CIN. Firstly, cervical tissues were collected from CIN patients in different stages [CIN grade 1 (CIN1) tissue, CIN grade 2/3 (CIN 2/3) and squamous cell carcinoma (SCC)] and healthy volunteers. Next, the expression levels of YAP, TAZ and TEAD in cervical tissues and cells were observed by immunohistochemistry, qRT-PCR and western blot. Besides, Z172 and Z183 cells were transfected with siRNA-YAP/TAZ (si-YAP/TAZ) and YAP/TAZ overexpression vector (YAP-5SA). Also, Z172 cells were co-transfected with YAP-5SA and si-TEAD2/4. Subsequently, the stemness characteristics, glycolysis level and malignant transformation of cells in each group were observed by sphere-formation assay, commercial kit, MTT, Transwell, scratch experiment, xenotransplantation and western blot.The expression of YAP, TAZ and TEAD increased significantly in cervical cancer tissue and cell line at the stage of CIN2/3 and SCC. When YAP/TAZ was knocked down, the stemness characteristics, glycolysis level and malignant transformation of cancer cells were notably inhibited; while activating YAP/TAZ exhibited a completely opposite result. In addition, activating YAP/TAZ and knocking down the TEAD expression at the same time significant weakened the effect of activated YAP/TAZ signal on precancerous cells and reduced inhibitory effect of knocking down TEAD alone. YAP/TAZ-TEAD signal activates the characteristics and Warburg effect of cancer stem cells, thereby promoting the malignant transformation of CIN.

Systemic glucocorticoids link to long-term microvascular injury in COVID-19 - Qian Yang; Cai Yun Xia; Ying Cai; Yan Fang Zhang; Dao Ting Li; Shu Qi Wu; Peng Hu (Angiogenesis, 2024)

Propagation characteristics of dynamic wave in fluid-containing granular materials at unified high and low frequency - Tao Li; Jiajun Shu; Yue Li; Bingni Wu; Rubén Galindo (Soil Dynamics and Earthquake Engineering, 2024)

Transformation of regional vegetation driven by climate change during the last deglacial–early Holocene at Chaohu Lake, eastern China: New pollen insights - Xiaoyu Han; Junwu Shu; Li Wu; Baohua Li; Shuguang Lu; Wei Chen; Jinglian Ge (Review of Palaeobotany and Palynology, 2024)

Recent progress and perspectives on coal dust sources, transport, hazards, and controls in underground mines - Yong Cao; Yang Xiao; Zhen-Ping Wang; Qing-Wei Li; Chi-Min Shu; Xing-Rui Jiang; Shi-Liang Wu (Process Safety and Environmental Protection, 2024)

Simulated gastrointestinal digestion of walnut protein yields anti-inflammatory peptides - Wei Xia; Yuan Gao; Xiangjun Fang; Long Jin; Ruiling Liu; Li-Shu Wang; Yangyong Deng; Junlong Gao; Hailong Yang; Weijie Wu; Haiyan Gao (Food Chemistry, 2024)

Shear performance of small-rib-height perfobond strip connector groups embedded in UHPC: Experimental investigations and design recommendations - Nianduo Wu; Shengwei Liao; Zezhou Pan; Zhuangcheng Fang; Shu Fang; Feng Liu; Lijuan Li; Zhe Xiong (Engineering Structures, 2024)

Spatial heterogeneity and temporal tendency of channeled snow avalanche activity retrieved from Landsat images in the maritime snow climate of the Parlung Tsangpo catchment, southeastern Tibet - Hong Wen; Xiyong Wu; Xiaoyan Shu; Dong Wang; Siyuan Zhao; Guiyu Zhou; Xiaoning Li (Cold Regions Science and Technology, 2024)

Multi-perspective interpretation for one-dimensional conventional neural network model to identify iron-bearing waste material - Chenglin Yan; Shu Liu; Zhixiu Zhu; Hong Min; Qingjian Zhang; Wenya Zhao; Piao Su; Yarui An; Chen Li; Xiaohong Wu (Journal of Environmental Chemical Engineering, 2024)

Polypeptide urea increases rice yield and nitrogen use efficiency through root growth improvement - Shuang Liao; Fei Deng; Wei Zhou; Li Wang; Wu Li; Hui Hu; Shi-lin Pu; Shu-xian Li; Yong Chen; You-feng Tao; Chi Zhang; Qiu-ping Li; et al. (Field Crops Research, 2024)

An efficient and mild fractionation of corn stover via 2-phenoxyethanol and silicotungstic acid biphasic pretreatment for biomass valorization - Linhai Jiang; Manman Yu; Weiwei Shu; Lu Yang; Wu Lan; Di Li; Zengyong Li; Chuanfu Liu (Chemical Engineering Journal, 2024)

3D Visualization of Whole Brain Vessels and Quantification of Vascular Pathology in a Chronic Hypoperfusion Model Causing White Matter Damage - Yang Wu; Jia Ke; Song Ye; Li-Li Shan; Shuai Xu; Shu-Fen Guo; Meng-Ting Li; Tian-Ci Qiao; Zheng-Yu Peng; Yi-Lin Wang; Ming-Yuan Liu; He Wang; et al. (Translational Stroke Research, 2024)

Reference Intervals of Serum Iodine Concentration in Chinese Pregnant Women - Yi Wu; Huan-huan Long; Su-juan Zhang; Min-Min Li; Chao-gang Chen; Cheng Wang; Zheng-yu Sheng; Yan-bin Ye; Shu-yu Zuo; Wen-jing Pan; Zhao-min Liu (Biological Trace Element Research, 2024)

Attributes of Specialized Households’ Resilience and Its Impact on Rural Industrial Advancement: A Case Study of National Musical Instrument Production Specialized Households in Lankao County, Henan, China - Nalin Wu; Yike Wei; Sizhe Fan; Li Li; Yufan Sun; Yan Zhang; Yan Shu (Chinese Geographical Science, 2024)

Formation of cation bridges and its promoting mechanism for sorption of sulfamethoxazole by montmorillonite - Peng Yi; Xiao Shu; Chenhui Wang; Mingfu Li; Yu Huang; Min Wu; Lijuan Zhang; Quan Chen (Chemosphere, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Allocate electric vehicles’ public charging stations with charging demand uncertainty - Ting Wu; Emily Fainman; Yasmina Maïzi; Jia Shu; Yongzhen Li (Transportation Research Part D: Transport and Environment, 2024)

Enhancing soil health and nutrient cycling through soil amendments: Improving the synergy of bacteria and fungi - Yanhong Ding; Xiaodong Gao; Duntao Shu; Kadambot H.M. Siddique; Xiaolin Song; Pute Wu; Changjian Li; Xining Zhao (Science of The Total Environment, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Identification of Marine Shellfish–Derived Bioactive Peptides by in Silico Analysis and in Vitro Inhibitory Activity on α-Glucosidase - Jili Wu; Li Yang; Tianyu Shu; Xuewu Zhang (Journal of Aquatic Food Product Technology, 2024)

The emerging role of zinc on alleviating inflammatory responses and enhancing immunity in grass carp (Ctenopharyngodon idella) - Xin Zeng; Zheng-Xing Song; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Ling Tang; Shu-Wei Li; Juan Yang; Lin Feng (Aquaculture, 2024)

Toxicological evaluation and concentration of airborne PM0.1 in high air pollution period in Guangzhou, China - Mo Yang; Qi-Zhen Wu; Yun-Ting Zhang; Ari Leskinen; Xin-Feng Wang; Mika Komppula; Henri Hakkarainen; Marjut Roponen; Nan-Xiang Jin; Wei-Hong Tan; Shu-Li Xu; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Data driven multi-objective design for low-carbon self-compacting concrete considering durability - Boyuan Cheng; Liu Mei; Wu-Jian Long; Qiling Luo; Jinrui Zhang; Chen Xiong; Yuqing Shu; Zhangjian Li; Song Gao (Journal of Cleaner Production, 2024)

Salinity controlling enhanced high-salinity pickle wastewater treatment coupling with high-value fatty acid production by Dunaliella salina - Hao Hu; Bang-Lei Wu; Dong Wei; Li Yu; Wei-Hua Li; Shu-Guang Zhu (Journal of Cleaner Production, 2024)

Structure-induced interfacial activation convoying the CO-relayed conversion of CO2 to dimethyl carbonate - Shu-Guo Han; Shenghua Zhou; Xiaofang Li; Jianqiang Zhao; Wen-Bo Wei; Lirong Zheng; Dong-Dong Ma; Xin-Tao Wu; Qi-Long Zhu (Chemical Engineering Journal, 2024)

Solid waste-derived solar desalination devices: Enhanced efficiency in water vapor generation and diffusion - Jiahui Yu; Chenxi Wang; Shu Liu; Shuo Yang; Xingmin Du; Shuai Liu; Changxiang Shao; Huijun Kong; Baolei Wang; Tao Wu; Chenwei Li (Chemical Engineering Journal, 2024)

Effect of different water contents on the softening characteristics of clay under intermittent cyclic dynamic loading - Tao Li; Jiajun Shu; Bingni Wu; Jingzhu Huang; Zhengding Deng (Bulletin of Engineering Geology and the Environment, 2024)

Melatonin Enhanced Microglia M2 Polarization in Rat Model of Neuro-inflammation Via Regulating ER Stress/PPARδ/SIRT1 Signaling Axis - Hung-Chuan Pan; Cheng-Ning Yang; Wen-Jane Lee; Jason Sheehan; Sheng-Mao Wu; Hong-Shiu Chen; Mao-Hsun Lin; Li-Wei Shen; Shu-Hua Lee; Chin-Chang Shen; Liang-Yi Pan; Shing‑Hwa Liu; et al. (Journal of Neuroimmune Pharmacology, 2024)

Mortality risk of people living with HIV under hypothetical intervention scenarios of PM2.5 and HIV severity: a prospective cohort study - Shujuan Yang; Chuanteng Feng; Teng Fei; Dan Wu; Liao Feng; Fengshun Yuan; Yao Fu; Hua Ma; Bin Yu; Li Liu; Yizhuo Li; Yiping Li; et al. (Science of The Total Environment, 2024)

Transition from non-adakitic rocks to adakitic rocks in the southern Lhasa subterrane: Implications for progressive crustal thickening and tectonic evolution during the Early Cenozoic - Haoyu Yan; Zhiqin Xu; Xiaoping Long; Jie Li; Chutian Shu; Longlong Gou; Bin Wu (Journal of Asian Earth Sciences, 2024)

High resolution osteoclast-targeted imaging-guided osteoporosis alleviation via persistent luminescence nanocomposite - Xiao Lin; Kewen Zhang; Yang Li; Fang Nan; Jun Li; Hui Zhang; Wei Deng; Weihang Ding; Kaixuan Li; Nur Jarhen; Yitong Zhou; Xiao Yu; et al. (Chemical Engineering Journal, 2024)

Storage, form, and influencing factors of karst inorganic carbon in a carbonate area in China - Chaochao Du; Xiaoyong Bai; Yangbing Li; Qiu Tan; Cuiwei Zhao; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Sirui Zhang; Lian Xiong; et al. (Science China Earth Sciences, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

Sustainable valorizing high-protein feather waste utilization through solid-state fermentation by keratinase-enhanced Streptomyces sp. SCUT-3 using a novel promoter - Wen-Jun Lu; Ming-Shu Zhang; De-Lin Lu; Zhi-Wei Li; Zhen-Dong Yang; Lei Wu; Jing-Tao Ni; Wei-Dong Chen; Jun-Jin Deng; Xiao-Chun Luo (Waste Management, 2024)

Elucidating drivers of severe wintertime fine particulate matter pollution episodes in the Yangtze River Delta region of eastern China - Lei Shu; Tijian Wang; Jane Liu; Zhixiong Chen; Hao Wu; Yawei Qu; Mengmeng Li; Min Xie (Science of The Total Environment, 2024)

α-Glucan derivatives as selective blockers of aldolase A: Computer-aided structure optimization and the effects on HCC - Qian-Han Xiao; Ze-Zhi Li; Li Ren; Shu-Yao Wang; Xiao-Qiang Li; Hong-Xin Bai; Rui-Zhi Qiao; Na Tang; Wen-Juan Liu; Jing-Mei Wang; Guang-Yuan Ma; Dian-Chao Dong; et al. (Carbohydrate Polymers, 2024)

Brown sugar as a carbon source can make agricultural organic waste compost enter the secondary thermophilic stage and promote compost decomposition - Peng Xu; Priyanka Tripathi; Sita Mishra; Luolin Shu; Xue Li; Shiwen Zhao; Sakshi Verma; Ranjeet Verma; Yongjun Wu; Zhenchao Yang (Environmental Monitoring and Assessment, 2024)

Anti-scour performance of fluidized solidified slurry in dynamic water for scour repair - Xiaoni Wu; Ruyu Li; Jian Shu; Jinjian Chen; Huili Wang; Haili Jiang; Xiao Wang (Ocean Engineering, 2024)

Investigation of bacterial diversity from hybrid water sources to multiple terminal sites on an isolated island in the south China sea - Xiao Chen; Xiao-Nan Wu; Jing-Chun Feng; Yi Wang; Shu-Jun Yang; Jie Kong; Ying-Li Zhou; Jun-Lin Hu; Ke Ding; Si Zhang (Journal of Cleaner Production, 2024)

Adverse effects of exposure to fine particles and ultrafine particles in the environment on different organs of organisms - Jianwei Zhang; Zhao Chen; Dan Shan; Yang Wu; Yue Zhao; Chen Li; Yue Shu; Xiaoyu Linghu; Baiqi Wang (Journal of Environmental Sciences, 2024)

Optimum pressure control with three controllable ejectors of a CO2 multi-ejector refrigeration system - Ligeng Li; Hua Tian; Kai Liu; Yibo Wu; Xuan Wang; Xingyu Liang; Gequn Shu (International Journal of Refrigeration, 2024)

Low intensity magnetic separation of vivianite induced by iron reduction on the surface layer of Fe(III)[Fe(0)] iron scrap - Yan Gao; Nanqi Ren; Shu Wang; Yu Wu; Xin Wang; Nan Li (Environmental Research, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Effects of initial temperature and moisture content on heat generation during degradation of municipal solid waste - Shi Shu; Jianyong Shi; Zuqiang Yao; Yuping Li; Xun Wu (Waste Management, 2023)

A new Trapa from the middle Miocene of Zhangpu, Fujian, southeastern China - Xie-Ting Wu; Zi-Xi Wang; Jun-Wu Shu; Su-Xin Yin; Li-Mi Mao; Gong-Le Shi (Palaeoworld, 2023)

Application of engineered heme enzymes based on myoglobin with high peroxidase activity for efficient degradation of various emerging pollutants - Guang-Rong Wu; Jia-Kun Xu; Li-Juan Sun; Ying-Fu Li; Shu-Qin Gao; Ying-Wu Lin (Journal of Environmental Chemical Engineering, 2023)

Vineyard soil heterogeneity and harvest date affect volatolomics and sensory attributes of Cabernet Sauvignon wines on a meso-terroir scale - Hao-Cheng Lu; Meng-Bo Tian; Xiao Han; Ning Shi; Hui-Qing Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Research International, 2023)

C4 leaf development and evolution - Chi-Fa Huang; Wen-Yu Liu; Chun-Ping Yu; Shu-Hsing Wu; Maurice S.B. Ku; Wen-Hsiung Li (Current Opinion in Plant Biology, 2023)

The Anterior Insula and its Projection to the Prelimbic Cortex are Involved in the Regulation of 5-HT-Induced Itch - Juan Yao; Xuan Li; Guang-Yan Wu; Bing Wu; Jun-Hui Long; Pu-Jun Wang; Shu-Lei Liu; Jie Gao; Jian-Feng Sui (Neuroscience Bulletin, 2023)
Itch is an unpleasant sensation that urges people and animals to scratch. Neuroimaging studies on itch have yielded extensive correlations with diverse cortical and subcortical regions, including the insular lobe. However, the role and functional specificity of the insular cortex (IC) and its subdivisions in itch mediation remains unclear. Here, we demonstrated by immunohistochemistry and fiber photometry tests, that neurons in both the anterior insular cortex (AIC) and the posterior insular cortex (PIC) are activated during acute itch processes. Pharmacogenetic experiments revealed that nonselective inhibition of global AIC neurons, or selective inhibition of the activity of glutaminergic neurons in the AIC, reduced the scratching behaviors induced by intradermal injection of 5-hydroxytryptamine (5-HT), but not those induced by compound 48/80. However, both nonselective inhibition of global PIC neurons and selective inhibition of glutaminergic neurons in the PIC failed to affect the itching-scratching behaviors induced by either 5-HT or compound 48/80. In addition, pharmacogenetic inhibition of AIC glutaminergic neurons effectively blocked itch-associated conditioned place aversion behavior, and inhibition of AIC glutaminergic neurons projecting to the prelimbic cortex significantly suppressed 5-HT-evoked scratching. These findings provide preliminary evidence that the AIC is involved, at least partially via aversive emotion mediation, in the regulation of 5-HT-, but not compound 48/80-induced itch.

Anticoagulants in adult extracorporeal membrane oxygenation: alternatives to standardized anticoagulation with unfractionated heparin - Shu Tang; Liqing Xu; Hui Li; Zhanshen Wu; Qiang Wen (European Journal of Clinical Pharmacology, 2023)

Modeling China's terrestrial ecosystem gross primary productivity with BEPS model: Parameter sensitivity analysis and model calibration - Xiuli Xing; Mousong Wu; Wenxin Zhang; Weimin Ju; Torbern Tagesson; Wei He; Songhan Wang; Jun Wang; Lu Hu; Shu Yuan; Tingting Zhu; Xiaorong Wang; et al. (Agricultural and Forest Meteorology, 2023)

A method of fast reading massive shot data of seismic acquisition based on two-level index - Xin-Jian Wei; Shu-Ping Li; Wu-Yang Yang; Xiang-Yang Zhang; Hai-Shan Li; Xin Xu (Applied Geophysics, 2023)

Socioeconomic status, lifestyle and risk of incident dementia: a prospective cohort study of 276730 participants - Ya-Nan Ou; Yan-Bo Zhang; Yu-Zhu Li; Shu-Yi Huang; Wei Zhang; Yue-Ting Deng; Bang-Sheng Wu; Lan Tan; Qiang Dong; An Pan; Ren-Jie Chen; Jian-Feng Feng; et al. (GeroScience, 2023)

In situ enrichment of sulphate-reducing microbial communities with different carbon sources stimulating the acid mine drainage sediments - Zhuo-hui Wu; Xiao-dan Yang; Li-ying Huang; Shi-lin Li; Fei-yun Xia; Yong-zhi Qiu; Xin-zhu Yi; Pu Jia; Bin Liao; Jie-Liang Liang; Wen-sheng Shu; Jin-tian Li (Science of The Total Environment, 2023)

Influence of the karst matrix hydraulic conductivity and specific yield on the estimation accuracy of karstic water storage variation - Yuxi Li; Longcang Shu; Peipeng Wu; Zhike Zou; Chengpeng Lu; Bo Liu; Shuyao Niu; Xiaoran Yin (Journal of Hydrology, 2023)

Progress in biological activities and biosynthesis of edible fungi terpenoids - Hai-Ying Chen; Jin-Yu Lei; Shu-Li Li; Li-Qiong Guo; Jun-Fang Lin; Guang-Hong Wu; Jun Lu; Zhi-Wei Ye (Critical Reviews in Food Science and Nutrition, 2023)

Emission of greenhouse gas from urban polluted river during different rainfall events: Typhoon and storm will promote stronger evasions - Guanghui Zhao; Dongqi Wang; Taihu Sun; Yan Ding; Shu Chen; Yizhe Li; Hechen Sun; Chenyang Wu; Zhongjie Yu; Zhenlou Chen (Journal of Hydrology, 2023)

Dietary threonine improves muscle nutritional value and muscle hardness associated with collagen synthesis in grass carp (Ctenopharyngodon idella) - Mei-Lan Wen; Pei Wu; Wei-Dan Jiang; Yang Liu; Cai-Mei Wu; Cheng-Bo Zhong; Shu-Wei Li; Ling Tang; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

Prevalence, distribution, accumulation, and risk of environmental corticosteroids and estrogens in biofilms from the Pearl River Delta - Jian Gong; Ke-Xin Yang; Can-Yuan Lin; Qiang Li; Chong Han; Wei Tao; Ying Huang; Wei-Quan Lin; Cui-Qin Wu; Shu-Han Zhang; De-Xin Wang (Environmental Pollution, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

An all-in-one enzymatic DNA network based on catalytic hairpin assembly for label-free and highly sensitive detection of APE1 - Shaoying Zhou; Xingrong Li; Xiaojia Shu; Xiaoying Cai; Haiping Wu; Shijia Ding; Yurong Yan (Analytica Chimica Acta, 2023)

Turbidite system controlled by fault interaction and linkage on a slope belt of rift basin: Zhanhua depression, Bohai Bay Basin, China - Rongheng Tian; Benzhong Xian; Qianran Wu; Qinglin Shu; Jianping Liu; Wenmiao Zhang; Zhen Wang; Qian Li; Naveed Ur Rahman; Yukun Gao; Jianwei Wang (Marine and Petroleum Geology, 2023)

Maternal di-(2-ethylhexyl) phthalate exposure elicits offspring IFN-λ upregulation: Insights from birth cohort, murine model, and in vitro mechanistic analysis - Fu-Chen Kuo; Mei-Lan Tsai; Shin-Ting Wu; Sih-Syuan Li; Chia-Fang Wu; Shu-Lin Wang; Michael W.Y. Chan; Jau-Ling Suen; Ming-Tsang Wu; Chih-Hsing Hung (Food and Chemical Toxicology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Association of long-term particulate matter exposure with all-cause mortality among patients with ovarian cancer: A prospective cohort - Yi-Zi Li; Shu-Hong Huang; Su Shi; Wen-Xiao Chen; Yi-Fan Wei; Bing-Jie Zou; Wei Yao; Lu Zhou; Fang-Hua Liu; Song Gao; Shi Yan; Xue Qin; et al. (Science of The Total Environment, 2023)

Suspended particulate matter-associated environmental corticosteroids in the Pearl River, China: Occurrence, distribution, and partitioning - Jian Gong; Yong-Shun Zhou; Can-Yuan Lin; Qiang Li; Chong Han; Ke-Xin Yang; Ying Huang; Wei-Quan Lin; Cui-Qin Wu; Shu-Han Zhang; Jia-Yu Huang (Science of The Total Environment, 2023)

Martynoside rescues 5-fluorouracil-impaired ribosome biogenesis by stabilizing RPL27A - Mengying Hong; Yushen Du; Dongdong Chen; Yuan Shi; Menglong Hu; Kejun Tang; Zhuping Hong; Xiangzhi Meng; Wan Xu; Gaoqi Wu; Yuanyuan Yao; Liubo Chen; et al. (Science Bulletin, 2023)

Paleoclimatic and anthropogenic impacts on the environment of Southwest China since 33 ka based on multiproxy analysis of karst depression deposits - Xing Tian; Xiaoyong Long; Shu’e Luo; Min Cao; Ji Li; Yuchuan Sun; Sibo Zeng; Ze Wu; Chuan Liu; Lidan Lei; Thomas J. Algeo; Yongjun Jiang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

High mechanical CuO@stainless steel mesh for continuous and durable separation of surfactant-stabilized viscous and light/heavy-mixed oily emulsions in liter-scale - Qing He; Meiling Guo; Juan Shu; Hua Hu; Hongwei Su; Guilong Yan; Zhenyu Li; Li Wang; Dong Xiang; Chunxia Zhao; Yuanpeng Wu; Wei Wang; et al. (Journal of Water Process Engineering, 2023)

Fertilizing-induced alterations of microbial functional profiles in soil nitrogen cycling closely associate with crop yield - Ruochen Li; Chengyao Ren; Likun Wu; Xinxin Zhang; Xinyi Mao; Zhen Fan; Weili Cui; Wu Zhang; Gehong Wei; Duntao Shu (Environmental Research, 2023)

Synthetic phylogenetically diverse communities promote denitrification and stability - Min Zhou; Xiaotong Guan; Ting Deng; Ruiwen Hu; Lu Qian; Xueqin Yang; Bo Wu; Juan Li; Qiang He; Longfei Shu; Qingyun Yan; Zhili He (Environmental Research, 2023)

Treated wastewater and weak removal mechanisms enhance nitrate pollution in metropolitan rivers - Guanghui Zhao; Taihu Sun; Dongqi Wang; Shu Chen; Yan Ding; Yilan Li; Guitao Shi; Hechen Sun; Shengnan Wu; Yizhe Li; Chenyang Wu; Yufang Li; et al. (Environmental Research, 2023)

3D-printed stretchable sensor based on double network PHI/PEDOT:PSS hydrogel annealed with cosolvent of H2O and DMSO - Xiu-Yan Cheng; Shu-Qiang Peng; Li-Xin Wu; Qing-fu Sun (Chemical Engineering Journal, 2023)

CORM-3 alleviates the intestinal injury in a rodent model of hemorrhage shock and resuscitation: roles of GFAP-positive glia - Li-Min Zhang; Yue Xin; Rong-Xin Song; Wei-Chao Zheng; Jin-Shu Hu; Jie-Xia Wang; Zhi-You Wu; Dong-Xue Zhang (Journal of Molecular Histology, 2023)

Pollination intensity and nutrient availability interactively shape directional selection on flower size in an orchid herb - Yun Wu; Xuyu Duan; Bo Shu; Qingjun Li (Evolutionary Ecology, 2023)

Drought adaptation of Bauhinia faberi var. Microphylla seedlings with dual inoculation of arbuscular mycorrhizal fungi - Xia Li; Wan-ze Zhu; Wen-wu Wang; Sheng-lan Ma; Zhe-liang Sheng; Shu-miao Shu (Journal of Mountain Science, 2023)

Dynamic Inversion Model of the Mooring Force on a Floating Bollard of a Sea Lock - Linjian Wu; Zhouyu Xiang; Dan Shu; Mingwei Liu; Jia Yang; Minglong Li (Journal of Marine Science and Engineering, 2023)
Sea locks that connect inland canals and rivers to the open sea are crucial links that ensure the efficient navigation of ships. Floating bollards (FBs) are significant components of sea locks, and they are affected by factors such as large ships, speed of entry, and irregular mooring lines coupled with corrosion by chloride salts from seawater intrusion from the environment. These factors aggravate damage to metal structures, which seriously threatens the safety of FBs. Overloading of FBs by mooring forces caused by the illegal use of FBs for the braking of large ships that enter locks at excessive speed is the main cause of structural damage and overload failure for FBs. Controlling the dynamic mooring force acting on the FB is an important prerequisite to ensure the safe passage of a ship through a lock. It is impossible to perform real-time monitoring of the magnitude and direction of the mooring force on an FB by installing load-measuring equipment on the mooring line. Therefore, in this study, the structure of an FB in a sea lock project was taken as an example, and the mathematical relationships between the strain in the load-sensitive area of the FB and the mooring force and the mooring angle were quantified. A dynamic inversion model of the ship mooring force on an FB was proposed. This model used real-time feedback from the strain signal in the load-sensitive region of the FB structure to obtain information about the mooring force. The accuracy of the model was verified by conducting tests with a physical model of the topside structure of the FB and comparing the predicted results with the test data. The research results can lay a theoretical foundation for real-time monitoring of the structural response of an FB under the action of mooring forces and promote the development of intelligent methods for the operation and maintenance of a sea lock, which have important scientific significance and engineering value.

Selenium/sulfur-modified montmorillonite materials mitigate mercury pollution in farmland - Shu Ran; Tianrong He; Shengpeng Li; Deliang Yin; Pan Wu; Yiyuan Xu; Jiating Zhao (Environmental Pollution, 2023)

Dietary zearalenone alters gill epithelial morphology and subsequent risk of infection: Insights from a freshwater grass carp (Ctenopharyngodon idella) model - Hong-Yun Zhang; Ya-Li Wang; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Hai-Feng Mi; Sheng-Yao Kuang; Ling Tang; Shu-wei Li; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Ultrasensitive and simultaneous monitoring of multiple small-molecule pollutants on an immunochromatographic strip with multilayered film-like fluorescent tags - Wenqi Wang; Qing Yu; Shuai Zheng; Jiaxuan Li; Ting Wu; Shu Wang; Chongwen Wang; Bing Gu (Science of The Total Environment, 2023)

A rapid onset of ocean acidification associated with the end-Permian mass extinction - Rucao Li; Nanping Wu; Shu-Zhong Shen; Xiao-Lei Wang; Huayong Chen; Thomas J. Algeo; Hua Zhang; Feifei Zhang (Global and Planetary Change, 2023)

Non-thermal effects of microwave irradiation alleviates postharvest chilling injury of peach fruit by retarding phenolic accumulation and enhancing membrane stability - Ke Wang; Ge Zhu; Ya-li Li; Shu-qi Chen; Arif Rashid; Xiao-tong Wang; Xin-yu Wu (Food Chemistry, 2023)

Temporal decline of genetic differentiation among populations of western flower thrips across an invaded range - Li-Na Sun; Li-Jun Cao; Jin-Cui Chen; Li-Jun Ma; Gui-Fen Zhang; San-An Wu; Ary Anthony Hoffmann; Shu-Jun Wei (Biological Invasions, 2023)

Sensory evaluation, chemical structures, and threshold concentrations of bitter-tasting compounds in common foodstuffs derived from plants and maillard reaction: A review - He Li; Li-Feng Li; Zhi-Jun Zhang; Chun-Jian Wu; Shu-Juan Yu (Critical Reviews in Food Science and Nutrition, 2023)

SIPN South: six years of coordinated seasonal Antarctic sea ice predictions - François Massonnet; Sandra Barreira; Antoine Barthélemy; Roberto Bilbao; Edward Blanchard-Wrigglesworth; Ed Blockley; David H. Bromwich; Mitchell Bushuk; Xiaoran Dong; Helge F. Goessling; Will Hobbs; Doroteaciro Iovino; et al. (Frontiers in Marine Science, 2023)
Antarctic sea ice prediction has garnered increasing attention in recent years, particularly in the context of the recent record lows of February 2022 and 2023. As Antarctica becomes a climate change hotspot, as polar tourism booms, and as scientific expeditions continue to explore this remote continent, the capacity to anticipate sea ice conditions weeks to months in advance is in increasing demand. Spurred by recent studies that uncovered physical mechanisms of Antarctic sea ice predictability and by the intriguing large variations of the observed sea ice extent in recent years, the Sea Ice Prediction Network South (SIPN South) project was initiated in 2017, building upon the Arctic Sea Ice Prediction Network. The SIPN South project annually coordinates spring-to-summer predictions of Antarctic sea ice conditions, to allow robust evaluation and intercomparison, and to guide future development in polar prediction systems. In this paper, we present and discuss the initial SIPN South results collected over six summer seasons (December-February 2017-2018 to 2022-2023). We use data from 22 unique contributors spanning five continents that have together delivered more than 3000 individual forecasts of sea ice area and concentration. The SIPN South median forecast of the circumpolar sea ice area captures the sign of the recent negative anomalies, and the verifying observations are systematically included in the 10-90% range of the forecast distribution. These statements also hold at the regional level except in the Ross Sea where the systematic biases and the ensemble spread are the largest. A notable finding is that the group forecast, constructed by aggregating the data provided by each contributor, outperforms most of the individual forecasts, both at the circumpolar and regional levels. This indicates the value of combining predictions to average out model-specific errors. Finally, we find that dynamical model predictions (i.e., based on process-based general circulation models) generally perform worse than statistical model predictions (i.e., data-driven empirical models including machine learning) in representing the regional variability of sea ice concentration in summer. SIPN South is a collaborative community project that is hosted on a shared public repository. The forecast and verification data used in SIPN South are publicly available in near-real time for further use by the polar research community, and eventually, policymakers.

Weak environmental adaptation of rare phylotypes sustaining soil multi-element cycles in response to decades-long fertilization - Weili Cui; Ruochen Li; Zhen Fan; Likun Wu; Xining Zhao; Gehong Wei; Duntao Shu (Science of The Total Environment, 2023)

5-epi-ent-Kaurane diterpenoids from the aerial parts of Isodon eriocalyx and their anti-atherosclerotic potential - Long Mu; Tian Li; Peng-Lin Wu; Ling-Qiao Cai; Shu-Ying Li; Zi-Yuan Wang; Yuan-Yuan Liu; Jie Wang; Dong Yan; Zheng-Yun Rao; Chao-Jun Wang; Jian Zhang; et al. (Phytochemistry, 2023)

UiO-66-derived Ce/Ni-ZrO2 nano-catalysts with a large nickel surface area for the highly efficient CO2 methanation under high GHSVs - Jiahui Yu; Shuai Liu; Shu Liu; Peng Jiang; Edward Lester; Chenwei Li; Meichun Ding; Changxiang Shao; Kaiqi Shi; Tao Wu (Fuel, 2023)

Screening of host gut-derived probiotics and effects of feeding probiotics on growth, immunity, and antioxidant enzyme activity of hybrid grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂) - Yating Zhu; Wen Li; Mingqing Zhang; Zhongxuan Zhong; Zhiqian Zhou; Jiayi Han; Cuiping Zhang; Jinlin Yang; Yuxin Wu; Hu Shu (Fish & Shellfish Immunology, 2023)

The contribution of wetland plant litter to soil carbon pool: Decomposition rates and priming effects - Yan Ding; Dongqi Wang; Guanghui Zhao; Shu Chen; Taihu Sun; Hechen Sun; Chenyang Wu; Yizhe Li; Zhongjie Yu; Yu Li; Zhenlou Chen (Environmental Research, 2023)

An image-based soil type classification method considering the impact of image acquisition distance factor - Dejiang Wang; Yuning Si; Zhan Shu; Ao Wu; Yajun Wu; Yifan Li (Journal of Soils and Sediments, 2023)

Elevated Interleukin-37 Associated with Dengue Viral Load in Patients with Dengue Fever - Jun-Ai Zhang; Jia-Jun Wang; Wen-Ting Zhang; Li Zhang; Bi-Ying Zheng; Gan-Bin Liu; Jing Liang; Yuan-Bin Lu; Xian-Jin Wu; Shu-Ying Yao; Guo-Ying Chen; Yun-Qi Xie; et al. (Current Microbiology, 2023)
Dengue remains a public health issue worldwide. Similar to chronic infectious diseases, stimulation of cytokine production is not enough to drive immune effector cells for effective virus clearance. One possible mechanism is the virus induces a large number of negative stimulatory cytokines inhibiting immune response. Interleukin 37 (IL-37) plays a crucial regulatory role in infection and immunity, inhibits innate and adaptive immunity as an anti-inflammatory cytokine by inhibiting proinflammatory mediators and pathways. To date, there are few studies reporting correlations between dengue fever (DF) and IL-37. In this study we found that the serum IL-37b and IL-37b-producing monocytes in patients were significantly increased in DF patients. A majority of the IL-37b produced by DF patients was produced by monocytes, not lymphocytes. Increased levels of IL-6, IL-10, and IFN-α were also found in DF patients. However, we failed to detect IL-1β, IL-17A and TNF-α in plasma, because of off-target. In our study, there was no relation between IL-6, IL-10, and IFN-α expressions and IL-37b in serum ( P > 0.05). The IL-37b-producing monocytes were negatively correlated with the level of IFN-α in serum and platelet count, and positively correlated with lymphocytes percentage ( P < 0.05, respectively). Additionally, serum DENV nonstructural protein 1 levels were positively correlated with monocytes percentages ( P < 0.05). Our data represents findings for IL-37b expression and its potential mechanisms in DF patients’ immune response.

Phytic acid is a new substitutable plant-derived antifungal agent for the seedling blight of Pinus sylvestris var. mongolica caused by Fusarium oxysporum - Na Li; Yu-Xuan Wu; Yun-Di Zhang; Shu-Ren Wang; Guo-Cai Zhang; Jing Yang (Pesticide Biochemistry and Physiology, 2023)

Ganoderma lucidum extract promotes tumor cell pyroptosis and inhibits metastasis in breast cancer - Chunlian Zhong; Yumei Li; Wulin Li; Shu lian; Ye Li; Changhui Wu; Kun Zhang; Guiyu Zhou; Weiyu Wang; Huo Xu; Mingqing Huang; Vladimir Katanaev; et al. (Food and Chemical Toxicology, 2023)

Severe shoot topping slows down berry sugar accumulation rate, alters the vine growth and photosynthetic capacity, and influences the flavoromics of Cabernet Sauvignon grapes in a semi-arid region - Hao-Cheng Lu; Meng-Bo Tian; Ning Shi; Xiao Han; Hui-Qing Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (European Journal of Agronomy, 2023)

Chemical constituents from the aerial parts of Sambucus adnata Wall. and their chemotaxonomic significance - Zheng-Bo Wu; Mei-Mei Zheng; Shu-Ran Qin; Jiang-Li Huang; Dashan Li; Wen-Jing Wang (Biochemical Systematics and Ecology, 2023)

Molecular Hydrogen: an Emerging Therapeutic Medical Gas for Brain Disorders - Chongyun Wu; Peibin Zou; Shu Feng; Ling Zhu; Fanghui Li; Timon Cheng-Yi Liu; Rui Duan; Luodan Yang (Molecular Neurobiology, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

Anisotropic creep behavior of soft-hard interbedded rock masses based on 3D printing and digital imaging correlation technology - Yun Tian; Fa-quan Wu; Hong-ming Tian; Zhe Li; Xiao-yun Shu; Lin-kai He; Man Huang; Wei-zhong Chen (Journal of Mountain Science, 2023)

Evaluation of negative effect of Naphthenic acids (NAs) on physiological metabolism and polycyclic aromatic hydrocarbons adsorption of Phragmites australis - Hui Jia; Guang-xi Zhang; Yi-fan Wu; Wei-wei Dai; Quan-bin Xu; Shu Gan; Xiu-yun Ju; Zhao-zhong Feng; Rong-peng Li; Bo Yuan (Chemosphere, 2023)

Sources, chemical components, and toxicological responses of size segregated urban air PM samples in high air pollution season in Guangzhou, China - Mo Yang; Hui-Xian Zeng; Xin-Feng Wang; Henri Hakkarainen; Ari Leskinen; Mika Komppula; Marjut Roponen; Qi-Zhen Wu; Shu-Li Xu; Li-Zi Lin; Ru-Qing Liu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

Manipulating the severe shoot topping delays the harvest date and modifies the flavor composition of Cabernet Sauvignon wines in a semi-arid climate - Hao-Cheng Lu; Li Hu; Yao Liu; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Chemistry, 2023)

Volatomics of ‘Cabernet Sauvignon’ grapes and wines under the fan training system revealed the nexus of microclimate and volatile compounds - Meng-Bo Tian; Yao Liu; Hao-Cheng Lu; Li Hu; Yu Wang; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Chemistry, 2023)

Analysis of PAT1 subfamily members in the GRAS family of upland cotton and functional characterization of GhSCL13-2A in Verticillium dahliae resistance - Chen Chen; Li-Li Lu; Shu-Ya Ma; Yan-Peng Zhao; Na Wu; Wen-Jie Li; Li Ma; Xian-Hui Kong; Zong-Ming Xie; Yu-Xia Hou (Plant Cell Reports, 2023)

Evaluation of Fe3O4-MnO2@RGO magnetic nanocomposite as an effective persulfate activator and metal adsorbent in aqueous solution - Mang Lu; Xue-jiao Wu; Chu-xing Wan; Qiu-ping Gong; Jia-xin Li; Shuang-shuang Liao; Yu-an Wang; Shu-hao Yuan (Environmental Science and Pollution Research, 2023)

Vitamin D serves as a modulator of immune organs in grass carp (Ctenopharyngodon idella) infected with Aeromonas hydrophila - Yao Zhang; Chao-Nan Li; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Enhancements in flavor substances, mouthfeel characteristics and collagen synthesis in the muscle of sub-adult grass carp (Ctenopharyngodon Idella): Application of a dietary lysine nutrition strategy - Yan-Jie Tang; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

Isolation and evaluation of antioxidants from Arisaema heterophyllum tubers - Na Sun; Huanhuan Yang; Miao Zhou; Yanyan Hou; Xinru Wu; Wenqian Li; Yifang Zhang; Jinge Sun; Xin Xiong; Jihong Huang; Penghua Shu (Phytochemistry Letters, 2023)

Hydrodeoxygenation of lignin-derived phenolic compounds over Ru/TiO2 catalyst: Effect of TiO2 morphology - Zhuojie Zhong; Junxuan Li; Minyin Jian; Riyang Shu; Zhipeng Tian; Chao Wang; Ying Chen; Ning Shi; Yanxue Wu (Fuel, 2023)

Associations between maternal phthalate exposure and neonatal neurobehaviors: The Taiwan maternal and infant cohort study (TMICS) - Hsing-Kang Chen; Shu-Li Wang; Yu-Hsun Chang; Chien-Wen Sun; Ming-Tsang Wu; Mei-Lien Chen; Yu-Jie Lin; Chia-Jung Hsieh (Environmental Pollution, 2023)

Encapsulating selenium into mesoporous carbon for high-performance aqueous Cu-Se battery - Zhouxiang Wu; Xia Lin; Junwei Zhang; Xiquan Chu; Jiaxi Xu; Jing Li; Yiwen Liu; Haoxiang Yu; Lei Yan; Liyuan Zhang; Jie Shu (Chemical Engineering Journal, 2023)

Novel Sustainable Adsorbents Prepared by Banana/Pomegranate Peels via EDTA Grafting for Effective Removal of Cd(II), Co(II), Mn(II), and Ni(II) from Sewage System - Yun Wang; Fanghui Wang; Lin Shu; Peng Wu; Zhenjing Li; Jianfeng Gao; Huanhuan Liu (Water, Air, & Soil Pollution, 2023)

miR-34b-3p Inhibition of eIF4E Causes Post-stroke Depression in Adult Mice - Xiao Ke; Manfei Deng; Zhuoze Wu; Hongyan Yu; Dian Yu; Hao Li; Youming Lu; Kai Shu; Lei Pei (Neuroscience Bulletin, 2023)

Antibiotics degradation by advanced oxidation process (AOPs): Recent advances in ecotoxicity and antibiotic-resistance genes induction of degradation products - Shuo Li; Yanan Wu; Heshan Zheng; Hongbin Li; Yongjie Zheng; Jun Nan; Jun Ma; Dillirani Nagarajan; Jo-Shu Chang (Chemosphere, 2023)

The beneficial effects of exogenous protease K originated from Parengyodontium album on growth performance of grass carp (Ctenopharyngodon idella) in relation to the enhanced intestinal digestion and absorption capacities - Ling Feng; Lin Feng; Wei-Dan Jiang; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou; Pei Wu (Aquaculture, 2023)

Impaired intestinal physical barrier of on-growing grass carp by deficient iron under Aeromonas hydrophila infection - Yan-Lin Guo; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Shu-wei Li; Ling Tang; Lu Zhang; Haifeng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

PRMT6 inhibits K63-linked ubiquitination and promotes the degradation of IRF3 in the antiviral innate immunity of black carp Mylopharyngodon piceus - Can Yang; Shisi Yang; Yujia Miao; Juanjuan Shu; Yuqing Peng; Jun Li; Hui Wu; Jun Zou; Hao Feng (Aquaculture, 2023)

DNA methylation reprogramming provides insights into light-induced anthocyanin biosynthesis in red pear - Hai-Nan Liu; Qun Shu; Kui Lin-Wang; Richard V. Espley; Andrew C. Allan; Mao-Song Pei; Xiao-Long Li; Jun Su; Jun Wu (Plant Science, 2023)

Insights into the influence on 2,4,6-trichlorophenol microbial reductive dechlorination process by exposure to microplastics - Jia-Qi Yang; Zhi-Ling Li; Bin Wu; Ya-Ru Jin; Di Cao; Jun Nan; Xue-Qi Chen; Wen-Zong Liu; Shu-Hong Gao; Ai-Jie Wang (Journal of Hazardous Materials, 2023)

Rare disperse elements in epithermal deposit: Insights from LA–ICP–MS study of sphalerite at Dalingkou, South China - Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Guo-Guang Wang; Jun-Ying Ding; Shu-Wu Chu; Wen-Sheng Li; Wen-Qing Huang; Ren-Zhi Zhu; Zhe Chi (Journal of Geochemical Exploration, 2023)

Effects of furanic compounds from biomass pyrolysis on ketonization reaction: The role of oxygenated side groups - Wenran Gao; Yiling Wan; Shanhui Zhao; Muhammad Asif Akhtar; Kuan Ding; Bin Li; Yinlong Wu; Shoujun Zhang; Shu Zhang (Fuel, 2023)

Dietary cinnamaldehyde improves muscle protein content by promoting muscle fiber growth via PTP1B/IGF1/PI3K/AKTs-TOR/FOXO3a signaling pathway in grass carp (Ctenopharyngodon idella) - Yang Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Yan Peng; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

Molecular engineering of blue diphenylsulfone-based emitter with aggregation-enhanced emission and thermally activated delayed fluorescence characteristics: impairing intermolecular electron-exchange interactions using steric hindrance - Jinnan Huo; Shu Xiao; Yuanyuan Wu; Mengxing Li; Hongbo Tong; Heping Shi; Dongge Ma; Ben Zhong Tang (Chemical Engineering Journal, 2023)

Corrigendum to “CD44-targeted hyaluronic acid-curcumin prodrug protects renal tubular epithelial cell survival from oxidative stress damage” [Carbohydrate Polymers 193 (2018) 268–280] - Jing-Bo Hu; Shu-Juan Li; Xu-Qi Kang; Jing Qi; Jia-Hui Wu; Xiao-Juan Wang; Xiao-Ling Xu; Xiao-Ying Ying; Sai-Ping Jiang; Jian You; Yong-Zhong Du (Carbohydrate Polymers, 2023)

Antibiotic sulfadiazine degradation by persulfate oxidation: Intermediates dependence of ecotoxicity and the induction of antibiotic resistance genes - Heshan Zheng; Yunfei Zhang; Shuo Li; Xiaochi Feng; Qinglian Wu; Yoong Kit Leong; Jo-Shu Chang (Bioresource Technology, 2023)

The prenatal weekly temperature exposure and neonatal congenital heart disease: a large population-based observational study in China - Weize Xu; Die Li; Zehua Shao; Yanqin You; Feixia Pan; Hongliang Lou; Jing Li; Yueqin Jin; Ting Wu; Lulu Pan; Jing An; Junqiu Xu; et al. (Environmental Science and Pollution Research, 2022)

Study on the Relationship Between Diet, Physical Health and Gut Microflora of Chinese College Students - Xiafen Hu; Jiaqi Guo; Jiadun Wang; Wanxin Liu; Xiaochen Xiang; Siyang Chen; Xinquan Li; Jinhan Tang; Wei Zhang; Hui Chen; Rong Shu; Qingming Wu; et al. (Current Microbiology, 2022)

7,8-Dihydroxyflavone attenuates the virulence of Staphylococcus aureus by inhibiting alpha-hemolysin - Nan Bian; Xiangqian Chen; Xinran Ren; Zishu Yu; Mengli Jin; Xiaoyu Chen; Chang Liu; Yanhe Luan; Lin Wei; Ying Chen; Wu Song; Yicheng Zhao; et al. (World Journal of Microbiology and Biotechnology, 2022)

The role of ancestral seascape discontinuity and geographical distance in structuring rockfish populations in the Pacific Northwest - Cheng-He Sun; Rodolphe Elie Gozlan; Ting Wu; Dan Xue; Ye-Ling Lao; Jian-Feng Yu; Xiao-Shu Zeng; Sha Li; Emilie A. Hardouin; Demetra Andreou; Qun Zhang (Frontiers in Marine Science, 2022)
Despite the apparent absence of physical barriers in the ocean to prevent dispersal, recent studies have highlighted the importance of biological, geographical, physical, and historical barriers in the genetic structuring of marine species populations. This representation is essential for the sustainable exploitation of natural marine resources and for the setup of efficient protected area networks for the conservation of marine species. In this study, we used extensive sampling of Sebastiscus marmoratus , a commercially important inshore rockfish with high site fidelity, to characterize their population genetic structure along the China–Japan coast and to determine the effect of past geological and current biological–physical barriers on the current genetic footprint. A 461-bp fragment of the mtDNA hypervariable portion control region was sequenced for 675 individuals from 15 geographical locations. A total of 292 haplotypes were identified. The population of S. marmoratus showed high haplotype and nucleotide diversity. Pairwise fixation index ( F ST ) and analysis of molecular variance (AMOVA) revealed significant genetic differentiation among populations. The Bayesian skyline plots and neutrality statistics showed a sudden expansion of the S. marmoratus population around the Pleistocene. The Beibu Gulf group had the lowest mean number of pairwise differences, the lowest significant genetic differentiation, and the lowest haplotype and nucleotide diversity, and should be prioritized for protection in the future. Ocean currents, seascape discontinuity, geographical distance, and ecological characteristics may play an important role in shaping the contemporary phylogeographical patterns and population structures of S. marmoratus .

A data-driven interpretable ensemble framework based on tree models for forecasting the occurrence of COVID-19 in the USA - Hu-Li Zheng; Shu-Yi An; Bao-Jun Qiao; Peng Guan; De-Sheng Huang; Wei Wu (Environmental Science and Pollution Research, 2022)

Elder people can be more susceptible to the association between short-term ambient air pollution and sleep disorder outpatient visits: a time-series study - Yu-Meng Zhou; Shu-Jie An; Yi Cao; Chen Xu; Xiao-Ling Liu; Chun-Yan Yao; Xiang Li; Na Wu; Cheng-Ying Li; Long Wu; Ya-Fei Li; Ai-Ling Ji; et al. (Environmental Science and Pollution Research, 2022)

Oral fate and stabilization technologies of lactoferrin: a systematic review - Yun-shan Wei; Kun Feng; Shu-fang Li; Teng-gen Hu; Robert J. Linhardt; Min-hua Zong; Hong Wu (Critical Reviews in Food Science and Nutrition, 2022)

Halomonas faecis sp. nov., a halophilic bacterium isolated from human faeces - Zhu-Xiang Liu; Jin-Hua Chen; Ling-Ling Yang; Yu-Zhou Feng; Li-Ying Deng; Jian-Wu He; Shu-Kun Tang; Yi-Guang Chen (Extremophiles, 2022)

A neuropsin-based optogenetic tool for precise control of Gq signaling - Ruicheng Dai; Tao Yu; Danwei Weng; Heng Li; Yuting Cui; Zhaofa Wu; Qingchun Guo; Haiyue Zou; Wenting Wu; Xinwei Gao; Zhongyang Qi; Yuqi Ren; et al. (Science China Life Sciences, 2022)

Remarkable effects of microbial factors on soil phosphorus bioavailability: A country‐scale study - Jing‐li Lu; Pu Jia; Shi‐wei Feng; Yu‐tao Wang; Jin Zheng; Shu‐ning Ou; Zhuo‐hui Wu; Bin Liao; Wen‐sheng Shu; Jie‐Liang Liang; Jin‐tian Li (Global Change Biology, 2022)
Low soil phosphorus (P) bioavailability causes the widespread occurrence of P‐limited terrestrial ecosystems around the globe. Exploring the factors influencing soil P bioavailability at large spatial scales is critical for managing these ecosystems. However, previous studies have mostly focused on abiotic factors. In this study, we explored the effects of microbial factors on soil P bioavailability of terrestrial ecosystems using a country‐scale sampling effort. Our results showed that soil microbial biomass carbon (MBC) and acid phosphatase were important predictors of soil P bioavailability of agro‐ and natural ecosystems across China although they appeared less important than total soil P. The two microbial factors had a positive effect on soil P bioavailability of both ecosystem types and were able to mediate the effects of several abiotic factors (e.g., mean annual temperature). Meanwhile, we revealed that soil phytase could affect soil P bioavailability at the country scale via ways similar to those of soil MBC and acid phosphatase, a pattern being more pronounced in agroecosystems than in natural ecosystems. Moreover, we obtained evidence for the positive effects of microbial genes encoding these enzymes on soil P bioavailability at the country scale although their effect sizes varied between the two ecosystem types. Taken together, this study demonstrated the remarkable effects of microbial factors on soil P bioavailability at a large spatial scale, highlighting the importance to consider microbial factors in managing the widespread P‐limited terrestrial ecosystems.

Blocking Hepatoma-Derived Growth Factor Attenuates Vasospasm and Neuron Cell Apoptosis in Rats Subjected to Subarachnoid Hemorrhage - Chia-Li Chung; Chieh-Hsin Wu; Yu-Hua Huang; Shu-Chuan Wu; Chee-Yin Chai; Hung-Pei Tsai; Aij-Lie Kwan (Translational Stroke Research, 2022)
Subarachnoid hemorrhage (SAH) is an important subcategory of stroke due to its unacceptably high mortality rate as well as the severe complications it causes, such as cerebral vasospasm, neurological deficits, and cardiopulmonary abnormality. Hepatoma-derived growth factor (HDGF) is a growth factor related to normal development and is involved in liver development and regeneration. This study explored the relationship between SAH and HDGF. Sixty rats were divided into five groups (n = 12/group): (A) control group; (B) rHDGF ab only group [normal animals treated with 50 µM recombinant HDGF antibodies (rHDGF ab)]; (C) SAH group; (D) SAH + pre-rHDGF ab group (SAH animals pre-treated with 50 µM rHDGF ab into the subarachnoid space within 24 h before SAH); and (E) SAH + post-rHDGF ab group (SAH animals post-treated with 50 µM rHDGF ab into the subarachnoid space within 24 h after SAH). At 48 h after SAH, serum and cerebrospinal fluid (CSF) samples were collected to measure the levels of pro-inflammatory factors by ELISA, and rat cortex tissues were used to measure protein levels by western blot analysis. Immunofluorescence staining for Iba-1, GFAP, TUNEL, and NeuN was detected proliferation of microglia and astrocyte and apoptosis of neuron cells. Neurological outcome was assessed by ambulation and placing/stepping reflex responses. Morphology assay showed that pre-treatment and post-treatment with rHDGF ab attenuated vasospasm after SAH. SAH up-regulated the levels of TNF-α, IL-1β, and IL-6 in both the CSF and serum samples, and both pre- and post-treatment with rHDGF ab inhibited the up-regulation of these pro-inflammatory factors, except for the serum IL-6 levels. Western blot analysis demonstrated that SAH up-regulated pro-BDNF and NFκB protein levels, and both pre- and post-treatment with rHDGF ab significantly reduced the up-regulation. The result from immunofluorescence staining showed that SAH induced proliferation of microglia and astrocyte and apoptosis of neuron cells. Both pre- and post-treatment with rHDGF ab significantly attenuated proliferation of microglia and astrocyte and inhibited apoptosis of neuron cells. Furthermore, treatment with rHDGF ab significantly improved neurological outcome. Blocking HDGF attenuates neuron cell apoptosis and vasospasm through inhibiting inflammation in brain tissue at early phase after SAH.

Lineage tracing reveals the origin of Nestin-positive cells are heterogeneous and rarely from ependymal cells after spinal cord injury - Xiaoyu Xue; Muya Shu; Zhifeng Xiao; Yannan Zhao; Xing Li; Haipeng Zhang; Yongheng Fan; Xianming Wu; Bing Chen; Bai Xu; Yaming Yang; Weiyuan Liu; et al. (Science China Life Sciences, 2022)

Discovery of Nanos1 and Nanos2/3 as Germ Cell Markers During Scallop Gonadal Development - Liangjie Liu; Tian Liu; Shaoxuan Wu; Yajuan Li; Huilan Wei; Lijing Zhang; Ya Shu; Yaxin Yang; Qiang Xing; Shi Wang; Lingling Zhang (Marine Biotechnology, 2022)

Epigenetic inactivation of ACAT1 promotes epithelial-mesenchymal transition of clear cell renal cell carcinoma - Peipei Han; Shu Wu; Limei Li; Danping Li; Jun Zhao; Haishan Zhang; Yifang Wang; Xuemin Zhong; Zhe Zhang; Ping Li; Liudmila Matskova; Xiaoying Zhou (Genes & Genomics, 2022)

Functional traits explain the consistent resistance of biodiversity to plant invasion under nitrogen enrichment - Shao‐peng Li; Pu Jia; Shu‐ya Fan; Yingtong Wu; Xiang Liu; Yani Meng; Yue Li; Wen‐sheng Shu; Jin‐tian Li; Lin Jiang (Ecology Letters, 2022)
Elton's biotic resistance hypothesis, which posits that diverse communities should be more resistant to biological invasions, has received considerable experimental support. However, it remains unclear whether such a negative diversity–invasibility relationship would persist under anthropogenic environmental change. By using the common ragweed ( Ambrosia artemisiifolia ) as a model invader, our 4‐year grassland experiment demonstrated consistently negative relationships between resident species diversity and community invasibility, irrespective of nitrogen addition, a result further supported by a meta‐analysis. Importantly, our experiment showed that plant diversity consistently resisted invasion simultaneously through increased resident biomass, increased trait dissimilarity among residents, and increased community‐weighted means of resource‐conservative traits that strongly resist invasion, pointing to the importance of both trait complementarity and sampling effects for invasion resistance even under resource enrichment. Our study provides unique evidence that considering species’ functional traits can help further our understanding of biotic resistance to biological invasions in a changing environment.

Association between maternal exposure to PM10 and risk of anorectal atresia/stenosis in offspring: a population-based case-control study in Liaoning Province, China - Tie-Ning Zhang; Qi-Jun Wu; Yan-Hong Huang; Jing Li; Zong-Jiao Chen; Li-Li Li; Yan-Ling Chen; Shu Liu; Cheng-Zhi Jiang; Yu-Hong Zhao (Environmental Science and Pollution Research, 2022)

Risk and protection strategies of Amolops wuyiensis intestine against gastrointestinal nematode ( Cosmocercoides wuyiensis n. sp.) infection - Yilin Shu; Yunyun Xie; Shikun Li; Liming Cai; Ying Liu; Yalin Feng; Jun He; Huijuan Zhang; Menglong Ran; Qina Jia; Hailong Wu; Linming Lu (Environmental Microbiology, 2022)
Summary Anuran amphibians are susceptible to infection by intestinal nematodes, but the damage and response mechanisms that occur in their intestines after infection are only partially understood. In this study, the intestinal disruption and response mechanisms in Amolops wuyiensis frogs infected with Cosmocercoides wuyiensis n. sp. were revealed through analysis of the intestinal histopathology, digestive enzyme activity, transcriptome and intestinal microbiota. Tissue section analysis showed histological damage and inflammation in the infected intestine, and the digestive enzyme activity indicated a decrease in digestion and absorption of some nutrients. We found that infection led to differences in the intestinal microbiota composition, including lower diversity and symbiotic relationships. The greater relative abundance of the genera Burkholderia and Rhodococcus may enhance intestinal immunity to resist pathogenic infections. A comparison of the transcriptomes of infected and uninfected intestines revealed 1055 differentially expressed genes. GO enrichment and KEGG pathways analyses suggested that the guts of infected C . wuyiensis n. sp. show enhanced complement activation, cell adhesion molecule function, NOD‐like receptor signalling pathway activity and other innate immunity responses. Among the adaptive immune responses, the intestinal immune network for IgA production was significantly enriched, and the expression of IL‐17D and transforming growth factor beta‐1 genes were upregulated in the infected intestine. These results imply that C . wuyiens is n. sp. infection of A . wuyiensis intestine may trigger innate and adaptive immune responses, which reduce the post‐infection burden. Furthermore, the intestine of A . wuyiensis may also respond to C . wuyiensis n. sp. infection by increasing metallocarboxypeptidase activity and accelerating smooth muscle contraction.

Single-cell RNA sequencing reveals Nestin+ active neural stem cells outside the central canal after spinal cord injury - Muya Shu; Xiaoyu Xue; Hu Nie; Xianming Wu; Minghan Sun; Lianyong Qiao; Xing Li; Bai Xu; Zhifeng Xiao; Yannan Zhao; Yongheng Fan; Bing Chen; et al. (Science China Life Sciences, 2022)

Overexpression of ORX or MCH Protects Neurological Function Against Ischemic Stroke - Gang Wu; Xi’an Zhang; Shijun Li; Dan Zhou; Jie Bai; Hanxiang Wang; Qing Shu (Neurotoxicity Research, 2022)

Sex-specific mediation of placental inflammatory biomarkers in the effects of prenatal phthalate coexposure on preschooler cognitive development - Hui Gao; Juan Tong; Bei-bei Zhu; Meng-long Geng; Hong Gan; Li Sun; Xiao-yan Wu; Kun Huang; Hui Cao; Wen-wen Liu; Shu-man Tao; Peng Ding; et al. (Environmental Science and Pollution Research, 2022)

Comparative analysis of chemical constituents and bioactivities of the extracts from leaves, seed coats and embryoids of Ginkgo biloba L. - Xuanxuan Chen; Wu Zhong; Changqing Shu; Hong Yang; Erhu Li (Natural Product Research, 2021)

Monthly Streamflow Forecasting Using Convolutional Neural Network - Xingsheng Shu; Wei Ding; Yong Peng; Ziru Wang; Jian Wu; Min Li (Water Resources Management, 2021)

Forest Fragmentation Slows the Decomposition of Coarse Woody Debris in a Subtropical Forest - Chunsheng Wu; Chunjie Shu; Zhijian Zhang; Yanyan Li; Yi Zhang; Yuanqiu Liu (Forest Science, 2021)
Forest fragmentation is increasing rapidly around the world, and edge effects caused by fragmented forests can influence ecosystem functions and ecological processes, including coarse woody debris (CWD) decomposition. Understanding the influencing mechanisms of edge effect on CWD decomposition is needed to assess the effects of forest fragmentation on carbon cycling and storage. We measured rates of mass loss of CWD of Cinnamomum camphora (L.) Presl. and Pinus taiwanensis Hayata over two years at two distances (0−5 m versus 60 m) from a forest edge at two altitudes (215 and 1,400 m a.s.l.), in a subtropical forest. In addition, we determined the microbial community of each CWD segment and the soil beneath via phospholipid fatty acids (PLFAs). Mass loss of CWD 60 m from the forest edge was 15% greater than that at the edge (0–5 m). Mass loss was positively correlated with the abundance of microbial and fauna community and moisture content of the decaying CWD. Distance from edge explained 17.4% of the total variation of the microbial abundance in CWD. The results indicate that the reduced abundance of microbial and fauna communities and moisture content at forest edges influenced rates of decomposition of CWD. Long-term experiments with more tree species and more forest types are needed to better assess edge effects generally.

Effects of climate variables on the transmission of COVID-19: a systematic review of 62 ecological studies - Hu-Li Zheng; Ze-Li Guo; Mei-ling Wang; Chuan Yang; Shu-Yi An; Wei Wu (Environmental Science and Pollution Research, 2021)

The effect of typical geological heterogeneities on the performance of managed aquifer recharge: physical experiments and numerical simulations - Peipeng Wu; Longcang Shu; Jean-Christophe Comte; Qiting Zuo; Mei Wang; Fulin Li; Huawei Chen (Hydrogeology Journal, 2021)

Maternal exposure to sulfur dioxide and the risk of oral clefts in Liaoning Province, China: a population-based case-control study - Fang-Hua Liu; Ze Xing; Ting-Ting Gong; Jia-Yu Zhang; Yan-Hong Huang; Jing Li; Shu Liu; Yan-Ling Chen; Li-Li Li; Cheng-Zhi Jiang; Zong-Jiao Chen; Yu-Hong Zhao; et al. (Environmental Science and Pollution Research, 2021)

Retrieval of sea surface temperature from the scanning microwave radiometer aboard HY-2B - Shu-Bo Liu; Xin-Dong Cui; Yi-Nan Li; Xu Jin; Wu Zhou; Hong-Xing Dang; Hao Li (International Journal of Remote Sensing, 2021)

Bioactive polyketides from the pathogenic fungus of Epicoccum sorghinum - Ching-Chia Chang; Chi-Ying Li; Yi-Hong Tsai; Mohamed El-Shazly; Chien-Kei Wei; Zih-Jie Yang; Shu-Li Chen; Chin-Chung Wu; Yang-Chang Wu; Fang-Rong Chang (Planta, 2021)

Population origin, maternal effects, and hydric conditions during incubation determine embryonic and offspring survival in a desert-dwelling lizard - Yang Wang; Shu-Ran Li; Meng-Yuan Pei; Dan-Yang Wu; Wei-Guo Du (Oecologia, 2021)

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Snapshot of the Pliocene environment of West Kunlun region, Northwest China - Jia Liu; Teng-Xiang Wang; Xin-Wen Zhang; Ai Song; Shu-Feng Li; Jian Huang; Teresa Spicer; Robert A. Spicer; Fei-Xiang Wu; Tao Su; Zhe-Kun Zhou (Palaeobiodiversity and Palaeoenvironments, 2021)

A Highly Selective Turn‐on Fluorescent and Naked‐eye Colourimetric Dual‐channel Probe for Cyanide Anions Detection in Water Samples - Ya Wu; Wen-Min Ding; Juan Li; Geng Guo; Shu-Zhen Zhang; Hao-Ran Jia; Yin-Xia Sun (Journal of Fluorescence, 2021)

Maternal exposure to ambient SO2 and risk of polydactyly and syndactyly: a population-based case-control study in Liaoning Province, China - Yu-Ting Jiang; Ting-Ting Gong; Jia-Yu Zhang; Yan-Hong Huang; Jing Li; Shu Liu; Yan-Ling Chen; Li-Li Li; Cheng-Zhi Jiang; Zong-Jiao Chen; Yu-Hong Zhao; Qi-Jun Wu (Environmental Science and Pollution Research, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Community structure of bacterioplankton and its relationship with environmental factors in the upper reaches of the Heihe River in Qinghai Plateau - Zhang Qian‐Qian; Jian Sheng‐Long; Li Ke‐Mao; Wu Zhen‐Bing; Guan Hong‐Tao; Hao Jin‐Wen; Wang Shu‐Yi; Lin Yao‐Yao; Wang Guo‐Jie; Li Ai‐Hua (Environmental Microbiology, 2021)
Summary Planktonic microorganisms play a key role in the biogeochemical processes of the aquatic system, and they may be affected by many factors. High‐throughput sequencing technology was used in this study to investigate and study the bacterioplankton community of water bodies in the upper reaches of the Heihe River Basin in Qinghai Plateau. Results showed that Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria are the predominant phyla in this river section, while the main genera are Thiomonas , Acidibacillus , Acidocella , Rhodanobacter , Acidithiobacter and Gallionella , which are autochthonous in the acid‐mine drainage. Additionally, total nitrogen, total phosphorus, permanganate index and pH are significantly correlated with the bacterioplankton abundance and are the main limiting factors for the spatial distribution of the bacterioplankton. PICRUSt inferred that the mainstream microbial assemblages had a higher abundance of KOs belong to metabolism of terpenoids and polyketides, while the tributary had higher abundance of KOs belong to the immune system. The relationship between bacterioplankton community composition and environmental factors in the Heihe River basin was discussed for the first time in this study, which provides a theoretical basis for the healthy, orderly development of the water environment in the Heihe River Basin.

Artificial Neural Network-based prediction of glacial debris flows in the ParlungZangbo Basin, southeastern Tibetan Plateau, China - Wang Tang; Hai-tao Ding; Ning-sheng Chen; Shang-Chang Ma; Li-hong Liu; Kang-lin Wu; Shu-feng Tian (Journal of Mountain Science, 2021)

Identification of Amino Acid Dysregulation as a Potential Biomarker for Autism Spectrum Disorder in China - Mingyang Zou; Dexin Li; Luxi Wang; Ling Li; Shu Xie; Yu Liu; Wei Xia; Caihong Sun; Lijie Wu (Neurotoxicity Research, 2020)

Correction to: Protein-bound calcium phosphate in uremic rat serum: a quantitative study - Hong-Xing Fan; Bao-Di Gou; Yu-Xi Gao; Gang Wu; Shu-Hu Liu; Fan Li; Tian-Lan Zhang (JBIC Journal of Biological Inorganic Chemistry, 2020)

Protein-bound calcium phosphate in uremic rat serum: a quantitative study - Hong-Xing Fan; Bao-Di Gou; Yu-Xi Gao; Gang Wu; Shu-Hu Liu; Fan Li; Tian-Lan Zhang (JBIC Journal of Biological Inorganic Chemistry, 2020)

Replication study and meta-analysis indicate a suggestive association of RUNX3 locus with primary biliary cholangitis - Rohil Jawed; Mingming Zhang; Chan Wang; Shu-Han Yang; Peng Jiang; Qiuyuan Wu; Li Li; Weichang Chen; M. Eric Gershwin; Ye Tian; Michael F. Seldin; Xiong Ma; et al. (Immunogenetics, 2020)

Spinal CCL2 Promotes Pain Sensitization by Rapid Enhancement of NMDA-Induced Currents Through the ERK-GluN2B Pathway in Mouse Lamina II Neurons - Hui Zhang; Sui-Bin Ma; Yong-Jing Gao; Jun-Ling Xing; Hang Xian; Zhen-Zhen Li; Shu-Ning Shen; Sheng-Xi Wu; Ceng Luo; Rou-Gang Xie (Neuroscience Bulletin, 2020)
Previous studies have shown that CCL2 (C–C motif chemokine ligand 2) induces chronic pain, but the exact mechanisms are still unknown. Here, we established models to explore the potential mechanisms. Behavioral experiments revealed that an antagonist of extracellular signal-regulated kinase (ERK) inhibited not only CCL2-induced inflammatory pain, but also pain responses induced by complete Freund’s adjuvant. We posed the question of the intracellular signaling cascade involved. Subsequent experiments showed that CCL2 up-regulated the expression of phosphorylated ERK (pERK) and N-methyl D-aspartate receptor [NMDAR] subtype 2B (GluN2B); meanwhile, antagonists of CCR2 and ERK effectively reversed these phenomena. Whole-cell patch-clamp recordings revealed that CCL2 enhanced the NMDAR-induced currents via activating the pERK pathway, which was blocked by antagonists of GluN2B and ERK. In summary, we demonstrate that CCL2 directly interacts with CCR2 to enhance NMDAR-induced currents, eventually leading to inflammatory pain mainly through the CCL2–CCR2–pERK–GluN2B pathway.

New cadinane sesquiterpenoids from Mikania micrantha - Yao Zhang; You-Mei Zeng; You-Kai Xu; Shu-Qi Wu; Shen Li; Hai-Yan Tian; Sheng Yin (Natural Product Research, 2020)

Overexpression of PREX1 in oral squamous cell carcinoma indicates poor prognosis - Shu-Cheng Wan; Hao Wu; Hao Li; Wei-Wei Deng; Yao Xiao; Cong-Cong Wu; Lei-Lei Yang; Wen-Feng Zhang; Zhi-Jun Sun (Journal of Molecular Histology, 2020)

SARS-CoV-2-encoded nucleocapsid protein acts as a viral suppressor of RNA interference in cells - Jingfang Mu; Jiuyue Xu; Leike Zhang; Ting Shu; Di Wu; Muhan Huang; Yujie Ren; Xufang Li; Qing Geng; Yi Xu; Yang Qiu; Xi Zhou (Science China Life Sciences, 2020)

The role of bias correction on subseasonal prediction of Arctic sea ice during summer 2018 - Jiechen Zhao; Qi Shu; Chunhua Li; Xingren Wu; Zhenya Song; Fangli Qiao (Acta Oceanologica Sinica, 2020)

Astrocytic GABAB Receptors in Mouse Hippocampus Control Responses to Behavioral Challenges through Astrocytic BDNF - Ji-Hong Liu; Ze-Lin Li; Yi-Si Liu; Huai-De Chu; Neng-Yuan Hu; Ding-Yu Wu; Lang Huang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2020)

Development of a specific AFLP-based SCAR marker for Chinese Race 34MKG of Puccinia graminis f. sp. tritici - Si Chen; Xue Yang; Wen-gong Huang; Yan Liu; Ying Yu; Guang-wen Wu; Shu-quan Zhang; Tian-ya Li; Yuan-yin Cao (Molecular Biology Reports, 2020)

Improvement of water quality in the Pearl River Estuary, China: a long-term (2008–2017) case study of temporal-spatial variation, source identification and ecological risk of heavy metals in surface water of Guangzhou - Yan-ping Zhao; Rui Wu; Jin-li Cui; Shu-chai Gan; Jia-chuan Pan; Peng-ran Guo (Environmental Science and Pollution Research, 2020)

Coupled data assimilation and parameter estimation in coupled ocean–atmosphere models: a review - Shaoqing Zhang; Zhengyu Liu; Xuefeng Zhang; Xinrong Wu; Guijun Han; Yuxin Zhao; Xiaolin Yu; Chang Liu; Yun Liu; Shu Wu; Feiyu Lu; Mingkui Li; et al. (Climate Dynamics, 2020)

Biological Aerosol Particles in Polluted Regions - Wei Hu; Zihan Wang; Shu Huang; Lujie Ren; Siyao Yue; Ping Li; Qiaorong Xie; Wanyu Zhao; Lianfang Wei; Hong Ren; Libin Wu; Junjun Deng; et al. (Current Pollution Reports, 2020)

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Environmental impact of fluidized solidified silt casting on surrounding water bodies - Yunquan Li; Wei Zhu; Silin Wu; Shi Shu; Yiyan Lv; Yan Cui (Marine Georesources & Geotechnology, 2020)

Analysis of an improved workflow of endoscope reprocessing for bedside endoscopic diagnosis and treatment on COVID-19 patients - Qing Gu; Hua-fen Wang; Ying Fang; Ye Lu; Zhe Shen; Yan Wang; Xin Wu; Li Cen; Yi-shu Chen (Journal of Zhejiang University-SCIENCE B, 2020)

Identification of a novel mutant spp1 that specifies the identity of inflorescence meristem in rice - Peizhou Xu; Asif Ali; Yun Li; Hongyu Zhang; Xiaoqiong Chen; Shaohong Fu; Yang Jin; Zhongwei Zhang; Shu Yuan; Xianjun Wu (Plant Biosystems, 2020)

An automatic evaluation method for retinal image registration based on similar vessel structure matching - Yifan Shu; Yunlong Feng; Guannan Wu; Jieliang Kang; Huiqi Li (Medical & Biological Engineering & Computing, 2020)

Chemical constituents from Ginkgo biloba leaves and their cytotoxicity activity - Penghua Shu; Mengyuan Sun; Junping Li; Lingxiang Zhang; Haichang Xu; Yueyue Lou; Zhiyu Ju; Xialan Wei; Wenming Wu; Na Sun (Journal of Natural Medicines, 2020)

Identification of cadmium-produced lipid hydroperoxides, transcriptomic changes in antioxidant enzymes, xenobiotic transporters, and pro-inflammatory markers in human breast cancer cells (MCF7) and protection with fat-soluble vitamins - Wageh Sobhy Darwish; Zhen Chen; Yonghan Li; Yue Wu; Hitoshi Chiba; Shu-Ping Hui (Environmental Science and Pollution Research, 2020)

Repellent activities of essential oils rich in sesquiterpenoids from Saussurea amara (L.) DC. and Sigesbeckia pubescens Makino against two stored-product insects - Zhi-Hua Li; Yang Wang; Jian-Sheng Sun; Ji-Gang Li; Ke-Xing Zou; Hong Liu; Gui-Xiang Li; Zhi-Zhong Hu; Li-Zheng Nong; Zhen-Xing Ning; Yan Wu; Shu-Shan Du (Environmental Science and Pollution Research, 2019)

Biogas production from anaerobic co-digestion of waste activated sludge: co-substrates and influencing parameters - Qi Yang; Bo Wu; Fubing Yao; Li He; Fei Chen; Yinghao Ma; Xiaoyu Shu; Kunjie Hou; Dongbo Wang; Xiaoming Li (Reviews in Environmental Science and Bio/Technology, 2019)

Microencapsulated β-carotene preparation using different drying treatments - Xiang-yu Li; Mian-bin Wu; Min Xiao; Shu-huan Lu; Zhi-ming Wang; Jian-ming Yao; Li-rong Yang (Journal of Zhejiang University-SCIENCE B, 2019)

Correction to: Vertical Distributions of Suspended Sediment Concentrations in the Turbidity Maximum Zone of the Periodically and Partially Stratified Changjiang Estuary - Zhanhai Li; Jianjun Jia; Yongsheng Wu; Haibo Zong; Guoan Zhang; Ya Ping Wang; Yang Yang; Liang Zhou; Shu Gao (Estuaries and Coasts, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

A New Neural Pathway from the Ventral Striatum to the Nucleus Basalis of Meynert with Functional Implication to Learning and Memory - Si Yun Shu; Gang Jiang; Zhaocong Zheng; Lin Ma; Bin Wang; Qiyi Zeng; Hong Li; Shen Tan; Bin Liu; Wood Yee Chan; Sheng Wu; Chunhua Zhu; et al. (Molecular Neurobiology, 2019)

Vertical Distributions of Suspended Sediment Concentrations in the Turbidity Maximum Zone of the Periodically and Partially Stratified Changjiang Estuary - Zhanhai Li; Jianjun Jia; Yongsheng Wu; Haibo Zong; Guoan Zhang; Yax Ping Wang; Yang Yang; Liang Zhou; Shu Gao (Estuaries and Coasts, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

The impact of N-terminal nonessential domains on the enzymological properties of the pullulanase from a marine Bacillus megaterium - YuLiang Jiao; Yong Wu; HongXu Chen; ShuJun Wang; Li Chen; MingSheng Lv; YaoWei Fang; Shu Liu (Biotechnology Letters, 2019)

Characterization of Cucurbita maxima Fruit Metabolomic Profiling and Transcriptome to Reveal Fruit Quality and Ripening Gene Expression Patterns - He-Xun Huang; Ting Yu; Jun-Xing Li; Shu-Ping Qu; Man-Man Wang; Ting-Quan Wu; Yu-Juan Zhong (Journal of Plant Biology, 2019)

β-Glucanase specific expression in the intestine of transgenic pigs - Li-zeng Guan; Shuai Zhao; Gang Shu; Qing-yan Jiang; Geng-yuan Cai; Zhen-fang Wu; Qian-yun Xi; Yong-liang Zhang (Transgenic Research, 2019)

Distribution characteristics of the additional vertical stress on a shaft wall in thick and deep alluvium: a simulation analysis - Yun Wu; Shu-yun Zhu; Xiao-zhao Li; Hui Zhang; Zhen Huang (Natural Hazards, 2019)

Simulation of interannual variability of summer rainfall over the Tibetan Plateau by the Weather Research and Forecasting model - Xingwen Jiang; Yao Wu; Yueqing Li; Jianchuan Shu (International Journal of Climatology, 2019)
A realistic simulation of rainfall over the Tibetan Plateau (TP) is a big challenge for both regional and global climate models. In this study, we investigate the simulations of summer rainfall over the TP from 1979 to 2010 by the Weather Research and Forecasting (WRF) model with various horizontal resolutions and cumulus schemes, with a focus on the difference in the model's skill in simulating interannual variability of rainfall between early and high summer. The WRF captures spatial pattern of climatological summer mean rainfall over the TP. However, it produces apparent wet bias, especially in southern and eastern edges of the TP. Despite this climatological bias, WRF skilfully reproduces the interannual variability of summer rainfall over the southeastern TP, where maximum rainfall is located. An increase in horizontal resolution or an appropriate cumulus scheme mostly improves the simulation of climatological mean rainfall. However, the phase of interannual variability of simulated rainfall is not sensitive to horizontal resolution and cumulus scheme. Instead, it is sensitive to mechanisms responsible for interannual variability of rainfall. WRF has a high skill in simulating the interannual variability of rainfall over the southeastern TP in July and August, but a low skill in June. The WRF's high skill is attributed to that the interannual variability of July–August rainfall is largely driven by large‐scale circulation, while its low skill for June rainfall may be ascribed to the overestimation of snow and its relationship with rainfall.

Prestack Multi-Gather Simultaneous Inversion of Elastic Parameters Using Multiple Regularization Constraints - Shu Li; Zhenming Peng; Hao Wu (Journal of Earth Science, 2018)

Analysis of slight precipitation in China during the past decades and its relationship with advanced very high radiometric resolution normalized difference vegetation index - Xinyue Li; Yves Balkanski; Zhengfang Wu; Thomas Gasser; Philippe Ciais; Feng Zhou; Laurent Li; Shu Tao; Shushi Peng; Shilong Piao; Rong Wang; Tao Wang; et al. (International Journal of Climatology, 2018)
Precipitation is one of the most important factors determining the occurrence of extreme hydro‐meteorological events and water resource availability. Precipitation in different grades has diverse ecological effects, and slight precipitation (SP, defined as 0.1–1.0 mm/day) is the minimal level among them. In this study, we investigated SP trends from 1961 to 2013, as well as the relationship between SP and advanced very high radiometric resolution (AVHRR) normalized difference vegetation index (NDVI) in China during growing season from 1981 to 2006. The distributions and trends of SP were analysed by calculating the daily precipitation data. The average annual slight precipitation amount (SPA) and the number of slight precipitation days (SPD), derived from 839 monitoring stations in China, show a decreasing trend over the last five decades, which is in agreement with total precipitation (TP) but in different rates. When the trend was analysed seasonally, SP in most stations decreases significantly in September–October–November (SON) and June–July–August (JJA), and the largest decrease is found in SON. About 49.5 and 68.7% of monitoring stations show a decreasing trend in SON, in both SPA and SPD, whereas the trend is less popular in March–April–May (MAM, SPA: 19.7%, SPD: 41.4%) and December–January–February (JJF, SPA: 25.6%, SPD: 43.1%). Moreover, our analysis indicates that the decrease of SP is mainly due to the decrease of SPD as the median amount of daily SP was unchanged over the past five decades (close to 0.3 mm/day). Based on 26‐year (1981–2006) semi‐monthly AVHRR NDVI data and the records of SP data, the relationship between AVHRR NDVI and SP was also investigated. In regions with lower (

Serotonin transporter gene (5-HTT) rs6354 polymorphism, job-related stress, and their interaction in burnout in healthcare workers in a Chinese hospital - Zeyuan Cao; Shuang Wu; Chao Wang; Li Wang; Jair C. Soares; Shu-Chang He; Xiang Yang Zhang (Psychopharmacology, 2018)

The combination of everolimus and terameprocol exerts synergistic antiproliferative effects in endometrial cancer: molecular role of insulin-like growth factor binding protein 2 - Angel Chao; Chiao-Yun Lin; Ren-Chin Wu; Yun-Shien Lee; Li-Yu Lee; Chia-Lung Tsai; Lan-Yan Yang; Hsuan Liu; Shu-Jen Chen; Tzu-Hao Wang; Chyong-Huey Lai (Journal of Molecular Medicine, 2018)

Source tectonic dynamics features of Jiuzhaigou Ms 7.0 earthquake in Sichuan Province, China - Shu-jian Yi; Chun-hao Wu; Yu-sheng Li; Chao Huang (Journal of Mountain Science, 2018)

Characterization, tissue distribution of apela and periprandial, fasting and refeeding changes of apela mRNA in Siberian sturgeon Acipenser baerii - Ni Tang; Jin Hao; Xin Zhang; Yuan B. Wu; Shu Y. Wang; Jin W. Qi; Zhen Z. Tian; Bin Wang; Hu Chen; De F. Chen; Zhi Q. Li (Journal of Fish Biology, 2018)
Apela identified from zebrafish Danio rerio for the first time in 2013 is a novel endogenous peptide ligand for the apelin receptor. To study the role of apela in regulating fish feeding, the complementary (c) DNA sequence of apela of Siberian sturgeon Acipenser baerii was cloned for the first time. The apela cDNA fragment of 836 bp was obtained by cloning. The open reading frame (ORF) of apela was 165 bp encoding a 54 amino acid, including 22 amino acids signal peptide and two proteolytic sites. Phylogenetic tree analysis showed that A. baerii apela was clustered with mammalian and amphibian sequences. A. baerii apela messeger (m)RNA was widely distributed in 11 tissues related to feeding, with high expressions in brain, oesophagus and stomach, especially in the brain. The level of apela mRNA in brain increased significantly after feeding. On the first day of fasting, apela expression in brain was significantly lower than that of the fed group, but after fasting for 3–15 days, the expression of apela in A. baerii brain was significantly higher than that in the fed group. After refeeding apela mRNA expression was obviously reduced. These results suggest that apela plays a bidirectional role in feeding regulation of A. baerii , which may serve as a short‐term satiation factor and a long‐term hunger factor.

Screening wheat genotypes for better performance on reduced phosphorus supply by comparing glasshouse experiments with field trials - De-Yong Zhao; Shu-Song Zheng; Muhammad Kashif Naeem; Jian-Qing Niu; Ning Wang; Zhong-Jian Li; Hui-Lan Wu; Hong-Qing Ling (Plant and Soil, 2018)

Trimetazidine protects against myocardial ischemia/reperfusion injury by inhibiting excessive autophagy - Shiyong Wu; Guanglei Chang; Lei Gao; Dan Jiang; Liyou Wang; Guoxing Li; Xuexiu Luo; Shu Qin; Xueli Guo; Dongying Zhang (Journal of Molecular Medicine, 2018)

Turbulent mixing mediates the photosynthetic activities and biochemical composition of Anabaena: implications for bioengineering - Yan Xiao; Shuqing Zhang; Zhe Li; Xinghua Wu; Shu Wang; Jinsong Guo (Journal of Applied Phycology, 2018)

Expression of BC1 Impairs Spatial Learning and Memory in Alzheimer’s Disease Via APP Translation - Tongmei Zhang; Pei Pang; Zemin Fang; Yu Guo; Hao Li; Xinyan Li; Tian Tian; Xin Yang; Wenting Chen; Shu Shu; Na Tang; Jianhua Wu; et al. (Molecular Neurobiology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

A new DDA model for kinematic analyses of rockslides on complex 3-D terrain - Hong Zhang; Shu-guang Liu; Wei Wang; Lu Zheng; Ying-bin Zhang; Yan-qiang Wu; Zheng Han; Yan-ge Li; Guang-qi Chen (Bulletin of Engineering Geology and the Environment, 2018)

Seismogenic fault and topography control on the spatial patterns of landslides triggered by the 2017 Jiuzhaigou earthquake - Chun-hao Wu; Peng Cui; Yu-sheng Li; Irasema Alcántara Ayala; Chao Huang; Shu-jian Yi (Journal of Mountain Science, 2018)

A 3-D DDA damage analysis of brick masonry buildings under the impact of boulders in mountainous areas - Shu-guang Liu; Zhu-jun Li; Hong Zhang; Wei Wu; Gui-hui Zhong; Sha Lou (Journal of Mountain Science, 2018)

Characteristics and failure mechanism of an ancient earthquake-induced landslide with an extremely wide distribution area - Chao Huang; Yu-sheng Li; Shu-jian Yi; Kai Liu; Chun-hao Wu (Journal of Mountain Science, 2018)

Release and kinetics of arsenic and plumbum in the Songhua River surficial sediments - Guang-Min Liu; Qing An; Li-Juan Wang; Xin Jia; Si-Hui Feng; Shu-Mei Xia; Yi-Ning Wu; Hong Qi (Environmental Science and Pollution Research, 2018)

Viral metagenomics of six bat species in close contact with humans in southern China - Xue-yan Zheng; Min Qiu; Wei-jie Guan; Jin-ming Li; Shao-wei Chen; Ming-ji Cheng; Shu-ting Huo; Zhong Chen; Yi Wu; Li-na Jiang; Qing Chen (Archives of Virology, 2018)

Paleogene marine deposition records of rifting and breakup of the South China Sea: An overview - QianYu Li; GuoXuan Wu; LiLi Zhang; Yu Shu; Lei Shao (Science China Earth Sciences, 2017)

Recent progress in the development of white spot syndrome virus vaccines for protecting shrimp against viral infection - Shuying Feng; Chen Wang; Shu Hu; Qiongya Wu; Aifang Li (Archives of Virology, 2017)

Erratum to: A metagenomics study for the identification of respiratory viruses in mixed clinical specimens: an application of the iterative mapping approach - Yu-Nong Gong; Shu-Li Yang; Guang-Wu Chen; Yu-Wen Chen; Yhu-Chering Huang; Hsiao-Chen Ning; Kuo-Chien Tsao (Archives of Virology, 2017)

A metagenomics study for the identification of respiratory viruses in mixed clinical specimens: an application of the iterative mapping approach - Yu-Nong Gong; Shu-Li Yang; Guang-Wu Chen; Yu-Wen Chen; Yhu-Chering Huang; Hsiao-Chen Ning; Kuo-Chien Tsao (Archives of Virology, 2017)

Nearly a decade‐long repeatable seasonal diversity patterns of bacterioplankton communities in the eutrophic Lake Donghu (Wuhan, China) - Qingyun Yan; James C. Stegen; Yuhe Yu; Ye Deng; Xinghao Li; Shu Wu; Lili Dai; Xiang Zhang; Jinjin Li; Chun Wang; Jiajia Ni; Xuemei Li; et al. (Molecular Ecology, 2017)
Uncovering which environmental factors govern community diversity patterns and how ecological processes drive community turnover are key questions related to understand the community assembly. However, the ecological mechanisms regulating long‐term variations of bacterioplankton communities in lake ecosystems remain poorly understood. Here we present nearly a decade‐long study of bacterioplankton communities from the eutrophic Lake Donghu (Wuhan, China) using 16S rRNA gene amplicon sequencing with MiSeq platform. We found strong repeatable seasonal diversity patterns in terms of both common (detected in more than 50% samples) and dominant (relative abundance >1%) bacterial taxa turnover. Moreover, community composition tracked the seasonal temperature gradient, indicating that temperature is a key environmental factor controlling observed diversity patterns. Total phosphorus also contributed significantly to the seasonal shifts in bacterioplankton composition. However, any spatial pattern of bacterioplankton communities across the main lake areas within season was overwhelmed by their temporal variabilities. Phylogenetic analysis further indicated that 75%–82% of community turnover was governed by homogeneous selection due to consistent environmental conditions within seasons, suggesting that the microbial communities in Lake Donghu are mainly controlled by niche‐based processes. Therefore, dominant niches available within seasons might be occupied by similar combinations of bacterial taxa with modest dispersal rates throughout different lake areas.

The Activities of Adhesion and Biofilm Formation by Candida tropicalis Clinical Isolates Display Significant Correlation with Its Multilocus Sequence Typing - Shuan Bao Yu; Wen Ge Li; Xiao Shu Liu; Jie Che; Jin Xing Lu; Yuan Wu (Mycopathologia, 2017)

Anti-oxidative Responses on Hepatic Tissue of Zebrafish (Danio rerio) in a Short Duration of Sub-lethal Concentrations of Cadmium Exposure - Su Mei Wu; Li-Hsin Shu; Jia-Hao Liu; Ching Hsein Chen (Bulletin of Environmental Contamination and Toxicology, 2017)

First complete genome sequence of parainfluenza virus 5 isolated from lesser panda - Jun-Qiong Zhai; Shao-Lun Zhai; Tao Lin; Jian-Kui Liu; He-Xing Wang; Bing Li; He Zhang; Shu-Zhan Zou; Xia Zhou; Meng-Fan Wu; Wu Chen; Man-Lin Luo (Archives of Virology, 2017)

Impacts of potassium ferrate(VI) on the growth and organic matter accumulation, production, and structural changes in the cyanobacterium Microcystis aeruginosa - Shu-yu Liu; Jingling Xu; Wen-li Chen; Berthold E. David; Minghong Wu; Fang Ma (Environmental Science and Pollution Research, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Activation of group I metabotropic glutamate receptors regulates the excitability of rat retinal ganglion cells by suppressing Kir and I h - Qian Li; Peng Cui; Yanying Miao; Feng Gao; Xue-Yan Li; Wen-Jing Qian; Shu-Xia Jiang; Na Wu; Xing-Huai Sun; Zhongfeng Wang (Brain Structure and Function, 2017)

Improvement of anti-nutritional effect resulting from β-glucanase specific expression in the parotid gland of transgenic pigs - Li-zeng Guan; Jin-shun Cai; Shuai Zhao; Yu-ping Sun; Jing-lan Wang; Yong Jiang; Gang Shu; Qing-yan Jiang; Zhen-fang Wu; Qian-yun Xi; Yong-liang Zhang (Transgenic Research, 2017)

A comparative analysis of five global cropland datasets in China - Miao Lu; WenBin Wu; Li Zhang; AnPing Liao; Shu Peng; HuaJun Tang (Science China Earth Sciences, 2016)

Global mapping of artificial surfaces at 30-m resolution - XueHong Chen; Xin Cao; AnPing Liao; LiJun Chen; Shu Peng; Miao Lu; Jin Chen; WeiWei Zhang; HongWei Zhang; Gang Han; Hao Wu; Ran Li (Science China Earth Sciences, 2016)

Genome-wide profiling of genetic variation in Agrobacterium-transformed rice plants - Wen-xu Li; San-ling Wu; Yan-hua Liu; Gu-lei Jin; Hai-jun Zhao; Long-jiang Fan; Qing-yao Shu (Journal of Zhejiang University-SCIENCE B, 2016)

Anti-oxidative functions of mt2 and smtB mRNA expression in the gills and brain of zebrafish (Danio rerio) upon cadmium exposure - Su Mei Wu; Li-Hsin Shu; Jia-Hao Liu (Fish Physiology and Biochemistry, 2016)

Environmental filtering decreases with fish development for the assembly of gut microbiota - Qingyun Yan; Jinjin Li; Yuhe Yu; Jianjun Wang; Zhili He; Joy D. Van Nostrand; Megan L. Kempher; Liyou Wu; Yaping Wang; Lanjie Liao; Xinghao Li; Shu Wu; et al. (Environmental Microbiology, 2016)
Summary Gut microbiota typically occupy habitats with definable limits/borders that are comparable to oceanic islands. The gut therefore can be regarded as an ‘island’ for the assembly of microbial communities within the ‘sea’ of surrounding environments. This study aims to reveal the ecological mechanisms that govern microbiota in the fish gut ‘island’ ecosystem. Taxonomic compositions, phylogenetic diversity, and community turnover across host development were analyzed via the high‐throughput sequencing of 16S rRNA gene amplicons. The results indicate that the Shannon diversity of gut microbiota in the three examined freshwater fish species all significantly decreased with host development, and the dominant bacterial taxa also changed significantly during host development. Null model and phylogenetic‐based mean nearest taxon distance (MNTD) analyses suggest that host gut environmental filtering led to the assembly of microbial communities in the fish gut ‘island’. However, the phylogenetic clustering of local communities and deterministic processes that governed community turnover became less distinct as the fish developed. The observed mechanisms that shaped fish gut microbiota seemed to be mainly shaped by the gut environment and by some other selective changes accompanying the host development process. These findings greatly enhance our understanding of stage‐specific community assembly patterns in the fish gut ecosystem.

Determination of Dynamic Flexural Tensile Strength of Thermally Treated Laurentian Granite Using Semi-Circular Specimens - Tubing Yin; Pin Wang; Xibing Li; Bangbiao Wu; Ming Tao; Ronghua Shu (Rock Mechanics and Rock Engineering, 2016)

Use of cardioselective β-blockers and overall death and cardiovascular outcomes in patients with COPD: a population-based cohort study - Yaa-Hui Dong; Chia-Hsuin Chang; Li-Chiu Wu; Mei-Shu Lai (European Journal of Clinical Pharmacology, 2016)

Genes encoding Δ8-sphingolipid desaturase from various plants: identification, biochemical functions, and evolution - Shu-Fen Li; Guo-Jun Zhang; Xue-Jin Zhang; Jin-Hong Yuan; Chuan-Liang Deng; Zan-Min Hu; Wu-Jun Gao (Journal of Plant Research, 2016)

Nucleus accumbens hyperpolarization-activated cyclic nucleotide-gated channels modulate methamphetamine self-administration in rats - Dan-Ni Cao; Rui Song; Shu-Zhuo Zhang; Ning Wu; Jin Li (Psychopharmacology, 2016)

A pilot study on using chlorine dioxide gas for disinfection of gastrointestinal endoscopes - Ying Yi; Li-mei Hao; Shu-ren Ma; Jin-hui Wu; Tao Wang; Song Lin; Zong-xing Zhang; Jian-cheng Qi (Journal of Zhejiang University-SCIENCE B, 2016)

Alterations and correlations of the gut microbiome, metabolism and immunity in patients with primary biliary cirrhosis - Long‐Xian Lv; Dai‐Qiong Fang; Ding Shi; De‐Ying Chen; Ren Yan; Yi‐Xin Zhu; Yan‐Fei Chen; Li Shao; Fei‐Fei Guo; Wen‐Rui Wu; Ang Li; Hai‐Yan Shi; et al. (Environmental Microbiology, 2016)
Summary We selected 42 early‐stage primary biliary cirrhosis (PBC) patients and 30 healthy controls (HC). Metagenomic sequencing of the 16S rRNA gene was used to characterize the fecal microbiome. UPLC‐MS/MS assaying of small molecules was used to characterize the metabolomes of the serum, urine and feces. Liquid chip assaying of serum cytokines was used to characterize the immune profiles. The gut of PBC patients were depleted of some potentially beneficial bacteria, such as Acidobacteria, Lachnobacterium sp., Bacteroides eggerthii and Ruminococcus bromii , but were enriched in some bacterial taxa containing opportunistic pathogens, such as γ‐Proteobacteria, Enterobacteriaceae, Neisseriaceae, Spirochaetaceae , Veillonella , Streptococcus , Klebsiella , Actinobacillus pleuropneumoniae , Anaeroglobus geminatus , Enterobacter asburiae , Haemophilus parainfluenzae , Megasphaera micronuciformis and Paraprevotella clara . Several altered gut bacterial taxa exhibited potential interactions with PBC through their associations with altered metabolism, immunity and liver function indicators, such as those of Klebsiella with IL‐2A and Neisseriaceae with urinary indoleacrylate. Many gut bacteria, such as some members of Bacteroides, were altered in their associations with the immunity and metabolism of PBC patients, although their relative abundances were unchanged. Consequently, the gut microbiome is altered and may be critical for the onset or development of PBC by interacting with metabolism and immunity.

Repetitive sequences and epigenetic modification: inseparable partners play important roles in the evolution of plant sex chromosomes - Shu-Fen Li; Guo-Jun Zhang; Jin-Hong Yuan; Chuan-Liang Deng; Wu-Jun Gao (Planta, 2016)

Enhanced butanol production from cassava with Clostridium acetobutylicum by genome shuffling - Shu-Bo Li; Yi Qian; Zheng-Wu Liang; Yuan Guo; Mou-Ming Zhao; Zong-Wen Pang (World Journal of Microbiology and Biotechnology, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Changes in the physiological properties and kinetics of citric acid accumulation via carbon ion irradiation mutagenesis of Aspergillus niger - Wei Hu; Ji-hong Chen; Shu-yang Wang; Jing Liu; Yuan Song; Qing-feng Wu; Wen-jian Li (Journal of Zhejiang University-SCIENCE B, 2016)

Chemical composition and antioxidant activities of the essential oil from Nandina domestica fruits - Shu-Feng Bi; Guang-Qi Zhu; Jie Wu; Zhong-Kang Li; Yong-Zhan Lv; Ling Fang (Natural Product Research, 2016)

Fatal pneumonia cases caused by human adenovirus 55 in immunocompetent adults - Shu-Yan Zhang; Yan-Ping Luo; Dou-Dou Huang; Hang Fan; Qing-Bin Lu; Ying Wo; Gang Chen; Xiao-Ai Zhang; Yan Li; Yi-Gang Tong; Wu-Chun Cao; Wei Liu (Infectious Diseases, 2016)

The Ephrin-A5/EphA4 Interaction Modulates Neurogenesis and Angiogenesis by the p-Akt and p-ERK Pathways in a Mouse Model of TLE - Yi Shu; Bo Xiao; Qian Wu; Tiantian Liu; Yang Du; Haiyun Tang; Si Chen; Li Feng; Lili Long; Yi Li (Molecular Neurobiology, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

High prevalence and diversity of viruses of the subfamily Gammaherpesvirinae, family Herpesviridae, in fecal specimens from bats of different species in southern China - Xue-yan Zheng; Min Qiu; Shao-wei Chen; Jian-peng Xiao; Li-zhen Ma; Shan Liu; Jun-hua Zhou; Qiong-hua Zhang; Xing Li; Zhong Chen; Yi Wu; Hui-fang Chen; et al. (Archives of Virology, 2016)

Recovery and characterization of homozygous lines from two sweet orange cultivars via anther culture - Shu-Ming Wang; Hong Lan; Hong-Bo Cao; Qiang Xu; Chun-Li Chen; Xiu-Xin Deng; Wen-Wu Guo (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Corilagin Protects Against HSV1 Encephalitis Through Inhibiting the TLR2 Signaling Pathways In Vivo and In Vitro - Yuan-Jin Guo; Tao Luo; Fei Wu; Huan Liu; Hua-Rong Li; Yuan-Wu Mei; Shu-Ling Zhang; Jun-Yan Tao; Ji-Hua Dong; Yuan Fang; Lei Zhao (Molecular Neurobiology, 2015)

EGCG induces G-CSF expression and neutrophilia in experimental sepsis - Wei Li; Andrew H. Wu; Shu Zhu; Jianhua Li; Rong Wu; John D’Angelo; Haichao Wang (Immunologic Research, 2015)

Rapid cloning and bioinformatic analysis of spinach Y chromosome-specific EST sequences - CHUAN-LIANG DENG; WEI-LI ZHANG; YING CAO; SHAO-JING WANG; SHU-FEN LI; WU-JUN GAO; LONG-DOU LU (Journal of Genetics, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Antigenic variation of the human influenza A (H3N2) virus during the 2014–2015 winter season - Sha Hua; XiYan Li; Mi Liu; YanHui Cheng; YouSong Peng; WeiJuan Huang; MinJu Tan; HeJiang Wei; JunFeng Guo; DaYan Wang; AiPing Wu; YueLong Shu; et al. (Science China Life Sciences, 2015)

Isolation of differentially expressed sex genes in garden asparagus using suppression subtractive hybridization - Chuan-liang Deng; Ning-na Wang; Shu-fen Li; Tian-yu Dong; Xin-peng Zhao; Shao-jing Wang; Wu-jun Gao; Long-dou Lu (Journal of Plant Research, 2015)

The prevalence and determinants of drug-resistance-associated mutations in the HIV-1-infected MSM population of Henan Province in China - Li-Juan Hou; Hong-Wei Wang; Shu-Peng Duan; Ya Zhuo; Yan-Cai Zhou; Hong-Jie Wu; Bao-Sheng Shen (Archives of Virology, 2015)

Identification of differentially expressed genes using digital gene expression profiles in Pyrus pyrifolia Nakai cv. Hosui bud release following early defoliation - Quan-jun Zhang; Shu-tian Tao; Meng Li; Xiao-xiao Qi; Jun Wu; Hao Yin; Jia-lin Deng; Shao-ling Zhang (Tree Genetics & Genomes, 2015)

Late Miocene accelerated exhumation of the Daliang Mountains, southeastern margin of the Tibetan Plateau - Bin Deng; Shu-gen Liu; Eva Enkelmann; Zhi-wu Li; Todd A. Ehlers; Luba Jansa (International Journal of Earth Sciences, 2015)

Smooth muscle 22α facilitates angiotensin II-induced signaling and vascular contraction - Xiao-Li Xie; Xi Nie; Jun Wu; Fan Zhang; Li-Li Zhao; Yan-Ling Lin; Ya-Juan Yin; Hui Liu; Ya-Nan Shu; Sui-Bing Miao; Huan Li; Peng Chen; et al. (Journal of Molecular Medicine, 2015)

The Marginal Division of the Striatum and Hippocampus Has Different Role and Mechanism in Learning and Memory - Si-Yun Shu; Gang Jiang; Qi-Yi Zeng; Bin Wang; Hong Li; Lin Ma; Harry Steinbusch; Cai Song; Wood-Yee Chan; Xu-Hong Chen; Yon-Ming Wu; Rong Bao; et al. (Molecular Neurobiology, 2015)

Human health risk assessment of soil dioxin/furans contamination and dioxin-like activity determined by ethoxyresorufin-O-deethylase bioassay - Yu Bon Man; Ka Lai Chow; Hong Sheng Wang; Xiao Lin Sun; Sheng Chun Wu; Zong Wei Cai; Yuan Kang; Hui Li; Jin Shu Zheng; John P. Giesy; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

Genetic polymorphisms of CYP2D6*10 and the effectiveness of combined tamoxifen citrate and testosterone undecanoate treatment in infertile men with idiopathic oligozoospermia - Kai-fa Tang; Yi-li Zhao; Shang-shu Ding; Qi-fei Wu; Xing-yang Wang; Jia-qi Shi; Fa Sun; Jun-ping Xing (Journal of Zhejiang University-SCIENCE B, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Altered BDNF is correlated to cognition impairment in schizophrenia patients with tardive dyskinesia - Jing Qin Wu; Da Chun Chen; Yun Long Tan; Shu Ping Tan; Li Hui; Men Han Lv; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Effect of auxin, cytokinin and nitrogen on anthocyanin biosynthesis in callus cultures of red-fleshed apple (Malus sieversii f.niedzwetzkyana) - Xiao-Hao Ji; Yan-Ting Wang; Rui Zhang; Shu-Jing Wu; Meng-Meng An; Min Li; Chuan-Zeng Wang; Xiao-Liu Chen; Yan-Min Zhang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

A mutation of Aspergillus niger for hyper-production of citric acid from corn meal hydrolysate in a bioreactor - Wei Hu; Jing Liu; Ji-hong Chen; Shu-yang Wang; Dong Lu; Qing-hua Wu; Wen-jian Li (Journal of Zhejiang University-SCIENCE B, 2014)

Role of SIRT1 in Streptococcus pneumoniae-induced human β-defensin-2 and interleukin-8 expression in A549 cell - Li Lin; Shun-hang Wen; Shu-zhen Guo; Xiao-yan Su; Hu-jun Wu; Lei Chong; Hai-lin Zhang; Wei-xi Zhang; Chang-chong Li (Molecular and Cellular Biochemistry, 2014)

Two Chinese pedigrees for adenomatous polyposis coli: new mutations at codon 1309 and predisposition to phenotypic variations - Dai-Xiang Liao; Bing Li; Xue-Mei Du; Jun-Hui Yu; Hong Chang; Zhi-Qiang Wu; Hao-Jie Hao; You-Xin Wang; Wei-Dong Han; Shu-jun Cheng; Cheng-Hua Luo (Familial Cancer, 2014)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

Three homologous genes encoding functional ∆8-sphingolipid desaturase in Populus tomentosa - Shu-Fen Li; Guo-Jun Zhang; Ying-Chun Yuan; Cong-Hui Wang; Wu-Jun Gao; Chuan-Liang Deng; Long-Dou Lu; Zan-Min Hu (Genes & Genomics, 2014)

Isolation and characterization of microsatellite loci in Euphorbia lamarckii Sweet (Euphorbiaceae) from the Canary Islands - Yan-Shu Li; Ye Sun; Fa-Guo Wang; Fu-Wu Xing (Conservation Genetics Resources, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Circulating cytokines and gastric cancer risk - Meira Epplein; Yong-Bing Xiang; Qiuyin Cai; Richard M. Peek; Honglan Li; Pelayo Correa; Jing Gao; Jie Wu; Angelika Michel; Michael Pawlita; Wei Zheng; Xiao-Ou Shu (Cancer Causes & Control, 2013)

The Effect of Manganese-induced Cytotoxicity on mRNA Expressions of HSP27, HSP40, HSP60, HSP70 and HSP90 in Chicken Spleen Lymphocytes in Vitro - Yihao Zhu; Xinxing Lu; Di Wu; Shaohe Cai; Shu Li; Xiaohua Teng (Biological Trace Element Research, 2013)

Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Fang Liu; Min Wu; Yan-huan Feng; Hui Zhong; Tian-lei Cui; You-qun Huang; Ya-ping Liang; Yong-shu Diao; Li Zang; Ling Li; Jing Zang; Hong-yu Qiu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Hierarchically Clustering to 1,033 Genes Differentially Expressed in Mouse Superior Colliculus in the Courses of Optic Nerve Development and Injury - Qiang Mei; Yan-qi Zhang; Jian-jun Liu; Cheng-ren Li; Xing-shu Chen; Hong-li Li; Mao-lin Qin; Ya-zhou wu; Yun-lai Liu; Wen-qin Cai (Cell Biochemistry and Biophysics, 2013)

Fruit and vegetable intake and the risk of colorectal cancer: results from the Shanghai Men’s Health Study - Emily Vogtmann; Yong-Bing Xiang; Hong-Lan Li; Emily B. Levitan; Gong Yang; John W. Waterbor; Jing Gao; Hui Cai; Li Xie; Qi-Jun Wu; Bin Zhang; Yu-Tang Gao; et al. (Cancer Causes & Control, 2013)

Discoloration of Methyl Orange in the Presence of Schorl and H2O2: Kinetics and Mechanism - Huan-Yan Xu; Tian-Nuo Shi; Li-Cheng Wu; Shu-Yan Qi (Water, Air, & Soil Pollution, 2013)

Cellular boron allocation and pectin composition in two citrus rootstock seedlings differing in boron-deficiency response - Gui-Dong Liu; Rui-Dong Wang; Lei-Chao Liu; Li-Shu Wu; Cun-Cang Jiang (Plant and Soil, 2013)

Cloning and characterization of a novel apolipoprotein gene, apolipoprotein AV, in tree shrews - Guoping Li; Huairong Luo; Guotao Sun; Guisheng Wu; Gang Wu; Yan Wang; Yong Man; Shu Wang; Jian Li; Baosheng Chen (Molecular Biology Reports, 2013)

Nitrate facilitates cadmium uptake, transport and accumulation in the hyperaccumulator Sedum plumbizincicola - Pengjie Hu; Yong-Gen Yin; Satoru Ishikawa; Nobuo Suzui; Naoki Kawachi; Shu Fujimaki; Masato Igura; Cheng Yuan; Jiexue Huang; Zhu Li; Tomoyuki Makino; Yongming Luo; et al. (Environmental Science and Pollution Research, 2013)

Up-regulation of Slc39A2(Zip2) mRNA in peripheral blood mononuclear cells from patients with pulmonary tuberculosis - Yan-ting Tao; Qing Huang; Ya-li Jiang; Xiao-lei Wang; Ping Sun; Yuanyuan Tian; Hai-liang Wu; Min Zhang; Si-bo Meng; Yu-shu Wang; Qing Sun; Lian-ying Zhang (Molecular Biology Reports, 2013)

Microdissection and painting of the Y chromosome in spinach (Spinacia oleracea) - Chuan-liang Deng; Rui-yun Qin; Ying Cao; Jun Gao; Shu-fen Li; Wu-jun Gao; Long-dou Lu (Journal of Plant Research, 2013)

Selection and validation of suitable reference genes for mRNA qRT-PCR analysis using somatic embryogenic cultures, floral and vegetative tissues in citrus - Zheng Liu; Xiao-Xia Ge; Xiao-Meng Wu; Shu-Jun Kou; Li-Jun Chai; Wen-Wu Guo (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

The Acute and Chronic Effects of Monosodium l-Glutamate on Serum Iron and Total Iron-Binding Capacity in the Jugular Artery and Vein of Pigs - Wu Xin; Shu Xugang; Chunyan Xie; Jun Li; Jiangning Hu; Yu-long Yin; Ze-yuan Deng (Biological Trace Element Research, 2013)

Morphological and molecular cytogenetic characterization of partial octoploid Tritileymus - Jing Wang; Xin-Hong Chen; Wan-Li Du; Ji-Xin Zhao; Jun Wu; Xue-Ni Cheng; Yu-Hui Pang; Qun-Hui Yang; Shu-Hui Liu; Jie Fu (Genetic Resources and Crop Evolution, 2013)

Development and identification of a wheat-Leymus mollis multiple alien substitution line - Ji-Xin Zhao; Wan-Li Du; Jun Wu; Xue-Ni Cheng; Yang Gao; Yu-Hui Pang; Xin-Hong Chen; Shu-Hui Liu; Qun-Hui Yang; Jie Fu (Euphytica, 2013)

Meso-Cenozoic tectonic evolution of the Dangyang Basin, north-central Yangtze craton, central China - Wei Shi; Shu-Wen Dong; Lothar Ratschbacher; Mi Tian; Jian-Hua Li; Guo-Li Wu (International Geology Review, 2013)

Investigation of transferability of BovineSNP50 BeadChip from cattle to water buffalo for genome wide association study - Jun Jing Wu; Li Jun Song; Fang Jie Wu; Xian Wei Liang; Bing Zhuang Yang; D. Claire Wathes; Geoff E. Pollott; Zhangrui Cheng; De Shun Shi; Qing You Liu; Li Guo Yang; Shu Jun Zhang (Molecular Biology Reports, 2013)

The Role of Neuroglobin in the Neuroprotection of Limb Ischemic Preconditioning in Rats - Shu-Qin Li; Wen-Bin Li; Min Zhang; Yu-Zhou Wu; Yu-Yan Hu (Molecular Neurobiology, 2013)

Effects of PGR and ESRα genotypes on the pregnancy rates after embryo transfer in Luxi cattle - Ke-Qiong Tang; Wu-Cai Yang; Bin Pai; Shu-Jing Li; Long Chen; Li-Guo Yang (Molecular Biology Reports, 2013)

Effects of recombinant hIL-2-Luffin P1 immunotoxin combining with arotinoid ethylester on the proliferation and apoptosis of Hut-78 cells - Shu-lei Liu; Wei He; Ru-peng Wang; Zhi Li; Ju Wu; Yun Zhao; Xiao-hong Hu (Molecular & Cellular Toxicology, 2012)

Phylogenetic analysis of the bovine parainfluenza virus type 3 from cattle herds revealing the existence of a genotype A strain in China - Yong-Jun Wen; Xin-Chuan Shi; Feng-Xue Wang; Wei Wang; Shu-Qin Zhang; Guo Li; Ni Song; Li-Zhi Chen; Shi-Peng Cheng; Hua Wu (Virus Genes, 2012)

Quaternary palaeoenvironmental oscillations drove the evolution of the Eurasian Carassius auratus complex (Cypriniformes, Cyprinidae) - Yun Gao; Shu‐Yan Wang; Jing Luo; Robert W. Murphy; Rui Du; Shi‐Fang Wu; Chun‐Ling Zhu; Yan Li; Andrei D. Poyarkov; Sang Ngoc Nguyen; Peng‐Tao Luan; Ya‐Ping Zhang (Journal of Biogeography, 2012)
Aim We sought to reconstruct the spatio‐temporal genetic diversification in goldfish of the Carassius auratus complex, which is widely distributed in Eurasia, to test whether vicariance events or human‐mediated translocations best explained lineage divergence and genogeographical history. Location East Asia and the Oriental islands including Japan, the Ryukyus and Taiwan, and Europe, including Russia and the Czech Republic. Methods We reconstructed the matrilineal history of Eurasian goldfish using 1876 sequences from the partial mitochondrial DNA control region (426 bp) and 191 complete sequences of cytochrome b (1140 bp) from 67 localities representing most of the range of the species. Divergence times were estimated using a Bayesian Markov chain Monte Carlo approach based either on molecular clock data or on the fossil record. Genetic structure and the historical demography of populations were analysed using partial correlation tests and analyses of molecular variance. Results Three lineages had high levels of regional specificity. Lineages A and B from the main islands of Japan differed greatly from lineage C, which occurred on the mainland, Taiwan and the Ryukyus. Lineages A and B had late Pliocene origins. Six geographically constrained sublineages within lineage C had near‐simultaneous mid‐Pleistocene divergences. Main conclusions Genetic structure in the C. auratus complex appears to have been driven by palaeoenvironmental perturbations rather than human translocations. The disappearance of a land bridge in the Tsushima Strait around 3.0 Ma is responsible for the separation of Japanese and continental lineages; the estimated divergence time is 2.75–2.32 Ma. Fujian, China and Vietnam appear to have provided important refugia for the C. auratus complex during glaciation. After warm, moist summer monsoons intensified during the mid‐Pleistocene, goldfish are likely to have dispersed north‐eastwards to recolonize the Ryukyus via Taiwan and northwards to recolonize mainland China.

Boron distribution and mobility in navel orange grafted on citrange and trifoliate orange - Gui-Dong Liu; Rui-Dong Wang; Li-Shu Wu; Shu-Ang Peng; Yun-Hua Wang; Cun-Cang Jiang (Plant and Soil, 2012)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

Structural insights into a human anti-IFN antibody exerting therapeutic potential for systemic lupus erythematosus - Songying Ouyang; Bin Gong; Jin-Zhi Li; Li-Xia Zhao; Wei Wu; Fu-Shun Zhang; Lina Sun; Shu-Jun Wang; Meng Pan; Chuan Li; Wenguang Liang; Neil Shaw; et al. (Journal of Molecular Medicine, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

S-nitrosylation of c-Src via NMDAR-nNOS module promotes c-Src activation and NR2A phosphorylation in cerebral ischemia/reperfusion - Li-Juan Tang; Chong Li; Shu-Qun Hu; Yong-Ping Wu; Yan-Yan Zong; Chang-Cheng Sun; Fa Zhang; Guang-Yi Zhang (Molecular and Cellular Biochemistry, 2012)

Role of mitochondrial pathway in compression-induced apoptosis of nucleus pulposus cells - Fan Ding; Zeng-Wu Shao; Shu-Hua Yang; Qiang Wu; Fei Gao; Li-Ming Xiong (Apoptosis, 2012)

Neuroprotective Effects of Salidroside and its Analogue Tyrosol Galactoside Against Focal Cerebral Ischemia In Vivo and H2O2-Induced Neurotoxicity In Vitro - Tian-yao Shi; Shu-fang Feng; Jiang-hao Xing; Yu-mei Wu; Xiao-qiang Li; Nan Zhang; Zhen Tian; Shui-bing Liu; Ming-gao Zhao (Neurotoxicity Research, 2012)

Characterization of Prototheca zopfii Associated with Outbreak of Bovine Clinical Mastitis in Herd of Beijing, China - Jian Gao; Han-qi Zhang; Jian-zhong He; Yang-hua He; Shu-mei Li; Rong-guang Hou; Qiao-xing Wu; Yang Gao; Bo Han (Mycopathologia, 2012)

Polymorphisms in chicken extracellular fatty acid binding protein gene - Zhi-yuan Zhao; Li Zhang; Bing-wang Du; Ning-xian Cao; Xin-sheng Jiang; Wen-xia Tian; Shu-jun Li; Wei-wei Wu; Chang-hui Ye (Molecular Biology Reports, 2012)

Polymorphisms of the bovine luteinizing hormone/choriogonadotropin receptor (LHCGR) gene and its association with superovulation traits - Wu-Cai Yang; Ke-Qiong Tang; Shu-Jing Li; Lu-Ming Chao; Li-Guo Yang (Molecular Biology Reports, 2012)

Imprinting analysis of porcine DIO3 gene in two fetal stages and association analysis with carcass and meat quality traits - Mu Qiao; Hua-Yu Wu; Ling Guo; Shu-Qi Mei; Peng-Peng Zhang; Feng-E Li; Rong Zheng; Chang-Yan Deng (Molecular Biology Reports, 2012)

Involvement of calcium-sensing receptor in oxLDL-induced MMP-2 production in vascular smooth muscle cells via PI3K/Akt pathway - Hong-Xia Li; Fan-Juan Kong; Shu-Zhi Bai; Wen He; Wen-Jing Xing; Yu-Hui Xi; Guang-Wei Li; Jin Guo; Hong-Zhu Li; Ling-Yun Wu; Rui Wang; Guang-Dong Yang; et al. (Molecular and Cellular Biochemistry, 2012)

Effects of average velocity on the growth and surface topography of biofilms attached to the reclaimed wastewater drip irrigation system laterals - Gui Bing Li; Yun Kai Li; Ting Wu Xu; Yao Ze Liu; Hai Jin; Pei Ling Yang; Da Zhuang Yan; Shu Mei Ren; Zhi Fang Tian (Irrigation Science, 2012)

Simvastatin protects osteoblast against H2O2-induced oxidative damage via inhibiting the upregulation of Nox4 - Wei Huang; Wei-lin Shang; De-hao Li; Wen-wen Wu; Shu-xun Hou (Molecular and Cellular Biochemistry, 2012)

Surface topographic characteristics of suspended particulates in reclaimed wastewater and effects on clogging in labyrinth drip irrigation emitters - Yun Kai Li; Yao Ze Liu; Gui Bing Li; Ting Wu Xu; Hai Sheng Liu; Shu Mei Ren; Da Zhuang Yan; Pei Ling Yang (Irrigation Science, 2012)

The mediating and moderating role of personal strain and coping resource in the relationship between work stressor and quality of life among Chinese nurses - Si-Ying Wu; Huang-Yuan Li; Shu-Juan Yang; Wei Zhu; Xiao-Rong Wang (International Archives of Occupational and Environmental Health, 2012)

Selenium Regulates Gene Expression of Selenoprotein W in Chicken Skeletal Muscle System - Hongfeng Ruan; Ziwei Zhang; Qiong Wu; Haidong Yao; Jinlong Li; Shu Li; Shiwen Xu (Biological Trace Element Research, 2012)

Methyl-1-hydroxy-2-naphthoate, a novel naphthol derivative, inhibits lipopolysaccharide-induced inflammatory response in macrophages via suppression of NF-κB, JNK and p38 MAPK pathways - Jun-Yan Zhang; Hong Jin; Guang-Fa Wang; Peng-Jiu Yu; Shao-Yu Wu; Zheng-Guang Zhu; Zhong-Huang Li; Yuan-Xin Tian; Wei Xu; Jia-Jie Zhang; Shu-Guang Wu (Inflammation Research, 2011)

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

Serum biochemical analysis to indicate pathogenic risk on mouse Mus musculus exposure to source of drinking water - Shi Feng Yun; Xiao Yun Tian; Shu Pei Cheng; Yan Zhang; Ai Min Li; Li Bo Zhang; Xu Xiang Zhang; Li Chen; Bing Wu; Lian Qin Guo; Yun Zhong Shi (Ecotoxicology, 2011)

Risk assessment of polycyclic aromatic hydrocarbons in aquatic ecosystems - Bing Wu; Rui Zhang; Shu-Pei Cheng; Timothy Ford; Ai-Min Li; Xu-Xiang Zhang (Ecotoxicology, 2011)

Comparative analysis of binding affinities between styrene and mammalian CYP2E1 by bioinformatics approaches - Bing Wu; Jie Sun; Shu-Pei Cheng; Ji-Dong Gu; Ai-Min Li; Xu-Xiang Zhang (Ecotoxicology, 2011)

Knockdown of ASIC2a subunit aggravates injury of rat C6 glioma cells in acidosis - Xiao-Yan Liu; Shu-Zhuo Zhang; Xiao-Yun Ma; Hui Wang; Bao-Hong Wu; Hong-Liang Sun; Xin Li; Xiao-Li Wei; Jian-Quan Zheng (Journal of Physiology and Biochemistry, 2011)

Asialoglycoprotein receptor interacts with the preS1 domain of hepatitis B virus in vivo and in vitro - Xi Zhang; Shu-mei Lin; Tian-yan Chen; Min Liu; Feng Ye; Yun-ru Chen; Lei Shi; Ying-li He; Lie-xiu Wu; Shu-qin Zheng; Ying-ren Zhao; Shu-lin Zhang (Archives of Virology, 2011)

Bacillus hunanensis sp. nov., a slightly halophilic bacterium isolated from non-saline forest soil - Yi-Guang Chen; Di-Fei Hao; Qi-Hui Chen; Yu-Qin Zhang; Jian-Ben Liu; Jian-Wu He; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2011)

Bacillus zhanjiangensis sp. nov., isolated from an oyster in South China Sea - Yi-Guang Chen; Song-Ping Hu; Shu-Kun Tang; Jian-Wu He; Jian-Qing Xiao; Hong-Yi Zhu; Wen-Jun Li (Antonie van Leeuwenhoek, 2011)

Simplified RP-HPLC method for multi-residue analysis of abamectin, emamectin benzoate and ivermectin in rice - Xianchuan Xie; Shu Gong; Xiaorong Wang; Yinxing Wu; Li Zhao (Food Additives & Contaminants: Part A, 2011)

Genetic analysis of starch paste viscosity parameters in glutinous rice (Oryza sativa L.) - Chang-Jie Yan; Zhi-Xi Tian; Yu-Wei Fang; Ya-Chun Yang; Jian Li; Sheng-Yuan Zeng; Shi-Liang Gu; Chen-Wu Xu; Shu-Zhu Tang; Ming-Hong Gu (Theoretical and Applied Genetics, 2011)

An MspI polymorphism in the inhibin alpha gene and its associations with superovulation traits in Chinese Holstein cows - Ke-Qiong Tang; Shu-Jing Li; Wu-Cai Yang; Jun-Na Yu; Li Han; Xiang Li; Li-Guo Yang (Molecular Biology Reports, 2011)

An Experimental Study of the Influence of Interfacial Tension on Water–Oil Two-Phase Relative Permeability - Pingping Shen; Bin Zhu; Xian-Bin Li; Yu-Shu Wu (Transport in Porous Media, 2010)

Yaniella soli sp. nov., a new actinobacterium isolated from non-saline forest soil in China - Yi-Guang Chen; Jun Chen; Qi-Hui Chen; Shu-Kun Tang; Yu-Qin Zhang; Jian-Wu He; Wen-Jun Li; Yan-Qi Liu (Antonie van Leeuwenhoek, 2010)

The functional expression of calcium-sensing receptor in the differentiated THP-1 cells - Yu-hui Xi; Hong-zhu Li; Wei-hua Zhang; Li-na Wang; Li Zhang; Yan Lin; Shu-zhi Bai; Hong-xia Li; Ling-yun Wu; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2010)

α-Mangostin Suppresses Phorbol 12-myristate 13-acetate-Induced MMP-2/MMP-9 Expressions via αvβ3 Integrin/FAK/ERK and NF-κB Signaling Pathway in Human Lung Adenocarcinoma A549 Cells - Yuan-Wei Shih; Shang-Tao Chien; Pin-Shern Chen; Jian-Hui Lee; Shu-Hau Wu; Li-Te Yin (Cell Biochemistry and Biophysics, 2010)

Isolation and characterization of polymorphic microsatellite loci in Aquilaria sinensis (Lour.) Gilg - Yan-Ting Zhang; Zheng-Feng Wang; Hong-Lin Cao; Xiao-Yi Li; Lin-Fang Wu; Shu-Bin Zhuo; Xiao-Feng Huang (Conservation Genetics Resources, 2010)

Zhihengliuella salsuginis sp. nov., a moderately halophilic actinobacterium from a subterranean brine - Yi-Guang Chen; Shu-Kun Tang; Yu-Qin Zhang; Zhu-Xiang Liu; Qi-Hui Chen; Jian-Wu He; Xiao-Long Cui; Wen-Jun Li (Extremophiles, 2010)

An SSVEP-Actuated Brain Computer Interface Using Phase-Tagged Flickering Sequences: A Cursor System - Po-Lei Lee; Jyun-Jie Sie; Yu-Ju Liu; Chi-Hsun Wu; Ming-Huan Lee; Chih-Hung Shu; Po-Hung Li; Chia-Wei Sun; Kuo-Kai Shyu (Annals of Biomedical Engineering, 2010)

Treatment strategies for Parkinson’s disease - Hong Yuan; Zhen-Wen Zhang; Li-Wu Liang; Quan Shen; Xiang-Dang Wang; Su-Mei Ren; Hong-Jie Ma; Shu-Jun Jiao; Ping Liu (Neuroscience Bulletin, 2010)

Effects of compressive residual stress on the morphologic changes of fibroblasts - Shu-Li Lin; Jen-Chang Yang; Kuo-Ning Ho; Chau-Hsiang Wang; Chien-Wu Yeh; Haw-Ming Huang (Medical & Biological Engineering & Computing, 2009)

Studying the Interaction of Pirarubicin with DNA and Determining Pirarubicin in Human Urine Samples: Combining Excitation -Emission Fluorescence Matrices with Second-order Calibration Methods - Hong-Yan Zou; Hai-Long Wu; Yan Zhang; Shu-Fang Li; Jin-Fang Nie; Hai-Yan Fu; Ru-Qin Yu (Journal of Fluorescence, 2009)

Marinobacter zhanjiangensis sp. nov., a marine bacterium isolated from sea water of a tidal flat of the South China Sea - Da-Chun Zhuang; Yi-Guang Chen; Yu-Qin Zhang; Shu-Kun Tang; Xiao-Lei Wu; Zhou-Cai Tan; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Single-Trial Analysis of Cortical Oscillatory Activities During Voluntary Movements Using Empirical Mode Decomposition (EMD)-Based Spatiotemporal Approach - Po-Lei Lee; Li-Zen Shang; Yu-Te Wu; Chih-Hung Shu; Jen-Chuen Hsieh; Yung-Yang Lin; Chi-Hsun Wu; Yu-Lu Liu; Chia-Yen Yang; Chia-Wei Sun; Kuo-Kai Shyu (Annals of Biomedical Engineering, 2009)

Phase I clinical trial on intracoronary administration of Ad-hHGF treating severe coronary artery disease - Zhi-Jian Yang; You-Rong Zhang; Bo Chen; Shu-Lan Zhang; En-Zhi Jia; Lian-Sheng Wang; Tie-Bing Zhu; Chun-Jian Li; Hui Wang; Jun Huang; Ke-Jiang Cao; Wen-Zhu Ma; et al. (Molecular Biology Reports, 2009)

Shear-wave splitting in the southeast of Cathaysia block, South China - Yuan Gao; Jing Wu; Jin-An Cai; Yu-Tao Shi; Shu Lin; Ting Bao; Zu-Ning Li (Journal of Seismology, 2009)

Differential belowground allelopathic effects of leaf and root of Mikania micrantha - Ai-Ping Wu; Hua Yu; Shu-Qin Gao; Zhen-Ying Huang; Wei-Ming He; Shi-Li Miao; Ming Dong (Trees, 2009)

Identification of QTLs for the resistance to rice stripe virus in the indica rice variety Dular - Shu-Jun Wu; Huan Zhong; Yong Zhou; Hui Zuo; Li-Hui Zhou; Jin-Yan Zhu; Cao-Qiu Ji; Shi-Liang Gu; Ming-Hong Gu; Guo-Hua Liang (Euphytica, 2009)

Synergistic up-regulation of muscle LIM protein expression in C2C12 and NIH3T3 cells by myogenin and MEF2C - Zhen-Xing Ji; Chao Du; Guo-Sheng Wu; Shu-Yan Li; Guo-Shun An; Yu-Xi Yang; Ru Jia; Hong-Ti Jia; Ju-Hua Ni (Molecular Genetics and Genomics, 2009)

Potential inhibitors against Sclerotinia sclerotiorum, produced by the fungus Myrothecium sp. associated with the marine sponge Axinella sp. - Lian Wu Xie; Shu Mei Jiang; Hong Hui Zhu; Wei Sun; Yong Chang Ouyang; Shi Kun Dai; Xiang Li (European Journal of Plant Pathology, 2008)

Arsenic exposure, urinary arsenic speciation, and the incidence of urothelial carcinoma: a twelve-year follow-up study - Yung-Kai Huang; Ya-Li Huang; Yu-Mei Hsueh; Mo-Hsiung Yang; Meei-Maan Wu; Shu-Yuan Chen; Ling-I Hsu; Chien-Jen Chen (Cancer Causes & Control, 2008)

Opposite effects of α-lipoic acid on antioxidation and long-term potentiation in control and chronically lead-exposed rats - Hui-Li Wang; Xiang-Tao Chen; Shu-Ting Yin; Jin Liu; Ming-Liang Tang; Chuan-Yun Wu; Di-Yun Ruan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Effects of different types of palatal lateral excisions on growth and development of maxilla and dental arch - Jun Wu; Qian Zheng; Bing Shi; Tian Meng; Yan Wang; Sheng Li; Li-shu Liao (Journal of Zhejiang University-SCIENCE B, 2008)

Quercetin relieves chronic lead exposure-induced impairment of synaptic plasticity in rat dentate gyrus in vivo - Pu Hu; Ming Wang; Wei-Heng Chen; Ji Liu; Liang Chen; Shu-Ting Yin; Wu Yong; Ju-Tao Chen; Hui-Li Wang; Di-Yun Ruan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Effects of Cd2+ on transient outward and delayed rectifier potassium currents in acutely isolated rat hippocampal CA1 neurons - Shu Wang; Tai-Ran Xing; Ming-Liang Tang; Wu Yong; Chen-Chen Li; Liang Chen; Hui-Li Wang; Jiu-Lai Tang; Di-Yun Ruan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Prokaryotic expression, purification, and sub-cellular localization of a novel alcohol acyltransferase from apple - Dapeng Li; Gangming Xu; Yunfeng Xu; Tao Wu; Jin Shen; Dequan Li; Huairui Shu (Biotechnology Letters, 2007)

Multiplex specific PCR for identification of the genera Actinopolyspora and Streptomonospora, two groups of strictly halophilic filamentous actinomycetes - Xiao-Yang Zhi; Ling-Ling Yang; Jin-Yuan Wu; Shu-Kun Tang; Wen-Jun Li (Extremophiles, 2007)

Exploration of the emergence of the Victoria lineage of influenza B virus - J.-M. Chen; Y.-J. Guo; K.-Y. Wu; J.-F. Guo; M. Wang; J. Dong; Y. Zhang; Z. Li; Y.-L. Shu (Archives of Virology, 2007)

A review of ocean-atmosphere interaction studies in China - Qinyu Liu; Shu Wu; Jianling Yang; Haibo Hu; Ruijin Hu; Lijuan Li (Advances in Atmospheric Sciences, 2006)

Importin KPNA2, NBS1, DNA Repair and Tumorigenesis - Shu-Chun Teng; Kou-Juey Wu; Shun-Fu Tseng; Chui-Wei Wong; Li Kao (Journal of Molecular Histology, 2006)

Protoplast Fusion between Geotrichum candidium and Phanerochaete chrysosporium to Produce Fusants for Corn Stover Fermentation - Yong Zhang; Shu-Mei Lin; Yu-Jing Zhu; Chang-Jiang Liu; Yan Dong; Fang-Fang Li; Gao-Feng Wu; Hai-Yan Wang; Jing-Hai Zhang (Biotechnology Letters, 2006)

Expression analysis of the NDRG2 gene in mouse embryonic and adult tissues - Xiao-Lan Hu; Xin-Ping Liu; Yan-Chun Deng; Shu-Xin Lin; Lin Wu; Jian Zhang; Li-Feng Wang; Xiao-Bin Wang; Xia Li; Lan Shen; Yuan-Qiang Zhang; Li-Bo Yao (Cell and Tissue Research, 2006)

Status of Biological Studies and Aquaculture Development of the Mud Crab, Scylla serrata, in China: An Experimental Ecological Studies - Wang Gui-zhong; Li Shao-jing; Zeng Chao-shu; Lin Shu-jun; Kong Xiang-hui; Ai Chun-xiang; Lin Qiong-wu (Aquaculture International, 2005)

Inheritance and expression of the cry1Ab gene in Bt (Bacillus thuringiensis) transgenic rice - G. Wu; H. Cui; G. Ye; Y. Xia; R. Sardana; X. Cheng; Y. Li; I. Altosaar; Q. Shu (Theoretical and Applied Genetics, 2002)